Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Lychee seed extract improves growth performance and hepatic health in largemouth bass (Micropterus salmoides) fed high-fat diets: Novel insights from network pharmacology and in vivo validation - Zhenye Lin; Qi Li; Wenjie Chu; Shuling Bai; Shan Xie; Xiaotong Chen; Hao Chen; Zhipeng Zheng; Jiandong Zhu; Yongxin Liu; Yingying Yu; Tengfei Zhu (Aquaculture, 2027)

Strip rotation intercropping enhances maize yield while improving soil quality in soybean strips in semi-arid Northeast China - Shuo Liu; Yuting Zheng; Yun Gu; Rui Liao; Bowei Duan; Jiajun Lin; Zhe Zhang; Wei Bai; Yuanquan Chen; Peng Sui (Soil and Tillage Research, 2026)

Jellyfish-like bilayer solar evaporator for desalination: A coupled heat and mass transfer approach for optimal water supply-evaporation matching - Weibin Bai; Yingxiang Wang; Jialin Chen; Weisong Wang; Haohan Deng; Xinlei Liu; Xiaolu Guo; Rongkun Jian; Yucai Lin (Desalination, 2026)

Thermophilic temperature of 70–80°C optimizes co-reduction of metal bioavailability and antibiotic resistance genes via microbially-associated stabilization and suppressed host-ARG co-occurrence - Xiaoxia Hao; Xueyao Sun; Fengshuo Yu; Shuyue Zhang; Hongxi Qian; Li Zhu; Lin Bai (Bioresource Technology, 2026)

A combined computational and functional approach identifies FBLN5 as an amino acid metabolism-related gene and suppressing colorectal cancer progression - Jiezhi Chen; Yang Bai; Shiyi Liu; Changwei Lin (Molecular Genetics and Genomics, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

A novel time-aware attention-enhanced transformer to prediction harmful algal Bloom's occurrence - Liye Song; Shengjun Xu; Jingyu Lin; Zhihui Bai (Marine Pollution Bulletin, 2026)

Biostratigraphic and paleobiogeographic significance of two cap-shaped fossil groups from the Cambrian Xinji Formation, North China: Evidence for North China–Australia faunal links - Meng Gong; Hong Hua; Yang Hou; Xinzi Wang; Song Zhang; Zihui Wu; Xueting Wang; Ling Yu; Yan Tan; Jinzhou Luo; Lin Bai (Journal of Asian Earth Sciences, 2026)

Characterization of phosphorylated whey protein and its hydrolytic insoluble peptide aggregates - Hui Yang; Ru Lin; Yinuo Xiao; Xuan Shang; Shanshan Bai (International Dairy Journal, 2026)

Phosphatized heterotrophic protists from the Ediacaran–Cambrian transition in South China: New evidence for evolutionary continuity - Jinzhou Luo; Song Zhang; Xiao Min; Hong Hua; Meng Gong; Qiaokun Dai; Lin Bai; Yang Hou; Xinzi Wang; Xueting Wang; Zihui Wu (Gondwana Research, 2026)

Experimental study on the effect of N2 injection pressure on the displacement kinetics of coal containing CH4 - Yang Bai; Ai-Dong Li; Shu-Gang Li; Hang Long; Jian-Kai Shi; Lei-Lei Yang; Yao-Ting Chang; Zhen-Guo Lin; Hai-Fei Lin (Fuel, 2026)

Atmospheric steam outperforms other thermal treatments in elevating the storage stability of oat flour: Revealed via enzyme inactivation, volatile profiles, and lipidomics - Shunzhang Ma; Ting Bai; Jinquan Lin; Lizhen Zhang; Shaojie Zhao; Qun Shen; Sumei Zhou; Dianzhi Hou (Food Research International, 2026)

Study on dimension scaling laws for hybrid steel and GFRP bar reinforced concrete beams under impact loading - Feng Fu; Tian-Qi Xue; Kai Qian; Bai-Chuan Lin (Engineering Structures, 2026)

A pomegranate-inspired B@(NH4)2SiF6@LiClO4 architecture for spatiotemporally coordinated boron combustion - Jiayan Liang; Hongyu Zhang; Jian Zhang; Xuwen Wang; Yangming Wang; Hao Bai; Yi Rong; Kaifeng Lin; Debin Xia; Yulin Yang (Chemical Engineering Journal, 2026)

Numerical insight into single large particle combustion of coal char - Cunmeng Lin; Xinhua Liu; Shanwei Hu; Xue Bai; Lijie Cui; Junrong Yue; Jingjing Wang (Chemical Engineering Journal, 2026)

Synergistic COF/FeOF cascade catalysis enables efficient self-Fenton degradation of β-lactam antibiotics - Zhanpeng Bai; Ziyi Chen; Ziyan Du; Xin Wu; Boyang Li; Ziqian Zhu; Yan Lin (Water Research, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Heterogeneous shipping companies’ responses under emissions trading schemes: An equilibrium analysis - Lerong Xu; Xi Lin; Xiwen Bai (Transportation Research Part D: Transport and Environment, 2026)

A new biostratigraphic marker for Cambrian Stage 3 on the Northern Margin of the Yangtze Platform: Mianxiantubus–Pelagiella subangulata assemblage subzone - Xueting Wang; Hong Hua; Jinzhou Luo; Yang Hou; Meng Gong; Song Zhang; Xinzi Wang; Zihui Wu; Yan Tan; Ling Yu; Lin Bai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The dominant π-π interaction in the adsorption of humic acids onto carbonized cuttlebone: Evidence from UV spectrophotometry and bleaching experiments - Xiaoao Bai; Bin Wang; De Wang; Hui Jiang; Lin Shi; Wenlin Xu; Di Zhang (Journal of Water Process Engineering, 2026)

Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Facile removal of alkali metals with production of potassium fertilizer from iron ore sintering baghouse dust - Tuo Pan; Zhiwei Peng; Shaochang Nie; Lin Xiong; Xiaoguang Bai; Jianzhi Zhang (Journal of Environmental Chemical Engineering, 2026)

Sedimentological and reservoir characteristics of Carboniferous–Permian shales in the northern Songliao Basin and surrounding areas, Northeastern China - Honggang Cheng; Deyong Li; Xuefeng Bai; Lin Jiang; Qinghua Huang; Dehai Wang; Hui Wang; Shujuan Xu; Xueqiong Wu; Wei Duan; Chengzao Jia (Journal of Asian Earth Sciences, 2026)

Seasonal variability and atmospheric drivers of particle-phase PFAS in PM2.5 near a municipal solid waste incineration facility in Nanchang, China - Xiaolu Liu; Dandan Huang; Zehui Zhang; Li Zhang; Xuan Lin; Chunyu Yan; Meng Chen; Renting Nie; Bai Gao; Wenjie Ma; Yuanyuan Liu; Haiyang Zhang (Environmental Pollution, 2026)

Interaction effects of Micropterus salmoides and Edwardsiella piscicida under ammonia nitrogen and nitrite stress - Changyi Lin; Biao Jiang; Jiahao Zhang; Wenhao Wu; Yuan Liang; Xuerou Lan; Jianshan Bai; Youlu Su (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

A starch-bridging strategy for achieving multi-performance synergy of solid-state ionic elastomers toward multimodal sensing - Huidong Liu; Jiang Liu; Meilin Zhang; Zehong Jin; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Carbohydrate Polymers, 2026)

Long-term variability of PM2.5 and its driving mechanisms in Xinjiang's Oasis Cities: insights from meteorological and anthropogenic heterogeneity - Wenyu Bai; Xueyan Zhao; Yingying Liu; Lijuan Wang; Wen Yang; Chunmei Geng; Weili Lin (Atmospheric Environment, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

An integrative framework linking substrate composition and physiological trade-offs to black soldier fly larval performance in organic waste valorization - Hongge Wang; Peiqi Yang; Xiaofei Wu; Zhaohai Bai; Lin Ma; Xuan Wang; Marcel Dicke; Feng Zhu (Waste Management, 2026)

Development of a Recombinant Goose Parvovirus VP2 Neutralizing Epitope-Containing Region Vaccine Adjuvanted with IL-2 and FliC for Enhanced Immune Responses and Protection Against Challenge - Qing Wu; Xinyu Li; Jiaxin Li; Ziran Liu; Lin Bai; Lin Zhang; Shujing Xia; Di Wu; Yuhan Jin; Xinyuan Shen; Yu Gao; Jingming Wang; et al. (The Veterinary Journal, 2026)

Dynamic characteristics and accumulated plastic deformation prediction of lithium slag filler for road applications based on interpretable machine learning - Hai Shi; Zhenghao Yu; Xiangjin Ji; Kun Yu; Mingzhou Bai; Daming Lin; Yin Cheng (Soil Dynamics and Earthquake Engineering, 2026)

A combined hazard to mariculture: Quality and safety impairment associated with intestinal barrier disruption in fish co-exposed to environmentally relevant microplastics and antibiotics - Lin Zhu; Changlong Cui; Ying Bai; Xuemei Sun; Qi Sui; Nurzafirah Mazlan; Bin Xia (Journal of Hazardous Materials, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Occurrence of microplastics in farmland around non-ferrous metals sulfide mining areas: Characteristics changes caused by sulfide minerals - Qi Jin; Xinru Li; Lin Bai; Yisheng Liu; Liang Wang; Yanrong Lu; Yingbo Dong; Hai Lin; Yinhai He (Journal of Environmental Sciences, 2026)

LandslideSegFormer: A non-local context-aware dual-branch network for accurate small-scale landslide segmentation from remote sensing imagery - Xuemei Lee; Lin Bai; Dinghong Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

New critical nitrogen dilution curve for brewing sorghum in Southwestern China based on a Bayesian hierarchical model - Lin Yang; Yifan Zhou; Zilong Bai; Haoran Zhang; Jie Wang (European Journal of Agronomy, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

Identification of Novel Polysaccharide from Myxococcus xanthus and its Function in Developmental Sporulation - Lin Liu; Songchen Jiang; Guirong Yang; Wenming Chang; Jin Lin; Lujun Zhang; Yijia Xu; Xinyu Li; Jie Bai; Lei Zhang; Xianfeng Ye; Yan Huang; et al. (Current Microbiology, 2026)

Spatiotemporal characterization of land deformation in the Fenwei Basin using multi-source SAR data - Lin Bai; Shuyi Zhang; Zhaoxia Miao; Zhimin Zhang (Advances in Space Research, 2026)

Unraveling the spatial paradox of multi-hazard mitigation: divergent impacts of urban form and function on heat and pluvial flood hazards - Bomeng Wu; Rui Sun; Zhaoren Wang; Ye Tian; Lanyu Qin; Hezi Bai; Mengyuan Chen; Huocheng Lin; Shuang Li; Shuanning Zheng (Natural Hazards, 2026)

Context-dependent coupling between rhizosphere biochemical activation and SOC enrichment in croplands: a global meta-analysis - Ya-Jun Cheng; Jie-Yu-Xin Kang; Chun-Yan Li; Bai-Jian Lin; Yun Zhang; Jian-Ying Qi (Plant and Soil, 2026)

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Mechanical response and optimized design of steel pipe composite piles in coastal soft-over-hard strata - Zengming Hao; Xiaoyu Bai; Nan Yan; Jianyong Han; Ling Zhang; Lin Cui; Yamei Zhang (Ocean Engineering, 2026)

New insights into the sclerite ultrastructure and affinity of early Cambrian maikhanellids from South China - Yang Hou; Hong Hua; Jin-Zhou Luo; Meng Gong; Xin-Zi Wang; Lin Bai; Zi-Hui Wu; Xue-Ting Wang; Song Zhang (Palaeoworld, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

Dipole driven interfacial coupling in COF/Bi2Fe4O9 S-scheme heterojunctions greatly boosts PMS activation for neonicotinoids degradation - Sai Bai; Wenzhen Lu; Lin Yang; Congcong Duan; Zhixuan Wang; Yan Shao; Tianjiao Xia; Lingyan Zhu (Journal of Hazardous Materials, 2026)

Novel ex-situ functionalized bacterial cellulose-based packaging films with full hydrogen-bonded network for sustainable and bio-safety food preservation - Changqing Zhao; Lang Wu; Jiao Huang; Liguo Yin; Jiawei Wang; Zihao Feng; Lin Bai; Xingxiu Zhao; Zhifeng Zhao; Shengdong Mu (Food Research International, 2026)

Stage-dependent aroma evolution of Liupao tea during long-term storage revealed by molecular sensory science - Lianqing Wang; Yuelan Pang; Ju Zhou; Meihui Huang; Zhichao Lin; Jing Wang; Hengbin Yao; Guohe Chen; Xuexue Zheng; Silei Bai; Jianan Huang; Zhonghua Liu; et al. (Food Chemistry, 2026)

Structure-activity relationships governing the membrane targeted antimicrobial mechanisms of essential oils for food pathogen control - Jinming Dai; Shuang Xue; Mei Bai; Terence Chiu; Tariq Aziz; Fahad Al-Asmari; Rewaa S. Jalal; Haiying Cui; Lin Lin (Food Bioscience, 2026)

Cosmetic exposure and hepatic steatosis: Investigating the role of metals and adipokines - Baihao Lin; Hao Deng; Yingjun Wu; Xiang Nie; Xinqi Jiang; Qiuyu Lin; Jiamin Wu; Shengya He; Yonglin Ye; Shuzhen Zhang; Zixiang Luo; Hang Hu; et al. (Food and Chemical Toxicology, 2026)

Perovskite-based flexible films for high-energy radiation shielding and detection - Jinlong Bai; Weiqiang Gong; Yi Zhao; Zizheng Li; Yi Chang; Ziming Wang; Tingting Liu; Xinci Zhang; Xitian Zhang; Feng Gao; Lin Li (Chemical Engineering Journal, 2026)

Multifunctional BQD interlayer enables high-resolution high-efficiency QLEDs:Eliminating EML void defects and optimizing interfacial carrier transport - Yue Chen; Yuting Bai; Zunxian Yang; Luxi Yuan; Ye Chen; Xudong Jiang; Jiajie Hong; Benfang Liu; Zhiyu Yuan; Jinzhu Gao; Zhezhou Fang; Runsen Yu; et al. (Chemical Engineering Journal, 2026)

A subcellular spatial profiling platform for expanding the drug toxicity window - Liu Yang; Qingjie Bai; Shuyuan Guo; Luyao Hu; Chenghao Bi; Litao Shao; Zihao Lin; Kairui Cui; Shenshen Yang; Jinxia Wei; Liwei Shao; Liwen Han; et al. (Chemical Engineering Journal, 2026)

Mapping and marker development of the rye-derived Hessian fly resistance gene H25 in wheat - Xiaoting Xu; Xuming Liu; Ming-Shun Chen; Amy Bernardo; Paul St. Amand; Xiaomao Lin; Sanzhen Liu; Katherine W. Jordan; Guihua Bai (Theoretical and Applied Genetics, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Acoustic Flutter Processing in the Inferior Colliculus of Awake Marmosets: Complementary Rate Coding Modulated by Acoustic Parameters - Siyi Bai; Xinyuan Cao; Min Xie; Guanglong Sun; Xiaohui Wang; Leilei Zheng; Xinjian Li; Zheng Lin; Lixia Gao (Neuroscience Bulletin, 2026)
The acoustic flutter is processed through complementary monotonic rate coding and cannot be modulated by other acoustic parameters in the auditory cortex (AC). However, it remains unclear how the inferior colliculus (IC) encodes acoustic flutter, especially when changing other acoustic parameters. Here, we recorded IC neural activity in response to acoustic flutter and determined the existence of conjunctive processing between repetition rate and other acoustic parameters. We found that most IC neurons also encode the repetition rate at the flutter range through complementary monotonic rate coding. In addition, although the acoustic parameters did not change their monotonicity, most IC neurons encode both repetition rate and other acoustic parameters, different from the flutter processing in AC. Thus, complementary monotonic rate coding for acoustic flutter was widespread in the auditory system; however, coding specificity for repetition rate increased from IC to AC, and the capacity for conjunctive coding with other acoustic parameters decreased.

Design and Synthesis of Silver Nanoparticles Green Formulated by Garcinia Mangostana Leaf Aqueous Extract: Its Performance in the Treatment of Bladder Cancer as a Potential/promising Anticancer Agent - Runhe Zhu; Shurong Li; Jinglu Bai; Dongye Li; Baiwen Yan; Lin Lu; Zhijun Guo (Journal of Pharmaceutical Innovation, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Subduction-controlled Late Triassic rifting along the northern margin of Gondwana - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Yang Wang; Jun-Pu Lv; Xin-Yu Hou (International Geology Review, 2026)

Deep seismic sounding methods for imaging the fine structure of the Earth’s crust - Yurui Guan; Tao Xu; Zhiming Bai; Jiyan Lin; Dengda Zhu; Jiwen Teng (Science China Earth Sciences, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Sustainable biosynthesis of bacterial nanocellulose from potato processing waste for high-fluidity water-resistant aqueous ink - Dingkang Wei; Yifan Wu; Mingjuan Wu; Yetong Feng; Jie Liu; Tao Chen; Yiran Yan; Yang Bai; Linxu Chen; Jianqun Lin; Jianqiang Lin; Jie Xu; et al. (Process Safety and Environmental Protection, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Targeted metabolomics analysis for discriminating geographical origin of Chardonnay grape and wine at sub-regions in China's Ningxia: Terroir effect - Xiaofeng Yue; Yang Zhang; Xinran Bai; Bo-chen Liu; Yu-lin Fang; Yan-lun Ju (Food Research International, 2026)

Tradeoffs between water and nutrient use efficiency in two dominant plantation species along a precipitation gradient in semiarid Loess Plateau - Lina Wang; Hao Lu; Jing Bai; Jia Yin; Ying Zhou; Yang Gao; Yuanjun Zhu; Yakun Tang; Gao-Lin Wu (Forest Ecology and Management, 2026)

Graphitization-driven interfacial polarization and conductivity in core–shell Fe3O4@hydrochar composites achieving high-performance electromagnetic wave absorption - Lin Wang; Yingshan Deng; Zurong Zhu; Dan Michelle Wang; Dafu Chen; Guanghui Bai; Zhongyi Feng; Yao Han; Yueyao Liu; Jinxia Zhai; Chengyun Ning; Zhengao Wang (Chemical Engineering Journal, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Biomimetic pangolin-scale sustainable cellulose-based composite paper serves as a multifunctional platform for portable radiative cooling - Fengqiong Jiang; Yuancheng Zhang; Zhen Wang; Tao Zheng; Yuntong Liang; Chuanhui Xu; Bai Huang; Lihua Fu; Baofeng Lin (Carbohydrate Polymers, 2026)

Catechol addition reshapes microbial metabolic networks to enhance humification and regulate nitrogen transformation in co-composting of chicken manure and corn straw - Haishi Qi; Xu Bai; Lin Zhang; Zimin Wei (Bioresource Technology, 2026)

Experimental Investigation into the Influence of Water Saturation on the Tensile Failure Behavior of Diaspore-Type Bauxite: Implications for Underground Mining of Bauxite - Defu Zhu; Wenshuo Hu; Yalin Li; Qingsheng Bai; Yongjie Jia; TengFei Fu; Gan Feng; Yujiang Zhang; Xiaosong Sun; Yongqing Lin; Dingwei Sun (Rock Mechanics and Rock Engineering, 2026)

Coactive adaptation to combined drought and UV-B stress in highland barley (qingke) through hormonal and nutrient crosstalk - Noman Shoaib; Liling Liu; Nishbah Mughal; Xiaoyun Bai; Fakhar Zaman; Yan Pan; Juan Zhang; Junjie Pan; Xiaogang Wu; Xiaoming Sun; Lin Zhang; Kaiwen Pan (Plant and Soil, 2026)

The characteristics of wind-blown snow hazards and an in-situ wind tunnel experiment study on snow disaster prevention along railway - Shumao Qiu; Guoce Liu; Hai Shi; Daming Lin; Mingzhou Bai; Jun Hou (Natural Hazards, 2026)

The biocontrol potential of Trichoderma asperellum M1 against kiwifruit soft rot caused by Botryosphaeria dothidea - Qing Tan; Jieyu Li; Qian Zhou; Chenlan Li; Ziqin Bai; Geng Liu; Jieping Lin; Hui Luo; Wei Xue (European Journal of Plant Pathology, 2026)

Multi-strain Bacillus Probiotics has Advantages in Improving Abnormal Behavior and Intestinal Flora in Rats of Autism Spectrum Disorder - Qi-qi Bai; Ji Chen; Lu-lu Dong; Mei-lin Jin; Bo-kai Hu; Yu Gan; Chen-ye You; Jing Hui (Current Microbiology, 2026)

A novel urban boundary layer model integrating lidar measurement and physical equation constraints - Yue Xu; Yi Yang; Xianfeng Yu; Baojun Bai; Kunbo Wen; Lijun Yuan; Xinjun Lin (Urban Climate, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Blade optimization of a tidal current turbine against abrasive wears and cavitation erosion: A numerical and experimental study - Yanjing Gao; Jiaqi Bai; Wenting Chen; Duan Liu; Yonggang Lin (Ocean Engineering, 2026)

An online hierarchical path planning method for morphological and ecological observation of polar icebergs - Zhuo Wang; Lin Zhou; Nan Zhou; Zhongchao Deng; Zhongben Zhu; Yifan Xue; Hongde Qin; Guiqiang Bai; Chong Wang (Ocean Engineering, 2026)

Dynamics of cavitation bubbles induced by whipping motion of flexible bodies with large deformation - Cheng Wang; Wei-Lin Xu; Yue Pan; Li-Xin Bai (Ocean Engineering, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Stable neodymium isotopic composition of the upper continental crust through time from ancient glacial diamictites and Holocene marine sediments - Xiaoxiao Yu; Jianghao Bai; Gangjian Wei; Mang Lin; Roberta L. Rudnick (Geochimica et Cosmochimica Acta, 2026)

Nontargeted screening of carbonyl-containing hormonal residues in meat products for food safety by using intelligent high-resolution mass spectrometry-based workflow - Jiajin Yi; Yuan Wu; Dandan Zhang; Tian Lin; Shiquan Zhou; Caixia Yuan; Hairong Zhang; Chunyan Zhu; Liuxin Dong; Hanwen Bai; Yulin Hu; Alweali Yousif; et al. (Food Chemistry, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

PFAS and adipokines: Decoding their roles in the risk of breast nodules and breast cancer - Mengya Xu; Xinyu Zhu; Yangyang Liu; Xuezhen Liu; Wanlu Liu; Baihao Lin; Yuyu Zheng; Kang Liu; Yue Feng; Nada Alhazmi; Shengtao Ma; Hao Chen; et al. (Environmental Research, 2026)

Identification method of distributed flow-induced loads on pipeline based on Chebyshev orthogonal polynomials and variational mode decomposition - Jinchuan Bai; Lin Zhang; Tao Zhang; Lejia Chen; Haihua Deng; Haotian Chen (Engineering Structures, 2026)

Dual effects of montmorillonite on CO2 hydrate formation kinetics in saline sand–clay systems: Experimental study and growth modeling - Xiran Lin; Ying Teng; Ying Liu; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Jinlong Zhu; Songbai Han; Huiru Sun; Senyou An; Jianbo Zhu (Chemical Engineering Journal, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Anti-aging effects of low-molecular-weight polysaccharide PSP-1-1 from steamed Polygonatum sibiricum via gut microbiota modulation - Chen Zhang; Hongru Lin; Congmin Wei; Xue Long; Shuomeng Bai; Haotian Wu; Xinran Li; Zhou Yang; Yihuai Gao; Hongbing Wang (Carbohydrate Polymers, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Decoupling Risks in the Fringe: An Integrated SOM-PMF Framework for Spatially-Explicit PFAS Source Apportionment Across Surface–Groundwater Interfaces - Xuan Lin; Shengpin Yu; Dandan Huang; Yiwen Pan; Zehui Zhang; Li Zhang; Chunyu Yan; Xiaolu Liu; Bai Gao; Yuanyuan Liu; Wenjie Ma (Water, Air, & Soil Pollution, 2026)

Comparative Transcriptome and Gene-Editing Analyses Reveal the Molecular Mechanism of Albinism in the Taiwanese Loach - Rongyun Li; Xiaohui Bai; Xiaojuan Cao; Shuang Hao; Keming Liu; Zhang Luo; Jian Gao; Yaoxin Wang; Yunbang Zhang; Lin Ma; Jufeng Jiang (Marine Biotechnology, 2026)

Acupuncture improves neurological function in ICH rats via suppression of WNK-SPAK-NKCC1 signaling activation - Bai-Wen Zhang; Lei Zheng; Bing-Lin Kuang; Jia Zheng; Xue-Ping Yu; Xiao-Hong Dai; Wei Zou (Journal of Molecular Histology, 2026)

Nano zero-valent iron-modified biochar regulates soil carbon mineralization and stability across aggregates in alpine degraded grassland - Yao Li; Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Feida Sun; Jinchao Gong; Shijie Zhou; Zhouwen Ma; Chengjing Wu; Lin Liu; Ran Xue; Yue Xiu; et al. (Soil Ecology Letters, 2026)

Dual-phase adhesive secretion in the stalked barnacle Capitulum mitella - Ziquan Zhou; Zewen Zheng; Xiuqin Bai; Xiaozhen Rao; Gang Lin (Biofouling, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Field data-based safety assessment and probabilistic deformation prediction of existing metro tunnels under adjacent excavation - Wei-Bin Chen; Hai-Tong Liu; Yue Chen; Xiang-Sheng Chen; Tao Xu; Jing-Song Bai; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Dual-Interface engineering and solvation structure regulation enable polyether based semi-solid polymer electrolyte in high voltage lithium metal battery - Yu-Jie Ren; Pei-Pei Chen; Kuan-Kuan Tian; Bai-Qin Xiong; Dong-Lin Zhao (Chemical Engineering Journal, 2026)

Corrigendum to “Dissection of denitrification pathways and synergistic degradation mechanisms of functional microbial communities under per- and polyfluoroalkyl substances (PFAS) exposure”. [Biores. Technol. 444 (2026) 133926] - Li Zhang; Dandan Huang; Zehui Zhang; Xiaolu Liu; Xuan Lin; Bai Gao; Yuanyuan Liu; Wenjie Ma; Haiyang Zhang (Bioresource Technology, 2026)

Antibiotic sensitivity as a key Determinant: B. Subtilis Reshapes the Microecology to mitigate antibiotic resistance genes during composting - Xiaoxia Hao; Lijia Jiang; Mengting Chen; Shuo Liu; Li Zhu; Dongmei Jiang; Lin Bai (Bioresource Technology, 2026)

Engineering a temperature-programmable biosensor toolkit for recombinant protein production in Corynebacterium glutamicum - Haofei Xu; Yanbo Li; Yiran Gan; Songzhou Liu; Bin Lin; Shijun Cen; Yankun Yang; Chunli Liu; Xiuxia Liu; Zhonghu Bai (Systems Microbiology and Biomanufacturing, 2026)

Mosses alter soil carbon and nitrogen resources and microbial biomass during desiccation and rehydration - Lumei Xiao; Juan Zhang; Xiaoyun Bai; Kathrin Rousk; Lin Zhang; Xuejing Wang; Xiaogang Wu; Xiaoming Sun; Kaiwen Pan (Plant and Soil, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Development of an “Off-On” Fluorescence Sensing System Based on Nitrogen-Doped Carbon Quantum Dot/Fe³⁺ for Sensitive Detection of Cysteine - Lihao Jiang; Wenjie Dong; Yongjian Pan; Jianyuan Lin; Shancai Guo; Teng Wang; Fuhang Xu; Haili Wang; Chunjie Bai; Lihua Teng; Jianghua Chen (Journal of Fluorescence, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Experimental and numerical investigation of mooring line failure dynamic responses for a 15 MW hybrid floating offshore wind turbine - Hongda Zhang; Lin Bai; Gang Ma; Hairui Jiang; Hailong Chen (Ocean Engineering, 2026)

Numerical investigation of submarine surface scattering and scaling effects under point forces excitation - Xiaoshen Ning; Xiaorui Bai; Xusheng Li; Lin Li; Jianxin Ren; Qing Wang; Jian Hu (Ocean Engineering, 2026)

Obstacle avoidance path tracking control for underwater tracked robots with path-dependent constraints - Xiaolong Yao; Kelin Feng; Kewen Li; Yongming Li; Yu Wang; Xuejian Bai; Wenxing Sun; Yazhou Fan; Zheng Wang; Guohai Lin (Ocean Engineering, 2026)

A multiple-interdependency risk assessment model with time-varying reasoning capabilities for long-distance water diversion projects - Zihan Chen; Boran Zhu; Shilei Zhang; Ruihua Han; Jin Bai; Junqiang Lin; Youzhi Liu; Bo Wang (Journal of Hydrology, 2026)

Ponds greatly influence watershed ecosystem services value: An optimized InVEST model for large-scale - Xiaofen Bai; Chen Lin; Shenmin Wang; Junfeng Xiong; Jinduo Xu; Kun Xue; DanHua Ma; Yijun Tong; Jianchun Chen; Wenzhuo Cui (Journal of Hydrology, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Selective recover of bismuth by amide extractant from chloride leaching of lead anode slime and the mechanism - Jinhua Bai; Manxing Huo; Lin He; Shiwei Wang; Qifeng Wei; Xiulian Ren; Shanshan Wang (Journal of Environmental Chemical Engineering, 2026)

Protist-mediated bacterial community recovery outweighs soil nutrient effects in tidal flats following cordgrass invasion and removal: implications for habitat transition management - Jichen Qiu; Junhong Bai; Zhiyi Lin; Xuehui Zhang; Kegang Zhang; Yujia Zhai; Changhong Xiao; Yaqi Wang (Journal of Environmental Management, 2026)

Surface reflectance in homogeneous regions follows a Gamma distribution: principles, validation and applications - Yuanhong Liao; Yuqi Bai; Yanping You; Jie Wang; Shuang Chen; Ming Lin; Jin Chen; Jing M. Chen; Bing Xu; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Charge-governed ionic essential oil-loaded liposomes for enhanced penetration and removal of Listeria monocytogenes biofilms - Jinming Dai; Mei Bai; Tariq Aziz; Fatma Alshehri; Nada K. Alharbi; Ashwag Shami; Fakhria A. Al-Joufi; Haiying Cui; Lin Lin (Food Research International, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

The synergistic effects of ammonium and phosphorus on higher alcohol biosynthesis in Zygosaccharomyces mellis LGL-1 and its application for wampee/grape winemaking - Chunyun Qu; Zuyue Qi; Shuochun Lin; Jianjun Li; Yu Zeng; Yiyin Xu; Weidong Bai; Gongliang Liu (Food Microbiology, 2026)

Multi-material vibration attenuation metastructure under multidirectional loads - Yu Li; Lin Li; Cuiping Bai; Zhidong Liu; Hualin Fan (Engineering Structures, 2026)

Validation of a numerical model for seismic behavior of wind turbine nacelle components using experimental data - Wei-Hung Hsu; Bai-Yi Huang; Juin-Fu Chai; Fan-Ru Lin (Engineering Structures, 2026)

UAV-based bridge inspection: RAS-YOLO11 for efficient and accurate multi-class surface defect detection - Qiao Chen; Lin Zhou; Zhaolong Bai; Qihang Zhu; Cheng Wang (Engineering Structures, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Genome-wide association mapping of native QTLs for Fusarium head blight resistance in US winter wheat - Ruolin Bian; Yaoguang Li; Yanhong Dong; Xiaomao Lin; Guihua Bai (Theoretical and Applied Genetics, 2026)

Age-related neural inefficiency: fNIRS evidence of prefrontal hyperactivation during emotional response inhibition - Gong-Hong Lin; Dorothy Bai; Mai Thi Thuy Vu; Yi-Jing Huang (GeroScience, 2026)

Moderate warming enhances CO2 concentrating mechanisms in diatoms by increasing CO2: HCO3− uptake ratio - Xuexia Bai; Jia-Zhen Sun; Wanjuan Song; Bixin Zhang; Xin Lin; Bangqin Huang; Ruiping Huang; Kunshan Gao (Algal Research, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Full Manure Recycling Risks an 18% Rise in China's Cropland N 2 O Emissions Without Improved Management - Shidi Ba; Zhaohai Bai; Lin Ma; Davey L. Jones; David R. Chadwick (Global Change Biology, 2026)
Cropland fertilization is the largest anthropogenic source of nitrous oxide (N 2 O‐N) emissions in China and could be mitigated through manure substitution. However, accurate quantification of N 2 O‐N losses under different combinations of manure and chemical fertilizer applications remains challenging due to limited national data, oversimplified methods of estimation, and neglect of the nitrogen (N) source (chemical‐N and manure‐N) interaction effects under mixed fertilization on N 2 O‐N production processes. Using a dataset consisting of 2186 observations across China, we developed N 2 O‐N models for fertilized (chemical fertilizer and manures) croplands incorporating climate, soil, fertilization and cropping variables, with particular emphasis on the manure component, through machine‐learning approaches. Model simulations estimated a median N 2 O‐N flux of 1.1 kg ha −1 and a total national N 2 O‐N loss of 243.7 Gg in 2019, with a hotspot in Northcentral China. During 2000–2019, N 2 O‐N losses were driven mainly by annual total N input. By 2050, merely pursuing 100% manure recycling without considering improved manure‐N use efficiency could lead to an 18% increase in N 2 O‐N losses compared with 2019. Hence, this study provides a high‐resolution modeling framework to predict how developments in manure substitution will affect the magnitude and spatial distribution of N 2 O‐N losses. We also demonstrate that future manure substitution policies will need to promote improved manure nutrient management at the same time as greater manure recycling rates.

CBC3T-3: a novel patient-derived cisplatin-resistant distal cholangiocarcinoma cell line harboring multiple TP53 missense mutations - Jiahui Xi; Mingzhen Bai; Ruyang Zhong; Chongfei Huang; Ruoshui An; Long Gao; Haidong Ma; Liang Tian; Jinyu Zhao; Ningzu Jiang; Xiang He; Leiqing Wang; et al. (Human Cell, 2026)
Distal cholangiocarcinoma (dCCA) is a malignant tumor characterized by a challenging diagnosis, high invasiveness, and extremely poor prognosis. Research on dCCA is limited by the scarcity of reliable patient-derived preclinical tumor models. This study established a novel human distal cholangiocarcinoma cell line, CBC3T-3, and systematically characterized its biological properties, genomic features, and potential for clinical application. This cell line was extracted from postoperative distal cholangiocarcinoma tumor from a 54-year-old male patient. It was stably passaged (> 50 generations) through primary culture and condition optimization, preserving the same pathology as that of the primary tumor. Whole-exome sequencing (WES) confirmed somatic mutations, tumor mutation burden, single-sample clonal structure, driver genes, and drug resistance genes in CBC3T-3 cells, revealing their genomic characteristics. Functional assays demonstrated that CBC3T-3 cells exhibit strong capabilities for proliferation, migration, and invasion in vitro. In a subcutaneous xenograft model in immunodeficient mice, palpable tumor nodules developed within 4 weeks, reflecting the clinical characteristics of rapidly progressive disease. Drug sensitivity analysis revealed that, compared with TFK-1 cells, CBC3T-3 cells presented significantly greater responses to paclitaxel, gemcitabine, and oxaliplatin but relatively poor responses to 5-FU and cisplatin. The integration of drug resistance gene findings from WES suggests that TP53 missense mutations may mediate primary resistance to cisplatin. The establishment of the CBC3T-3 cell line enhances the research toolkit for dCCA. Its genomic characteristics and functional plasticity provide a reliable preclinical tumor model for developing precision therapies and investigating drug resistance mechanisms.

Visco-elastic interface and dynamic response of a lined tunnel in anisotropic rock mass under unloading waves - Xue-Qian Fang; Zhao-Feng Zhong; Bai-Lin Li; Xin-Yu Liu; Ya-Wen Xiong (Soil Dynamics and Earthquake Engineering, 2026)

Mapping wide-area land subsidence from groundwater use in the North China plain by machine learning-based InSAR adjustment - Mi Jiang; Zhou Wu; Xudong Wang; Lin Bai; Zhiwei Li; Zhong Lu (Remote Sensing of Environment, 2026)

Comparing the performance of different hyperspectral satellite imaging spectroscopy in mapping methane point-source emissions - Fei Li; Keer Lin; Yingqi Yan; Shengxi Bai; Qidan Huang; Chenxi Feng; Shiwei Sun; Shaohua Zhao; Wei Zhou; Chunyan Zhou; Jun Lin; Xinwei Zhang; et al. (Remote Sensing of Environment, 2026)

Enhanced valorization of electric arc furnace dust through microwave-carbon-hydrogen coupled reduction: A novel approach for metallurgical waste utilization - Wanlong Fan; Zhiwei Peng; Lin Xiong; Shaochang Nie; Huixian Bai; Guanwen Luo; Tianle Yin; Jianzhi Zhang (Process Safety and Environmental Protection, 2026)

Mechanism study on ultrasonication combined with soybean 11S globulin to improve the quality and flavor compounds of low-salt lamb meat gel - Rong Bai; Hongqing Nie; Jing Xi; Aitmagambetova Madina; Lin Li; Huiyu Han; Shengqi Jiang; Gege Wang; Wu Ding (Meat Science, 2026)

Pyrimidine biosynthesis repression fuels cost and survival of trimethoprim/sulfamethoxazole – Resistant E. coli - Xiaoxia Hao; Guilin Zheng; Huanzhen Li; Shuo Liu; Li Zhu; Dongmei Jiang; Lin Bai (Journal of Hazardous Materials, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Environmental stress sensitivity determines bacterial Mn(II) oxidation - Yaohui Bai; Hui lin; Yuhan Wang; Jinsong Liang; Xue Ning (Journal of Environmental Sciences, 2026)

Early evolution of the Meso-Tethys Ocean: Constraints from Permo-Triassic flysch deposits - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Xin-Yu Hou; Yang Wang; Li-Qiang Zhang (Gondwana Research, 2026)

Electrospinning of gelatin-based composite Nanofibrous coating loaded with Citral and its antibacterial application in chilled meat preservation - Jinming Dai; Mei Bai; Tariq Aziz; Nada K. Alharbi; Ashwag Shami; Fahad Al-Asmari; Fakhria A. Al-Joufi; Haiying Cui; Lin Lin (Food Research International, 2026)

NaCl substitution characteristics of Salicornia plant salt and potential application in sturgeon caviar: focus on antibacterial activity and phospholipids oxidation - Weijia Zhang; Lingxin Kong; Jingqi Shen; Yuanhui Zhao; Yujin Li; Shuang Cong; Jian Li; Jinlin Wang; Fan Bai; Peng Xu; Lin Gao; Xinxing Xu (Food Chemistry, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Redox imbalance and NF-κB activation drives 1,3-diphenylguanidine (DPG)-induced hepatotoxicity in grass carp (Ctenopharyngodon idella): HSP70 as a protective therapeutic target - Siwen Li; Ruijing She; Bixiao Lin; Keman Li; Yiang Bai; Xuan Xiong; Xingchao Liu (Environmental Research, 2026)

Anisotropic eutectogels with ultra-high conductivity: aligned channels endows sensing directionality - Jiang Liu; Wanwan Liu; Zehong Jin; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Chemical Engineering Journal, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Gas-synergistic ferroptosis of tumor cells to activate Mg-mediated immunotherapy - Fanchao Que; Qingdeng Fan; Haobin Cai; Tianshui Bai; Lin Huang; Zehui Wang; Haolong Ma; Xinyu Chen; Bin Ren; Jing Yang; Chunmei Chen; Zhiqin Deng; et al. (Chemical Engineering Journal, 2026)

Dissection of denitrification pathways and synergistic degradation mechanisms of functional microbial communities under per- and polyfluoroalkyl substances (PFAS) exposure - Li Zhang; Dandan Huang; Zehui Zhang; Xiaolu Liu; Xuan Lin; Bai Gao; Yuanyuan Liu; Wenjie Ma; Haiyang Zhang (Bioresource Technology, 2026)

High-fat diet-induced obesity-related hypertension via altered gut microbiota-mediated histone butyrylation - Hui Wang; Yuting Wang; Haojie Wu; Chen Shen; Yaqi Li; Baoling Bai; Xiaodong Sun; Yanyan Liu; Qin Zhang; Lin Shi (Science China Life Sciences, 2026)

Effects of Three Microbiome-Based Therapies on Loperamide-Induced Constipation in Mice by Restoring Intestinal Motility and Modulating the Intestinal Microbiota - Xinfeng Bai; Lin Xu; Kai Wang; Lei Chen; Tianyu Bai; Peipei Li; Weihua Chu; Chao Song (Probiotics and Antimicrobial Proteins, 2026)

The short effect of ambient temperature on childhood asthma and wheezing: a combination of a nested case-control study and a case-crossover study - Jiatao Zhang; Shuoxin Bai; Shaoqian Lin; Yanling Wu; Fangyi Wang; Yuxiu Liang; Zhiping Wang (International Journal of Biometeorology, 2026)

Disruption of sphingolipid metabolism triggers lung vascular inflammation and aging-like changes under hypoxia through VDAC1-mediated mitochondrial DNA release - Jin Xu; YiLing Ge; Bin Zhang; SiYuan He; QingLin Cao; PeiJie Li; YingRui Bu; YunGang Bai; Lin Zhang; GuoDong Tan; Jin Ma; ManJiang Xie (Apoptosis, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

High-Top Shoes Reduce Ankle Inversion Injury Risk: Pressure and Kinematic Analysis during Sudden Inversion - Jialu Zhang; Taoping Bai; Lin Feng; Jiyang Zhang; Siqi Yang; Ming Zhang; Zhongyou Li; Wentao Jiang (Annals of Biomedical Engineering, 2026)

Marine heatwaves drive phytoplankton community shifts and chlorophyll a decline in the Bay of Bengal - Zhihao Yang; Pei Jiang; Yang Liu; Lin Deng; Zhimin Bai; Tuwang Li; Yuchen Liang; Zhongbing Chang; Heng Liu; Jun Zhao (Acta Oceanologica Sinica, 2026)

Vertical distribution of different phase particles in summer topographic clouds over Liupan Mountain - Tong Lin; Zhiliang Shu; Peiyun Deng; Lei Tian; Yanqiao Sun; Le Jia; Ning Cao; Hanbing Bai (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Multi-scale assessment of energy transition and emission patterns in industrial coastal regions - Ying Teng; Mingkun Bai; Xiran Lin; Jiajie Li; Tao Zhang; Shuyang Liu; Senyou An; Liangbin Xu; Pengfei Wang; Songbai Han; Jinlong Zhu; Jianbo Zhu; et al. (Fuel, 2026)

Low freezing point sustainable aviation fuels through asymmetric cycloalkane design enabled by Ru/NiAlOx catalyst - Jian Li; Xiangrui Lin; Ning Mao; Xiaowei Bai; Zhenghua Dai; Fangjing Liu; Yunpeng Zhao (Fuel, 2026)

W-induced reconstruction of NiFe (oxy)hydroxides with abundant O-vacancies as efficient electrocatalysts for water oxidation - Zhiqun Bai; Huifang Chen; Weihao Sha; Junru Lin; Jinyuan Miao; Ao Xie; Junqing Pan; Ran Pang; Kai Yan; Pingyu Wan; Yang Tang (Fuel, 2026)

Substrate-enhanced allometric growth of Phragmites australis improved tailwater purification efficiency in constructed wetlands - Tian Lin; Jia Niu; Weipeng Zhou; Huanlong Bai; Lihong Chen (Ecological Engineering, 2026)

Tin oxide coupling with Cu-LDHs Facilitate the highly efficient oxidation and reduction of complex Haloacetamides water via direct and indirect Electron transfer - Xue Bai; Jiahan Yang; Fengying Zhang; Jyunhong Shen; Huabin Liu; Zhehan Tu; Weixin Lin; Zhuwu Jiang (Desalination, 2026)

A novel blended adsorbent granule of crown ether polymer mixed with Mn-based lithium-ion sieves for efficient lithium recycling from shale gas wastewater - Xifan Li; Xin Li; Mingmei Zheng; Jialin Shi; Lu Yang; Yushun Yang; Guijing Chen; Shengchi Bai; Xiao Lin; Wen Liu; Baicang Liu (Desalination, 2026)

Water vapor-mediated cellulose skeleton enhances liquid-free ion-conductive elastomers for flexible electronics - Zongming Lv; Hongping Li; Meilin Zhang; Yuanyuan Lao; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Chemical Engineering Journal, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

A review of advancements in multicellular composites integrated with structural and functional characteristics: design, preparation and properties - Xiaotian Bian; Ting Zheng; Lili Zhang; Chengying Bai; Xiaohong Zhang; Xin Zhang; Lecheng Lin; Kai Shao; Si Shen; Yingjie Qiao; Xiaodong Wang (Chemical Engineering Journal, 2026)

Stable soil aggregates and complex microbial networks enhances soil quality in saline-alkali agroecosystem - Bangyan Zhang; Jinmin Wu; Rui Bu; Xiaoli Zhang; Xiaolong Bai; Lei Li; Meilin Lin; Yifei Zhang; Xing Xu; Bin Wang (Plant and Soil, 2026)

Salvianolic acid A reduces lipotoxicity injury of cardiomyocytes by orchestrating oxidative stress and inflammation via Akt/Nrf2/NF-κB axis - Lin Li; Siqi Du; Xianghui Meng; Liding Bai; Danni Huang; Fengjie Zhou; Wenwen Li; Xianzhe Qiu; Yulin Qi; Yanyan Wang; Yao Chen; Yuhong Li (Journal of Molecular Histology, 2026)

Evaluation of the multi-scale variability of ocean bottom pressure in a global ocean general circulation model - Jiahui Bai; Jingwei Xie; Zipeng Yu; Jiangfeng Yu; Hailong Liu; Fan Yang; Pengfei Lin; Tao Zhang; Chunxiang Shi; Yun Xiao (Acta Oceanologica Sinica, 2026)

Skin Ulceration in Farmed Leopard Coral Grouper (Plectropomus leopardus) Was Associated with Vibrio spp. and Photobacterium damselae in China - Yunji Xiu; Xiaowan Lin; Lirong Jiang; Zemin Bai; Jinlong Dong; Jinjing Cao; Xiuxiu Tian; Yu Zhang; Wei Wang; Ying Huang; Bo Zhou; Lei Wang; et al. (Fishes, 2026)
The leopard coral grouper (Plectropomus leopardus), an economically important marine fish, is widely farmed in Hainan Province, China. However, intensive farming has led to frequent disease outbreaks, including viral nervous necrosis, vibriosis, and enteritis, with skin ulceration a widespread and significant concern. To identify the pathogen causing skin ulceration, we collected diseased fish from Hainan and conducted histopathological and ultrastructural analyses, parasite examination, viral metagenomic sequencing, and bacterial isolation and identification. The histopathological analysis and ultrastructural observation showed that the diseased P. leopardus displayed marked pathological alterations, with significant hepatic degeneration and necrosis and splenic structural disorganization. Parasites and viruses were both excluded from being the primary pathogen. A total of 79 bacterial strains were isolated from diseased P. leopardus liver tissue, including Vibrio harveyi (38 strains, 48.1%), Vibrio owensii (17 strains, 21.5%), Vibrio rotiferianus (16 strains, 20.3%), and Photobacterium damselae subsp. damselae (8 strains, 10.1%). Infection experiments suggested that all four bacterial species could induce skin ulceration. This study demonstrates that skin ulceration in P. leopardus is associated with multiple bacterial pathogens, refining the previous view that attributed the disease solely to V. harveyi. These findings provide a foundation for developing vaccines and disease-resistant breeding strategies.

Integrating biodiversity hotspots, ecological gradients, and ecosystem services for transboundary conservation in the Gaoligong Mountains - Zhongde Huang; Qiying Wang; Jie Wang; Zhou Fang; Lin Wang; Maroof Ali; Zhangqian Yang; Haoran Chen; Shi Xue; Qin Zhou; Changgao Cheng; Feiling Yang; et al. (Conservation Biology, 2026)
Expanding transboundary protected areas is crucial to biodiversity conservation and maintenance of ecosystem services. Quantifying border gradients of species richness is essential to aligning ecological and management boundaries to enable the gradual integration of biodiversity hotspots in conservation strategies that include cross‐border areas that buffer the effects of extensive infrastructure. For the China–Myanmar border region (Gaoligong Mountains), we developed a conservation plan based on threatened species, ecosystem services, border gradient characteristics (i.e., spatial changes in ecological variables with increasing distance from a boundary), and ecological connectivity of protected areas. Although 20.2% of existing protected areas were in the north, 27.7% of identified priority conservation areas were outside these protected areas and only 2.93% were protected. Threatened plant and animal richness exhibited a positive spatial correlation (coefficient = 0.12), but their richness hotspots were spatially mismatched. The richness of threatened species was positively correlated with carbon storage and soil retention, but negatively correlated with water retention. In contrast, threatened animal diversity showed the opposite pattern. Threatened species richness decreased as distance from the border increased (strong linear relationship, R 2 = 0.95 for plants and 0.59 for animals). Based on our results, we propose an ecological gradient–based conservation strategy that prioritizes areas where the richness of threatened species overlaps in the central and southern regions and that protects biodiversity hotspots and creates corridors. The framework is applicable to other transboundary regions and supports global biodiversity conventions.

Cadzow Filtering Method Based on Adaptive Singular Value Decomposition - Zhong-lin Cao; Dan Wang; Peng-yuan Sun; Le Li; Ding-yu Xiong; Wen Yang; Yin-yu Wen; Jing Bai (Applied Geophysics, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Unveiling the submerged iceberg of semi-volatile organic pollutants in surface water across the Yangtze River Basin - Quanzhen Liu; Xiong Xu; Mengru Yang; Qingwei Bu; Yongchang Xie; Lihua Lin; Lu Bai; Donghong Wang (Water Research, 2026)

DDX21 nuclear-cytoplasmic shuttling recruits RPS18 to viral dsRNA to promote CSFV replication - Bingke Li; Bolun Zhou; Chenchen Sun; Shurou Li; Ye Bai; Ruibo Zhao; Yiwan Song; Yintao He; Lin Yi; Hongxing Ding; Shuangqi Fan; Jinding Chen; et al. (Veterinary Microbiology, 2026)

Mechanical and microstructural degradation of pile-surrounding mudstone induced by dynamic pile driving: A multi-scale experimental study - Jichao Yin; Xiaoyu Bai; Nan Yan; Yamei Zhang; Lin Cui; Yu Cong; Mingyi Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Improving soil organic carbon sequestration through conservation tillage incorporating legume-based crop rotations - Wen-Xuan Liu; Zhuo Shi; Hai-Yan He; Bai-Jian Lin; Cong He; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Soil and Tillage Research, 2026)

Comparison of metabolomic and transcriptomic analyses of Ganping mandarin fruit following on tree storage and postharvest low temperature storage - Xinyu Huang; Luoao Lin; John B. Golding; Penta Pristijono; Su Guo; Youjian Yu; Gang Chen; Dongdao Han; Huqing Yang; Ruihua Bai; Yongxin Li (Postharvest Biology and Technology, 2026)

Sugar-gibberellin crosstalk mediates leaf elongation in rice (Oryza sativa L.) - Jiaqi Bai; Bingjie Liu; Weiyan Zhang; Yan Zhu; Ganghua Li; Zhenghui Liu; Yanfeng Ding; Lin Chen (Plant Science, 2026)

Highly oxidized germacrane-type sesquiterpenoid dimers from Elephantopus tomentosus L.: Structural characterization, DFT calculation and anti-hepatoma potential - Zi-Hao Ge; Si-Hui Mi; Wen-Long Kou; Guo-Dong Yao; Bin Lin; Jian Wang; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2026)

Ecotoxicological risk and environmental assessment of mebendazole: A comprehensive study using freshwater snails as non-target species - Dinghao Li; Ji Wu; Yunyi Hu; Zifeng Zhu; Yao Liao; Yuheng Liu; Yun Huang; Peiying Peng; Du Gao; Zhongdao Wu; Chuan Bai; Xi Sun; et al. (Journal of Hazardous Materials, 2026)

Whole-genome sequencing of Listeria monocytogenes isolated from retail enoki mushrooms in China highlights public health risk - Jianyun Zhao; Lanqi Li; Menghan Li; Dajin Yang; Lin Yan; Yingying Nong; Shaofei Yan; Li Bai (International Journal of Food Microbiology, 2026)

Thermophilic-vermicomposting enhances nitrogen retention and reduces greenhouse gas emissions via microbial gene regulation - Guiling Zheng; Xiaoxia Hao; Binyan Hong; Dongmei Jiang; Hongxi Qian; Lin Bai (International Biodeterioration & Biodegradation, 2026)

Heatwaves exacerbate the effects of early-season drought on peak vegetation growth in the Northern Hemisphere - Shaozhi Lin; Huanjiong Wang; Wenrui Bai; Chengxi Gao; Quansheng Ge (Global and Planetary Change, 2026)

Predicting in-situ CO2 solubility in formation brines using Raman spectroscopy and machine learning: Implications for offshore geological carbon storage - Ying Teng; Yiqi Chen; Xiran Lin; Mingkun Bai; Senyou An; Shuyang Liu; Pengfei Wang; Tao Zhang; Songbai Han; Jinlong Zhu; Jianbo Zhu; Heping Xie (Gas Science and Engineering, 2026)

Unlocking controllable ignition and combustion in onion-structured Al@Na3AlF6@AP composites through Na3AlF6 “Temperature Switch” - Xuwen Wang; Jian Zhang; Hao Bai; Changsheng Tang; Jiayan Liang; Zhe Shi; Kaifeng Lin; Debin Xia; Bowen Tao; Fang Du; Yulin Yang (Fuel, 2026)

A polysaccharide isolated from sea cucumber intestines enhances immunity and modulates gut microbiota and metabolism with efficacy comparable to that from the body wall - Xinyi Jin; Lin Bai; Chen Song; Jingjing Li; Xiaomeng Ren; Fanhua Kong; Chunqing Ai; Shuang Song (Food Bioscience, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Electrochemical synthesis of H2O2 integrates reaction mechanisms, reaction media, mass-transfer effects, and device design - Lin Zhu; Rong Ma; Yixin Bai; Feng Li; Gao-feng Han; Yunfei Bu (Chemical Engineering Journal, 2026)

Bio-inspired coral-like ZnCo-LDH/Co-CAT hierarchical composite for multifunctional flexible pressure sensing and plantar monitoring system integration - Qingzheng Jia; Zelin Bai; Aijia Zhang; Zushan Huang; Wanxing Li; Ling Li; Youwei Zhao; Haijiao Lin; Wenming Zhang (Chemical Engineering Journal, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Hierarchical microstructure PANI@NH4V4O10@CC enables multifunctional pressure sensing and high capacity supercapacitive for self-powered wearable electronics - Yong Wang; Zelin Bai; Wanzhihan Zhang; Hang Li; Ling Li; Youwei Zhao; Haijiao Lin; Chuan Fang; Wenming Zhang (Chemical Engineering Journal, 2026)

Highly stable, temperature- and humidity-responsive eutectogels for long-term sustained release of ClO₂ - Qiao yuan Luo; Tianrui Zhou; Zhen Wang; Yuntong Liang; Lihua Fu; Chuanhui Xu; Bai Huang; Baofeng Lin (Chemical Engineering Journal, 2026)

Hybrid calcium carbonate nanoparticles incorporated with capsaicin for tumor therapy via calcium overload mediated mitochondria damage and endoplasmic reticulum stress - Yiling Li; Yiyin Zhang; Guoqiao Chen; Xiaolong Liu; Qiming Xia; Yixuan Li; Jing Yang; Guoqiao Xu; Jiayi Chen; Jun Chen; Guping Tang; Xiaoxiao Fan; et al. (Chemical Engineering Journal, 2026)

Optimization of bacterial nanocellulose synthesis using surfactants for immobilization of Saccharomyces cerevisiae to enhance resistance to lignocellulose-derived inhibitor - Yetong Feng; Dingkang Wei; Shuai Han; Peihong Chen; Jie Liu; Tao Chen; Yiran Yan; Yang Bai; Linxu Chen; Jianqun Lin; Jianqiang Lin; Zixiang Xu; et al. (Bioresource Technology, 2026)

Promoting effect of aerobic starvation on enhancing biological phosphorus removal system - Zhiwei Fan; Zekai Ren; Yanling Guan; Ling Bai; Haoyu Lin; Ziqi Zhao; Hao Wang; Mingxing Lu; Meijie Zhou; Fuping Li; Wei Zeng (Bioresource Technology, 2026)

Unraveling the impacts of climate factors on leaf area index of Chinese grasslands using interpretable machine learning models - Wei Liu; Chengxi Gao; Shaozhi Lin; Yu Zhou; Wenrui Bai; Junhu Dai; Huanjiong Wang (Theoretical and Applied Climatology, 2026)

Intercropping maize and soybean promotes specialized soil microbial communities and boosts carbon and nitrogen cycling in a semi-arid agroecosystem - Olatunde Pelumi Oladele; Shuo Yao; Ming-Zhu Huang; Yu-Gang Tian; Xin Zhao; Yash Pal Dang; Wei Bai; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Policy responses and spatial adjustments in China's pig production: Impacts on nitrogen losses and socioeconomic costs - Yue Zhao; Jiafa Luo; Ling Liu; Xiangbo Xu; Shuqin Jin; Xiaoming Yang; Zhaohai Bai; Lin Ma (Agricultural Systems, 2026)

Influence of Wake Flow on the Ice Accretion Morphology and Distribution of Twin-Cylinder Structures - Lingxin Tang; Xu Bai; Daolei Wu; Yukui Tian; Xuhao Gang; Baolong Lin (Journal of Marine Science and Engineering, 2025)
Ice accretion on arctic vessels and offshore platforms poses serious threats to navigation and operational safety. Existing research has primarily focused on isolated structures. This study employs a combined approach of numerical simulation and experimental validation. It systematically investigates the icing characteristics of tandem twin-cylinders in wake flow fields. This configuration is common yet rarely studied in real marine environments. The model employs two identical cylinders arranged in tandem. It examines the effects of wind speed, distance, diameter, and wind direction angle on ice accretion morphology and distribution. Validation was conducted through wind tunnel tests at 5 m/s wind speed and 2.0 g/m3 liquid water content. Results demonstrate a significant shielding effect from the upstream cylinder wake. As wind speed increases, the ice mass difference between upstream and downstream cylinders widens. Ice mass shows a nonlinear relationship with distance. Minimum ice accretion on the downstream cylinder occurs at 350–450 mm distance. This results from wake pattern transition. The shielding effect exhibits strong nonlinear dependence on wind direction angle. A deviation of 8.2° increases total ice mass by 242.5%. Multivariable analysis confirms these nonlinear mechanisms persist under coupled distance–wind speed variations. This study provides the first systematic revelation of twin-cylinder icing mechanisms in wake flow fields. It offers a validated predictive tool for anti-icing design of arctic marine structures.

Impact of protist predation on bacterial community traits in river sediments - Qiaojuan Wang; Linhao Zhang; Hui Lin; Jie Mao; Yaohui Bai; Chengzhi Hu; Jiuhui Qu (Water Research, 2025)

Multigenerational exposure reveals differential effects of ocean warming temporal scenarios on mercury toxicity in a marine copepod - Luman Cheng; Zhuoan Bai; Shiru Lin; Jae-Seong Lee; Quanlong Li; Minghua Wang (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Diminishing heavy metal co-resistance aids in antibiotic resistome elimination from livestock manure - Xinyuan Zhang; Xuan Wang; Chunxu Song; Guanyu Zheng; Yubo Cao; Fenghua Wang; Zhaohai Bai; Lin Ma (Journal of Hazardous Materials, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Intercity red meat trade exacerbates the spatial inequality of greenhouse gas emissions and health burdens in China - Yue Zhao; Le Yu; Zhaohai Bai; Lin Ma (Journal of Environmental Management, 2025)

Changes in soil quality and crop productivity along rice cultivation chronosequences in saline-alkali soils - Bangyan Zhang; Jinmin Wu; Xiaolong Bai; Lei Li; Meiling Lin; Xing Xu; Fengju Zhang; Bin Wang (Journal of Environmental Management, 2025)

Trade of crop products contribute to the alleviation of global nitrate leaching risks - Xuchong Chen; Ling Liu; Yu Lu; Xuan Wang; Zhaohai Bai; Lin Ma (Global Environmental Change, 2025)

Glacial-interglacial climate modulates sedimentary sulfur cycling in the Peruvian oxygen minimum zone: Mechanistic insights from pyrite multiple sulfur isotopes - Xiaoxiao Yu; Fang Qian; Xiaomin Lin; Longye Du; Jianghao Bai; Dawei Lv; Yanguang Liu; Gangjian Wei; Mang Lin (Geochimica et Cosmochimica Acta, 2025)

Preparation of sodium alginate/sodium carboxymethyl cellulose composite coating film and evaluation of its effects on mango preservation - Wei Wang; Jiakai Yu; Yuting Huang; Bai-Jun Li; Wenzhu Shen; Wenli Zhang; Yining Xia; Qiong Lin (Food Chemistry, 2025)

Nutritional and functional enhancement of cereal-based foods through lactic acid bacteria Fermentation: Focusing on postbiotics - Xiang Xiao; Ning Shen; Zhengyang Tu; Juan Bai; Yansheng Zhao; Lin Zhu; Zhihong Zhang; Songtao Fan (Food Bioscience, 2025)

Quantitative risk assessment of Listeria monocytogenes in cooked meat products from retail to consumption in China - Xiang Wang; Lisha Liu; Xiao Liu; Yibaina Wang; Yeru Wang; Yan Qi; Shuran Yang; Lin Yan; Dajin Yang; Zhaoping Liu; Jianwen Li; Li Bai (Food Control, 2025)

A review on migration behavior and safety regulation of inorganic nanoparticles in food packaging: Multi-scale mechanisms, risk assessment, and innovative strategies - Jingjing Wang; Xu Liang; Huanhuan Hou; Jing Deng; Qinlu Lin; Wen Li; Jie Bai (Food Control, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Solar spectrum prediction model for improving TMY database used in building performance calculation - Yanyun Zhang; Yajie Dong; Yupeng Wu; Yao Lin; Jinqing Peng; Peng Xue; Gongxun Bai (Energy and Buildings, 2025)

Storm water management model simulations of the non-point source pollution load in the northern Anhui plain - Yun Wan; Mingjun Li; Nan Zhang; Mengwan Lin; Yuxuan Li; Peiqing Huang; Yuqi Feng; Bai Sun; Wei Wei; Shuguang Zhu (Ecohydrology & Hydrobiology, 2025)

Resveratrol-functionalized framework nucleic acid nanoparticles enhance diabetic bone regeneration via targeted pyroptosis intervention - Chuan Ma; Long Bai; Qiumei Li; Yong Li; Fenglin Zhou; Kui Huang; Jingang Xiao; Yunfeng Lin (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Corrigendum to “boosting sustainable monocyclic aromatics yield from catalytic fast pyrolysis of cotton stalk via a novel ZnZrOx-ZSM-5 tandem catalysis” [Chem. Eng. J. Volume 524, 15 November 2025, 168988] - Lingxi Bai; Haonan Li; Xingxiang Wang; Xin Pu; Zhipeng Lin; Shuzhen Zhou; Jiangbing Li; Xiaogang Wang; Jie Li; Lingtao Kong; Lanli Bai; Jichang Liu (Chemical Engineering Journal, 2025)

Synergistic enhancement of CO2 hydrate growth by montmorillonite and tryptophan: Insights from piecewise kinetic modeling - Xiran Lin; Ying Teng; Mingkun Bai; Yiqi Chen; Pengfei Wang; Liangbin Xu; Senyou An; Jianbo Zhu; Jinlong Zhu; Songbai Han (Chemical Engineering Journal, 2025)

Schiff base-grafted bacterial cellulose-PCL composites: Humidity/temperature-driven hydrogen bond reconfiguration for mechanically adaptive nanofiber - Chenchen Qin; Bianjing Sun; Xinyu Chen; Du Ping; Wuxin Bai; Lin Shi; Ahsan Nazir; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2025)

Effects of Cyclic Thermal Stimulation on Granite Permeability and Mechanical Strength: Inspiration for the Enhanced Geothermal System - Yilong Yuan; Yu Wang; Tianfu Xu; Hongwu Lei; Hewen Bai; Lin Jiang; Taisen Wang; Zhiwu Xiong (Rock Mechanics and Rock Engineering, 2025)

Cortical Control of Itch Sensation by Vasoactive Intestinal Polypeptide-Expressing Interneurons in the Anterior Cingulate Cortex - Yiwen Zhang; Jiaqi Li; You Wu; Jialin Si; Yuanyuan Zhu; Meng Nian; Chen Chen; Ningcan Ma; Xiaolin Zhang; Yaoyuan Zhang; Yiting Lin; Ling Liu; et al. (Neuroscience Bulletin, 2025)

Chicago Sky Blue 6B modulates MAPK/NF-kB pathway in rat knee osteoarthritis - Yejin Zhang; Weiqing Li; Yu Bai; Hehuan Lai; Jiawei Fang; Lin Ye; Dengwei He; Zhenzhong Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Epithelial sodium channel in dendritic cells participates in high-fat-induced inflammatory responses - Xu Li; Shi-Li Zhou; Lin Bai; Chun-Lei Yu; Na Niu (Molecular Biology Reports, 2025)

Microalgae-based removal of pharmaceutically active compounds (PhACs) from wastewater: Mechanisms and applications - Ye Lin; Xue Pu; Jingyuan Xia; Xiyang Lu; Heyang Hu; Jiawei Bai; Fuyuan Guo; Shijian Ge; Shuang Qiu (Algal Research, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Numerical Analysis of Impact-Freezing and Spreading Dynamics of Supercooled Saline Droplets on Offshore Wind Turbine Blades Using the VOF–Enthalpy–Porosity Method - Guanyu Chen; Huan Xia; Xu Bai; Daolei Wu; Baolong Lin (Journal of Marine Science and Engineering, 2025)
The impact-freezing phenomenon of supercooled saline droplets on cold surfaces poses a serious threat to the operational stability and structural integrity of offshore wind turbines. Compared to freshwater droplets, numerical models for analyzing the impact-freezing behavior of saline droplets typically involve complex physical mechanisms, resulting in high computational costs. This study employs a simplified two-dimensional axisymmetric numerical model that integrates the Volume of Fluid (VOF) method with the enthalpy–porosity approach, enabling rapid analysis of the saline droplet impact-freezing process under marine environmental conditions. The model is validated by comparing the spreading factor curve of saline droplets with a salinity of 35‰ against existing experimental data. Results show that the salinity corresponding to the peak relative deviation shifts with varying impact parameters, depending on the competition between impact dynamics and solidification. Furthermore, the maximum spreading factor decreases with increasing supercooling degree and contact angle but increases with higher Weber number. These findings provide useful correction parameters for improving existing droplet motion and icing prediction models.

Detecting high-order rogue waves in two-component Bose–Einstein condensates via a convolutional neural network-based framework - Zhihao Zhang; Shunhong Lin; Tiantian Li; Xiao-Dong Bai; Jie Peng (Wave Motion, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Reduction of antibiotics and antibiotic resistance genes in simulated-sunlight-supported counter-diffusion bacteria-Algae biofilms: Interface properties and functional gene responses - Han Zhang; Jiao Yin; Haotian Jiang; Weichen Zeng; Yufei Cheng; Jiaxuan Yang; Dachao Lin; Langming Bai; Heng Liang (Water Research, 2025)

Electrostatic spinning technology coupled with traditional pollution control processes: A review - Hanrun Lv; Xuechen Li; Mengjiao Wang; Ruyu Bai; Hongjin Li; Junlang Lao; Mengda Du; Jiaqi Shi; Hanfei Gao; Baorong Duan; Qingjian Zhang; Lin Liu; et al. (Science of The Total Environment, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Integrated single-reactor system merging biological phosphate removal, semi-nitritation, anammox and in-situ sludge fermentation (PR-SNA-SF) to treat actual domestic wastewater - Zhiwei Fan; Ziqi Zhao; Zhuyan Dong; Ling Bai; Haoyu Lin; Meijie Zhou; Hao Wang; Fuping Li; Wei Zeng (Process Safety and Environmental Protection, 2025)

Boundary adaptive and dynamic neural network dual layer path planning algorithm for polar multi-mission area under-ice feature scanning - Lin Zhou; Zhongchao Deng; Nan Zhou; Guiqiang Bai; Hongde Qin; Zhongben Zhu (Ocean Engineering, 2025)

Radical reaction-wastewater fuel cell with Fe-modified graphene hydrogel particle electrodes - Tingsheng Zhou; Panyu Jiang; Jinhua Li; Yan Zhang; Lei Li; Beibei Li; Chaoyue Xie; Jia Lin; Jing Bai; Mingce Long; Baoxue Zhou (Journal of Hazardous Materials, 2025)

High-resolution assessment reveals underestimated human health risks of ammonia emissions in China's pig production - Yue Zhao; Le Yu; Zhenrong Du; Zhaohai Bai; Ling Liu; Tao Liu; Lin Ma (Journal of Cleaner Production, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Qualitative and quantitative detection of Zn2+ in food: design, synthesis and characterization of a near-infrared probe with large Stokes shift - Shizhen Wang; Xin Wang; Wenhui Xue; Yi Huo; Mengyu Chen; Cuibing Bai; Qixiang Song; Chenxu Liu; Lin Zhang; Changqing Qu; Hui Miao; Rui Qiao (Food Chemistry, 2025)

Extended thermophilic phase promotes fungal-bacterial collaboration to facilitate humification in batch-fed composting - Haichao Wang; Xiaowei Zheng; Dong Guo; Dan Liu; Bing Bai; Yan Shao; Bing Yue; Huan Zhang; Shuye Lin (Environmental Research, 2025)

Integrated analysis of lncRNA-miRNA-mRNA regulatory network revealing molecular mechanisms of immune response and ion transport in Eriocheir sinensis under alkalinity stress - Jun-Lei Ma; Yu-Lin Bai; Yi-Dong Liang; Ting Zhang; Lei You; Dong-Po Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Hierarchically plasticized intrinsically stretchable fully π-conjugated polymer films for flexible and large-area printed RGB light-emitting diodes - Ningning Yu; Zhiqiang Zhuo; Yingying Zheng; Mingjian Ni; Wenyu Chen; Jiabin Liu; Dunliang He; Jingyao Ma; Man Xu; Xiang An; Lubing Bai; Jinyi Lin; et al. (Chemical Engineering Journal, 2025)

Single-stage reverse-structured solar evaporator from two to three dimensional by transparent hydrogel - Shen Du; Bing-Lin Bai; Ya-Ling He; Mingyun Dai; Jia-Cheng Wan (Chemical Engineering Journal, 2025)

Boosting sustainable monocyclic aromatics yield from catalytic fast pyrolysis of cotton stalk via a novel ZnZrOx-ZSM-5 tandem catalysis - Lingxi Bai; Haonan Li; Xingxiang Wang; Xin Pu; Zhipeng Lin; Shuzhen Zhou; Jiangbing Li; Xiaogang Wang; Jie Li; Lingtao Kong; Lanli Bai; Jichang Liu (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

Divergent responses of ecological functions to long-term herbivore exclusion in the Tibetan mountainous grasslands - Shuaihao Bai; Jingxue Zhao; Guangpeng Qu; Lihua Tian; Gao-Lin Wu (Agriculture, Ecosystems & Environment, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Retrieving soil heavy metal concentrations using hyperspectral remote sensing images based on three-band indices at a coal mine in China - Haorui Bai; Bin Guo; Lin Pei; Bo Zhang; Pingping Luo; Tengyue Guo; Min Wu; Xiaohan Ma (Advances in Space Research, 2025)

Upscale Convective Growth Prevailing on the Monsoon Coast with Changing Atmospheric Conditions and Local Forcings - Sijia Zhang; Guixing Chen; Lanqiang Bai; Lin Su (Advances in Atmospheric Sciences, 2025)

Biofilm response in potential difference-enhanced membrane-aerated biofilm systems for accelerated antibiotic removal and ARG mitigation - Han Zhang; Haotian Jiang; Jiao Yin; Tianyi Wang; Weichen Zeng; Dachao Lin; Boyan Xu; Langming Bai; Heng Liang; How Yong Ng (Water Research, 2025)

Phase transitions in retrofitting urban drainage systems: a computational framework for adaptation-sustainability trade-offs - Qiyu Dong; Lin Shu; Shunwen Bai; Yiming Xu; Nanqi Ren (Water Research, 2025)

GM-CSF-adjuvanted Newcastle disease virus-vectored bivalent vaccine elicits enhanced dual immunity against Newcastle disease and infectious bursal disease in chickens - Qing Wu; Jinmiao Liu; Weiyue Cao; Jiaxin Li; Huimin Li; Yuhan Jin; Zhitong Li; Xinyu Li; Wenying Sun; Lin Bai; Xinyuan Shen; Xiaochen Guo; et al. (Veterinary Immunology and Immunopathology, 2025)

Exploring efficient chlorine evolution reaction with Ru-RuO2/C@TiC electrodes in antibiotic degradation under saline conditions - Zhehan Tu; Zhuwu Jiang; Weixin Lin; Jiahan Yang; Fengying Zhang; Xue Bai; Jyunhong Shen; Hongyu Zhang; Huabin Liu (Process Safety and Environmental Protection, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Drift trajectory prediction and search area optimization of marine targets based on hybrid optimization algorithm - Nan Zhou; Zhongben Zhu; Hongde Qin; Lin Zhou; Yifan Xue; Xiaokai Mu; Guiqiang Bai (Ocean Engineering, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Oxidative pyrolysis of biomass waste: Efficient production of humic substances with enhanced agricultural potential and environmental benefits - Jian Li; Wen Fu; Xiaowei Bai; Ning Mao; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Journal of Cleaner Production, 2025)

Mitigation of greenhouse gas emissions and nitrogen losses caused by migration and tourism in China's tropical island cities - Xiaoyang Shan; Zhaohai Bai; Lin Ma; Shuqing Zhao; Hongwei Zhao (Journal of Environmental Management, 2025)

Atomically dispersed iron-decorated activated carbon for boosted adsorption of oxygenated/chlorinated volatile organic compounds - Fangda Wei; Haiyan Bai; Xi Cui; Feng Wu; Zhixiong You; Lin Yue; Jinjun Li (Journal of Environmental Chemical Engineering, 2025)

The synergistic performance and mechanism of coal dust suppression contributed by Bacillus pasteurii assisted with a potent indigenous Lysinibacilus MN-5 - Gang Zhou; Yixin Xu; Wenqi Shao; Xueqiang Lv; Yongguang Lan; Xianchao Jia; Jintuo Zhu; Guochao Yan; Jianmin Bai; Lin Li (Journal of Environmental Chemical Engineering, 2025)

Optimizing KH2PO4 addition to enhance nitrogen retention in swine manure composting: Integrated mechanisms of enzyme activity, microbial community, and denitrification genes - Xiaoxia Hao; Lijia Jiang; Du Jin; Mengting Chen; Wenyi Wang; Dongmei Jiang; Lin Bai (Journal of Environmental Chemical Engineering, 2025)

Exploring the gas separation of N2/CH4 mixture on nitrogen-modified graphene - Shuang Wei; Shaobin Yang; Xu Zhang; Yingkai Xia; Lin He; Wei Dong; Ding Shen; Lailei Wu; Shulin Bai; Shuwei Tang (Journal of Environmental Chemical Engineering, 2025)

Combined impacts of chlorine and pharmaceutical discharge on river periphyton and zoobenthos - Jie Mao; Junwen Chen; Lutong Yang; Qiaojuan Wang; Hui Lin; Yaohui Bai (Journal of Environmental Sciences, 2025)

Association of air pollution exposure and habitual physical activity with risk of overall and cause-specific hospital-treated infections: a UK Biobank cohort study - Zixuan Jiang; Yahang Liu; Yifang Huang; Chen Huang; Yating Yang; Ruilang Lin; Jing Wang; Runzhi Bai; Xueying Zheng; Yongfu Yu; Guoyou Qin (Environmental Research, 2025)

Nitrate-induced microbial metabolic activation and community composition optimization enhance the anaerobic biodegradation of thiamethoxam - Jun Tu; Qiuru Chen; Ziyi Lin; Xiaotong Bai; Yiquan Qiu; Xiaohui Yi; Mingzhi Huang (Environmental Research, 2025)

A new quantitative characterization method of absolute methane adsorption isotherm in coal - Biao Hu; Zeyu Ren; Shugang Li; Xinxin He; Haifei Lin; Yang Bai; Dongjie Yan; Rongwei Luo (Chemical Engineering Journal, 2025)

Lithium bond-mediated multiple synergy enabling mechanical robustness, self-healing and ultrasensitive ion-conductive elastomers for flexible sensor - Lingli Kong; Tianwen Luo; Rufeng He; Dan Huang; Bai Huang; Lihua Fu; Baofeng Lin; Chuanhui Xu (Chemical Engineering Journal, 2025)

Tough, strongly adhesive, and highly conductive eutectogels enabled by homogeneous and stable organic–inorganic hybrid networks - Baochen Gu; Wenzhen Qin; Gaoyuan Li; Hongmin Ji; Bai Huang; Baofeng Lin; Chuanhui Xu; Yen Wei; Lihua Fu (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Simultaneous enhancement of mechanical strength and recyclability in fully bio-based epoxy vitrimers via rigid and reactive dihydromyricetin derivative - Yuan Cao; Zhi-Chao Yan; Mengni Guo; Lin Bai; Bingyue Xing; Yuanshuo Zhang; Yufu Gao; Jizhong Chen; Hongping Xiang; Tongfei Shi (Chemical Engineering Journal, 2025)

Highly integrated silk fibroin/nanohydroxyapatite hybrid composites via interface engineering for enhancing bone regeneration - Jie Li; Liu Su; Lingyu Qiu; Jie Zheng; Zhiqing Lin; Shumeng Bai (Chemical Engineering Journal, 2025)

Engineering a recombinant VP2-Based neutralizing epitope vaccine candidate against canine parvovirus: a preliminary immunogenicity assessment - Qing Wu; Yuhan Jin; Weiyue Cao; Zeheng Ren; Xinyu Li; Zhitong Li; Jiachi Han; Chunxu Shi; Rui Gao; Min Yan; Shengrui Zhu; Wenpeng Guan; et al. (Veterinary Research Communications, 2025)

Oxytocin Regulated Neuroinflammation through OTR/Mitochondria Mediated Pathway to Improve Hypoxia-Induced Brain Injury - Xiaomei Yang; Kai Li; Lin Chen; Lei Wang; Xuyang Wang; Kangping Lu; Yu Bai; Yonghao Hou; Jingchen Hou; Chao Wang; Xiaoyan Cheng; Joseph Oldam; et al. (Molecular Neurobiology, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Analysis of the damage characteristics of the Mandalay Royal Palace struck by the 2025 Mw 7.7 Myanmar earthquake - Xuchuan Lin; Xiaoxiang Yuan; Wen Bai; Aixia Dou (Earthquake Engineering and Engineering Vibration, 2025)

Joint Kinematics and Muscle Activity in Response to Prolonged Standing: Analysis of Standing and Subsequent Gait - Lin Feng; Wentao Jiang; Zhongyou Li; Taoping Bai; Jialu Zhang; Jiyang Zhang; Siqi Yang (Annals of Biomedical Engineering, 2025)

Distribution pattern of cetaceans in the northern South China Sea based on visual surveys and environmental DNA metabarcoding - Shengming Deng; Xiang Zhang; Min Liu; Bai‐An Lin; Yongcan Zhou; Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Hui Kang; Binshuai Liu; Shenglan Chen; et al. (Conservation Biology, 2025)
The South China Sea (SCS) is vital habitat and potential nursery and feeding grounds for large cetaceans, such as the sperm whale ( Physeter macrocephalus ), making understanding of the temporal and spatial patterns of cetaceans in this region essential. We examined the accuracy of environmental DNA (eDNA) in detecting cetacean species diversity and determine the spatial and temporal distribution of cetaceans in the northern SCS. We conducted 5 ship‐based visual surveys for cetaceans in 3 summers and 2 springs from 2020 to 2023 and used eDNA metabarcoding to determine the relative abundance and spatial and temporal distribution of cetaceans in offshore and abyssal areas of the northern SCS. We detected 18 cetacean species through visual observations and eDNA metabarcoding. Both methods identified 12 species in common. Cetaceans’ presence varied temporally. We detected 7 species in the springs and 17 species in the summers. Expedition route design, meteorological conditions, and sea conditions between the 2 seasons partly explained the seasonal differences. The species of Ziphiidae, Physeteridae, and Kogiidae tended to occupy regions with high bathymetric drop gradients, particularly those situated on continental slopes and seamounts. The Delphinidae were more widely distributed and relatively more abundant. Of the cetaceans successfully identified by eDNA metabarcoding, species with relatively large group sizes and that were relatively close to the sampling sites tended to be more easily detected. Our results provide new information on the relative abundance and spatial and temporal distribution of cetaceans and indicate that eDNA techniques can provide additional information and serve as a complementary tool for cetacean monitoring and conservation.

Observational Study of Local and Non-local Effects on Aerosols Vertical Distribution in the Boundary Layers - Haijiong Sun; Lin Wang; Hongrong Shi; Liang Ran; Jinqiang Zhang; Zhixuan Bai; Bai Liu; Xiaoqiong Zhen; Xuehua Fan; Hongbin Chen (Aerosol Science and Engineering, 2025)

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

SHAPAttention: A novel approach to enhance model performance and interpretability in agricultural spectral data analysis - Ting Wu; Longhui Zhu; Lei Li; Leian Liu; Weidong Bai; Li Lin; Ling Yang (Computers and Electronics in Agriculture, 2025)

A greenhouse strawberry seedbed image stitching method based on seedbed plane alignment and efficient point-line matching - Jiong Lin; Xue Bai; Mengen Yuan; Dong Wang; Shuqin Yang; Jifeng Ning (Computers and Electronics in Agriculture, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Biodegradable Janus membrane for oil/water separation and unidirectional oil transport via electrospinning and plasma treatment - Hongshen Lin; Fangxia Yu; Jingxi Liang; Shenao Bai; Rongzong Cai; Pingfan Xu; Peikun Zhang; Yaofa Luo (Journal of Cleaner Production, 2025)

Biological age acceleration mediates effects of household air pollution from solid fuels on dementia risk: A prospective cohort study in China - Haisheng Wu; Zengxian Lin; Chunren Zhang; Yuxing Jiang; Liming Bai; Jiazhen Zheng; Suosu Wei; Chunxia Deng (Environmental Pollution, 2025)

Portable miRNA profiling of sepsis-associated exosomes via a novel DNA molecular lock-mediated nanobiosensor - Wei Xie; Shu Jia; Rongjun Yu; Jianjiang Xue; Shulian Bai; Chenxing Wang; Gang Tian; Qiongyuan Zhang; Xiao Gui; Lilin Wang; Silin Chen; Ke Lin; et al. (Chemical Engineering Journal, 2025)

Robust LiF/LiCl-rich SEI layer via composite electrolyte design enables long-cycling all-solid-state lithium metal batteries - Chengdeng Wang; Jun Wu; Jiamao Hao; Lin Zhong; Lu Yang; Jiashuai Wang; Zhi Wang; Xiangrui Chen; Liyuan Bai; Jinpeng Li; Yan Gao; Xiaoqin Yan; et al. (Chemical Engineering Journal, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

In-situ carbon monoxide gas vaccine synergizes ferroptosis to reprogram immunosuppressive microenvironment for enhanced cancer immunotherapy - Yunhao Bai; Guishun Feng; Xiaoyu Lin; Chenyu Ma; Guoguang Chen; Qiyue Wang; Xueming Li; Hao Ren (Chemical Engineering Journal, 2025)

Fabrication of multicolor fluorescent perovskite-polymer composites and their application in information encryption - Yihui Lei; Huiling Liang; Lin Bai; Mingyu Jin; Juan Cheng; Tingcheng Li; Daohong Zhang; Sufang Chen; Zejun Xu (Chemical Engineering Journal, 2025)

Nanozyme platform with built-in electric field and gas modulation for deep biofilm penetration and enhanced antibacterial therapy - Bingshuai Zhou; Zhifang Wang; Xiaolin Sun; Jiao Sun; Songtao Hu; Liheng Sun; Lin Xu; Xue Bai; Min Liu; Lin Wang; Biao Dong (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Metallothioneins protect against isoconazole nitrate-induced antitumor activity through the maintenance of cellular redox homeostasis in hepatocellular carcinoma - Chun-fen Mo; Ya-ruo Lei; Jun Lin; Yi Liu; Zhi-wei Zhao; Wen-jing Xiao; Wen-bai Yan; Wei-wei Zhang (Chemico-Biological Interactions, 2025)

Combined space cooling/heating and domestic hot water supply driven by data center waste heat: Complementary energy conservation, economic capacity optimization and generic analysis framework - Jun Bai; Xiaohui Wu; Xiaoyuan Chen; Zhiying Zhang; Lin Fu; Chunxiao Zhao; Ke Qing; Qiaoyu Luo; Shirong Gong; Boyang Shen (Building and Environment, 2025)

Nitrogen addition improved rhizosphere phosphorus availability and phosphorus-phytoextraction of Polygonum hydropiper through optimizing rhizosphere enzymes, microbial interactions and functions - Daihua Ye; Xiaoyu Bai; Min Xie; Yujie Li; Tao Liu; Lin Ji; Xizhou Zhang; Huagang Huang; Haiying Yu; Yu Tang; Yongdong Wang; Tingxuan Li (Plant and Soil, 2025)

Genomic Approaches to Enhance Disease Resistance in Large Yellow Croaker: Recent Progress and Future Perspectives - Zhou Jiang; Yulin Bai; Ning Li; Lin Chen; Ji Zhao; Yin Li; Tao Zhou; Peng Xu (Reviews in Aquaculture, 2025)
Large yellow croaker is an important marine aquaculture species in China, but frequent disease outbreaks have led to significant losses in the aquaculture industry. Although traditional genetic selection methods have long been applied in fish breeding, an increasing number of studies are introducing genomic selection methods into large yellow croaker breeding to target complex traits such as disease resistance. Recent advancements in genomic resources, including an updated reference genome and SNP array, have opened up new opportunities for genetic and evolutionary research on this species. This review provides an overview of the current status of the large yellow croaker aquaculture industry and the existing approaches to addressing disease challenges. It also summarizes genomic selection techniques, the genetic mechanisms underlying disease resistance traits, and potential improvements in genomic selection methods. Furthermore, we summarize future directions for large yellow croaker breeding, incorporating the application of genetic research, multi‐dimensional data integration, standardized testing protocols, and artificial intelligence for phenotypic measurement. These strategies have opened new pathways to enhance disease resistance in large yellow croaker and to promote the sustainable development of its aquaculture industry.

Integrating deep Q-networks, convolutional neural networks, and artificial potential fields for enhanced search path planning of unmanned surface vessels - Tianqi Yang; Qingjia Chi; Ning Xu; Jixin Bai; Wei Wei; Hu Chen; Hengliang Wu; Zeyuan Yao; Wei Chen; Yongshui Lin (Ocean Engineering, 2025)

A stable dual-functional monomer imprinted polymer platform for electrochemical sensitive detection of PFAS - Xingyang Cheng; Jing Tang; Yu Chen; Xue Bai; Yibo Liao; Xilian Ouyang; Yuchen Wang; Lin Tang (Journal of Hazardous Materials, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Detection of toluene at ppb levels using Au catalyst supported on Al-doped ZnO - Jiali Hong; Keyu Chen; Kaiping Yuan; Mingyue Lin; Qi Cao; Jialong Lin; XinLin Wang; Xiaoqian Bai; Tamao Ishida; Toru Murayama; Guangli Xiu (Journal of Environmental Chemical Engineering, 2025)

Narrowband deep-blue polymer light-emitting diodes: Beneficial from the individual planar-conformational chain segment in hierarchically ordered nano-domain - Bin Liu; Jiangli Cai; Yingying Zheng; Yang Xu; Jinghao Yang; Wenyu Chen; Mengyuan Li; Ningning Yu; Mingjian Ni; Lubing Bai; Chongping Song; Lili Sun; et al. (Chemical Engineering Journal, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Characterization of CmXERICO gene regulating carotenoid accumulation and morphogenesis in Citrus maxima - Haoran Zhang; Jiaxing Zheng; Nan Bai; Xiaoqin Jin; Wenbo Lin; Changchun Wang (Genetic Resources and Crop Evolution, 2025)

Peri-urban ammonia emissions in Beijing-Tianjin-Hebei decrease with restructuring of China's livestock industry - Xiangwen Fan; Haodan Wang; Wilfried Winiwarter; Zhanqing Zhao; Zhaohai Bai; Lin Ma (Agricultural Systems, 2025)

An in vitro safety evaluation model for assessing the effects of a chemical drug on the human intestinal barrier integrity using genetically modified Caco-2 cells expressing drug-metabolizing enzymes - Lin Bai; Shuko Sakimura; Yuki Niwa; Hiroyuki Mizuguchi; Shinichiro Maeda; Kenji Ikemura; Masahiro Okuda; Masuo Kondoh (Toxicology Letters, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

The simulation of the South China Sea by the variable resolution version of the global ocean general circulation model LICOM3.0 - Jiangfeng Yu; Jingwei Xie; Hailong Liu; Pengfei Lin; Zipeng Yu; Jiahui Bai (Ocean Modelling, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Novel ductile and durable engineered cementitious composite columns reinforced with steel-FRP composite bars: Axial compression behavior and design - Yulei Bai; Qipeng Ma; Shiwen Han; Lin Yang; Yufeng Zhang; Hongyu Zhang (Engineering Structures, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Chaotic climate system forecasting using an improved echo state network with sparse observations - Lin Ding; Yulong Bai; Donghai Zheng; Xiaoduo Pan; Manhong Fan; Xin Li (Science China Earth Sciences, 2025)

Synergistic effect of canine FGF-21 combined with insulin in the treatment of canine diabetes - Wenying Sun; Yaoqun Wang; Ziran Liu; Qing Wu; Xiaochen Guo; Zhitong Li; Xinyu Li; Chunxu Shi; Rui Gao; Lin Bai; Jingming Wang; Yuhan Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A study of frictional instability induced by fluid injection for the granite fracture - Bing Bai; Hang Lin; Hengtao Yang; Yan Zou (Bulletin of Engineering Geology and the Environment, 2025)

Structural analysis and numerical modeling of multi-stage tectonic deformation in the Ziliujing anticline, SW Sichuan Basin, China: Implications for deformation propagation in salt-bearing fold-and-thrust belts - Jiawei Liu; Gang Rao; Sen Bai; Xiaolin Xiong; Jinwu Zhang; Wenxiong Yang; Chao Yin; Yaqi Zhong; Pengcheng Tang; Jianhua Qiu; Lin Gao (Tectonophysics, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Enhanced adsorption of neonicotinoids by MnCl₂ and H₃PO₄ co-modified corn stover biochar: Performance and mechanism analysis - Jun Tu; Qiuru Chen; Siyu Ke; Xiaohui Yi; Yiquan Qiu; Ziyi Lin; Shuxiang Yang; Xinzhi Wang; Xiaotong Bai; Mingzhi Huang (Journal of Environmental Chemical Engineering, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Ratiometric fluorescent and smartphone-assisted dual-mode sensor for folic acid determination based on N-Nb2C QDs/CQDs - Lin Yuan; Lizhen Liu; Yunfeng Bai; Yuzhen Wang; Lu Zhao; Zhi Mi; Jun Qin; Feng Feng (Food Chemistry, 2025)

Insights into Leuconostoc-clade as starters in Chinese paocai: Shaping microbial communities for rapid, safe, and flavor-preserving fermentation - Xinyu Hu; Mengke Cheng; Meng Zhang; Biyue Yang; Rong Wang; Juan Bai; Jiayan Zhang; Wei Wei; Lin Zhu; Xiang Xiao (Food Bioscience, 2025)

Chemical constituents from Dendrobium huoshanense and their chemotaxonomic significance - Huan Liu; Hui Yang; Bai-Lin Su; Bo-Wei Li; Peng-Yu Zhuang; Xiao-Xia Wang; Hang Liu (Biochemical Systematics and Ecology, 2025)

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

Deep multivariable spatial attention CNN-based spatial grid NWP error correction for accurate one-day-ahead photovoltaic power forecast - Mingliang Bai; Ruidong Wang; Chaojing Lin; Yunxiao Chen; Fuxiang Dong; Zhihao Zhou; Xusheng Yang; Jinfu Liu; Daren Yu (Earth Science Informatics, 2025)

The control of Moho uplift over the distribution of the oil-gas-rich sag belt in the Beibu Gulf Basin - Lin Wang; Ying Chen; Wanyin Wang; Zhizhao Bai (Acta Oceanologica Sinica, 2025)

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Quantitative threshold effects identification of urban green exposure on multidimensional human health – A case study in Xiamen City, China - Yicheng Zheng; Nicholas A.S. Hamm; Tao Lin; Jue Liu; Tongyu Zhou; Xiaopeng Ren; Xinwen Bai; Hongkai Geng; Junmao Zhang; Zixu Jia; Yuan Chen (Urban Forestry & Urban Greening, 2025)

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Deriving leaf-scale chlorophyll index (CIleaf) from canopy reflectance by correcting for the canopy multiple scattering based on spectral invariant theory - Chenpeng Gu; Jing Li; Qinhuo Liu; Hu Zhang; Alfredo Huete; Hongliang Fang; Liangyun Liu; Faisal Mumtaz; Shangrong Lin; Xiaohan Wang; Yadong Dong; Jing Zhao; et al. (Remote Sensing of Environment, 2025)

Natural promising daphnane diterpenoids: An integrated review of their sources, structural classification, biological activities, and synthesis - Kang Ding; Xuege Pan; Weifeng Yin; Lin Li; Hongjin Bai; Maoli Bai; Jiekun Xu; Jun He; Weiku Zhang (Phytochemistry, 2025)

Synthesis of a novel Cu₂O/BiFeO₃@Ti₃C₂ MXene Z-scheme heterojunction for enhanced photocatalytic wastewater treatment and N₂ fixation: Mechanistic insights and optimization - Yun Bai; Haitham Osman; Haitao Lin; M.A. Diab; Amal Abdulrahman; Heba A. El-Sabban; Farruh Atamurotov; Doniyor Jumanazarov; Abdelfattah Amari (Journal of Water Process Engineering, 2025)

Electrochemical enhancement of the accumulation of photosensitive components in anoxygenic phototrophic bacteria extracellular: A new insight into the preparation of degradable microbial photosensitizer for water treatment - Ronghui He; Jian Sun; Yong Yuan; Xiaoyan Bai; Qintie Lin; Yaping Zhang; Kang Dai; Zhenbo Xu (Journal of Hazardous Materials, 2025)

Highly efficient degradation of perfluoroalkyl substances (PFAS) by a novel polytetrafluoroetylene piezocatalyst - Shan Yao; Jieying Lin; Shaoxiong He; Yang Bai; Mingge Jin; Feng Zhu; Jingyun Fang; Mengye Wang (Journal of Hazardous Materials, 2025)

H4K12 lactylation-regulated NLRP3 is involved in cigarette smoke-accelerated Alzheimer-like pathology through mTOR-regulated autophagy and activation of microglia - Hailan Wang; Haibo Xia; Jun Bai; Zhongyue Wang; Yue Wang; Jiaheng Lin; Cheng Cheng; Weiyong Chen; Jingshu Zhang; Qingbi Zhang; Qizhan Liu (Journal of Hazardous Materials, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Inter-individual variation in human microbiota drives differential impacts on the fermentability of insoluble bran by soluble β-glucans from whole barley - Songtao Fan; Yiwei Ding; Zikang Hu; Zhihong Zhang; Lin Fu; Jiayan Zhang; Ying Zhu; Juan Bai; Xiang Xiao (Food Hydrocolloids, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

Synergistic Regulation of Color Transformation by Nutrient Elements, Osmotic Regulators, and Antioxidant Enzymes in Erythrophleum fordii - Zi-Long Ouyang; Xiang-Lu Jia; Tian-dao Bai; Lin-juan Huang; Xuan Jiang; Wei-Chao Teng (Journal of Plant Growth Regulation, 2025)

Root exudates of Salix cupularis orchestrate the accumulation of soil carbon and nitrogen in the rhizosphere during the restoration of a desertified alpine meadow - Qi Li; Fei Yan; Dongming Chen; Jiqiong Zhou; Zhouwen Ma; Yanfu Bai; Xingpeng Hu; Congyu Ma; Abeer S. Aloufi; Feida Sun; Anna Gunina; Jian Zhang; et al. (Applied Soil Ecology, 2025)

Hand preferences in captive non-human primates are associated with generation and stress level - Lin Wang; Yunchao Luo; Haoyu Sun; Yiru Gu; Yu Wang; Yali Bai; Zhongqiu Li (Applied Animal Behaviour Science, 2025)

Large Ensemble Simulations of Climate Models for Climate Change Research: A Review - Pengfei Lin; Lu Yang; Bowen Zhao; Hailong Liu; Pengfei Wang; Wenrong Bai; Jing Ma; Jilin Wei; Chenyang Jin; Yuewen Ding (Advances in Atmospheric Sciences, 2025)

Effect of initial shear stress on soft clay around monopile and natural frequency of offshore wind turbine structure - Lin Guo; Ziya Xu; Yilong Sun; Zhixu Bai; Hui Li; Shengnan Yao (Soil Dynamics and Earthquake Engineering, 2025)

Deformation and non-coaxial characteristics of soft marine clay subjected to wave load in a seabed of finite thickness - Hui Li; Jianhai Zhou; Lin Guo; Zhixu Bai; Feng Chen; Yilong Sun (Ocean Engineering, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Filament-woven SF/PA gel for removing ultrafine nanoparticles and unmanageable hazardous pollutants by "all-in-one net" - Qiumei Wei; Yuancheng Zhang; Fengqiong Jiang; Lihua Fu; Bai Huang; Chuanhui Xu; Baofeng Lin (Journal of Environmental Management, 2025)

Ni-doped ZnAl-layered double hydroxides for efficient non-radical activation of peroxydisulfate: The role of surface hydroxyl groups and the Ni2+/Ni3+ cycle - Xue Bai; Cheng Shen; Qi Wang; Kuangfei Lin (Journal of Environmental Chemical Engineering, 2025)

Potential genetic markers of biofilm formation ability by Listeria monocytogenes isolated from fresh agricultural products - Jing Wang; Qingli Dong; Xiujin Chen; Bo Feng; Yang Qu; Ting Lin; Yalong Bai; Peihong Liu; Changyan Zhou; Yujuan Suo (International Journal of Food Microbiology, 2025)

FengYun-3 meteorological satellites’ microwave radiation Imagers enhance land surface temperature measurements across the diurnal cycle - Yuyang Xiong; Tianjie Zhao; Haishen Lü; Zhiqing Peng; Jingyao Zheng; Yu Bai; Panpan Yao; Peng Guo; Peilin Song; Zushuai Wei; Ronghan Xu; Shengli Wu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Oxidative pyrolysis characteristics and exothermic heat release effects of cellulose, hemicellulose, and lignin - Jian Li; Wen Fu; Xiaowei Bai; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Fuel, 2025)

Insights into potential flavor-active peptides and taste-related compounds in Longjing teas: A comparative study of ‘Longjing 43’ and ‘Qunti’ cultivars - Kangni Yan; Jiatong Wang; Mengxue Zhou; Qunhua Peng; Abdelkader Bassiony Mahmoud; Xue Bai; Susanne Baldermann; Xinbing Jiang; Shan Feng; Yan Wu; Jianyu Fu; Zhi Lin; et al. (Food Chemistry, 2025)

Anti-osteoporosis properties and regulatory impact on gut microbiota of yak bone meal in ovariectomized osteoporotic mice - Haiyun Zhou; Jia Wei; Ziheng Wang; Lin Bai; Qianyu Wang; Yumei Wei; Xiaoxia Hu; Xiaojing Tian; Fumei Zhang (Food Bioscience, 2025)

Conformational entropy modulation of the work function for the construction of efficient ohmic contacts to accelerate the catalytic conversion of lithium polysulfide - Jing-Zhou Chen; Yu-Jie Ren; Kuan-Kuan Tian; Bai-Qin Xiong; Dong-Lin Zhao (Chemical Engineering Journal, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

The Two-Component System TtrRS Regulates the Expression of the 05890–05900 Operon that Promotes the Sulfur Metabolism of Vibrio parahaemolyticus - Yameng Bai; Tianqi Liang; Jie Zhao; Yawen Lin; Qian Lu; Xiujuan Zhou; Menghua Yang; Xiaojun Zhong (Current Microbiology, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Time-series InSAR reveals new insights into land subsidence in the Yellow River Delta, China - Yi Zhang; Ziliang Si; Xu Lin; Zehua Zhang; Hongxian Chu; Chang Cao; Yanxia Liu; Haijun Huang; Bingqi Huang; Zechao Bai; Kuifeng Wang; Xinghua Zhou; et al. (Marine Georesources & Geotechnology, 2025)

PWDViTNet: A lightweight early pine wilt disease detection model based on the fusion of ViT and CNN - Zhichao Chen; Haifeng Lin; Di Bai; Jingjing Qian; Hongping Zhou; Yunya Gao (Computers and Electronics in Agriculture, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Load-bearing characteristics and optimization design for rock-socketed bored piles in sandy silty clay in coastal areas - Nan Yan; Zengming Hao; Xiaoyu Bai; Lin Cui; Jichao Yin; Chao Liu; Yamei Zhang (Soil Dynamics and Earthquake Engineering, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

Mutation in FvPAL2 leads to light red strawberry fruits and yellow-green petioles - Chong Wang; Anqi Lin; Yankong Zhou; Zheng Liu; Peng Bai; Yuxuan Zhu; Junmiao Fan; Xiaoyi Bi; Huiyun Kuang; Hongli Lian; Pengbo Xu (Plant Science, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Increased Nitrogen Application Alleviates Straighthead Disease by Reducing Dimethylarsinic Acid Accumulation and Promoting Mineral Nutrient Uptake in Rice - Qinghui Liu; Cuihua Bai; Weisheng Lu; Zhijun Zhang; Xueying Yin; Wanting Lin; Lixian Yao (Journal of Soil Science and Plant Nutrition, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Novel near-infrared fluorescent probe with large stokes shift for detection of cysteine in food sample and living cells - Min Zhou; Chunyan Liu; Yanfei Lin; Tianwen Bai; Tianqing Ye; Zhaosheng Qian; Lei Li; Longhua Guo; Haiying Liu; Jianbo Wang (Food Chemistry, 2025)

Enhanced antioxidant potential of In vitro gastrointestinal digestion products derived from abalone myofibrillar protein-glucose conjugates based on structural changes - Gengxin Hao; Yanwen Ma; A.YiJiang Akemujiang; Yanping Bai; Peng Ye; Xujian Qiu; Shuting Lin (Food Bioscience, 2025)

Comprehensive assessment of straw returning with organic fertilizer on paddy ecosystems: A study based on greenhouse gas emissions, C/N sequestration, and risk health - Keqi Zhao; Xichen Zhao; Liuqin He; Nanyi Wang; Ma Bai; Xiaobing Zhang; Ge Chen; Anwei Chen; Lin Luo; Jiachao Zhang (Environmental Research, 2025)

Nonconventional phosphorus-based tertiary amine curing agent enabling the high fire safety, outstanding tensile strength and high glass transition temperature of epoxy resin - Xue-Qi Chen; Yu-Cai Lin; Wei-Bin Bai; Yuan-Wei Yan; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

D-Histidine modulated chiral metal-organic frameworks for discriminating 3,4-Dihydroxyphenylalanine enantiomers based on a chemiluminescence quenching mode - Xinyue Gao; Ruining Bai; Jin Yang; Shuai Luo; Hongwei Yuan; Lin Wang; Zhifeng Fu (Analytica Chimica Acta, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Foodborne iron overload induces oxidative stress and causes mitochondrial damage in the liver of grass carp (Ctenopharyngodon idellus) - Xiaoman Huang; Yan Yang; Yanhan Bai; Shiyi Yang; Bing Chen; Linpeng Zhang; Lihan Liu; Junjie Tao; Chengming Tu; Li Lin; Zhendong Qin (Aquaculture, 2025)

A smartphone-based enhanced colorimetric immunoassay for the detection of Trichinella spiralis infection - Yao Yu; Lianjing Zhao; Nuo Xu; Xiaolei Liu; Lin Li; Ning Xu; Xue Bai (Veterinary Parasitology, 2025)

Migration and risk assessment of heavy metals from swine manure in an organic fertilizer - soil - ryegrass - rex rabbit system: Based on field trials - Xiaoxia Hao; Kai Liu; Li Zhu; Li Rong; Dongmei Jiang; Lin Bai (Science of The Total Environment, 2025)

Nitrogen-driven shifts in molecular composition of soil dissolved organic matter linked to rare bacterial sub-communities - Xiaochun Yuan; Quanxin Zeng; Xinyu Bai; Xiaoqing Zhang; Xiaoting Fu; Mengxiao Ren; Juyan Cui; Qiufang Zhang; Xiaoli Gao; Jiacong Zhou; Yong Zheng; Kaimiao Lin; et al. (Science of The Total Environment, 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

MaERF9 and MaERF113 transcription factors involve in chilling injury development by regulating membrane lipid metabolism of postharvest banana fruit - Lijuan Bai; Yanting Wu; Hetong Lin; Wenbing Su; Zhongqi Fan (Postharvest Biology and Technology, 2025)

Efficient removal of levofloxacin by FeCo2O4@C-REC activated peroxymonosulfate: Performance and mechanism - Bai-Hang Zhao; Bao-Yu Zhang; Bing-Lin Zhang; Jing Zhang; Chun Wang; Ye Li (Journal of Water Process Engineering, 2025)

Integrating traditional and biotechnological innovations for mitigating greenhouse gas emissions in dairy farming in China - Peixian Hao; Xiaofei Wu; Zelong Liu; Lijin Tian; Xiaohang Zhang; Xuan Wang; Zhaohai Bai; Lin Ma (Journal of Cleaner Production, 2025)

Nitrogen addition accelerates aboveground biomass sequestration in old-growth forests by stimulating ectomycorrhizal tree growth - Zhichun Yang; Zikun Mao; Wenwen Ji; Antonio Gazol; Shufang Liu; Chao Wang; Ji Ye; Fei Lin; Xugao Wang; Zhanqing Hao; Edith Bai; Zuoqiang Yuan (Journal of Environmental Management, 2025)

Exploring the multifaceted reason for deficits in soil water within different soil layers in China's drylands - Liang He; Jianbin Guo; Xuefeng Liu; Wenbin Yang; Lin Chen; Qunou Jiang; Mingyue Bai (Journal of Environmental Management, 2025)

A novel machine learning approach for reservoir temperature prediction - Haoxin Shi; Yanjun Zhang; Yuxiang Cheng; Jixiang Guo; Jianqiao Zheng; Xin Zhang; Yude Lei; Yongjie Ma; Lin Bai (Geothermics, 2025)

Experimental study on characteristics and mechanism of hydrogen production from aluminium–water reaction for carbon-free power generation - Xinyue Gao; Chang’an Wang; Yujie Hou; Lin Zhao; Wengang Bai; Defu Che (Fuel, 2025)

Application of machine vision in food computing: A review - Zhiyao Zhao; Rong Wang; Minghao Liu; Lin Bai; Ying Sun (Food Chemistry, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

A flame-retardant and weakly solvated gel electrolyte for high-performance and high-safety Ah class sodium-ion batteries - Lixing Xue; Hongyan Pan; Yuejun Wang; Zhengyi Wang; Xuhui Wang; Qian Lin; Kuo Zhang; Xiangnan Bu; Maohui Bai; Bo Hong (Chemical Engineering Journal, 2025)

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

Enhancing crop production in the Haihe Basin while addressing challenges related to water quantity and quality - Gang Wang; Jing Yang; Xia Liu; Haodi Zhang; Xiangbo Xu; Jiafa Luo; Zhaohai Bai; Lin Ma (Science of The Total Environment, 2024)

Unveiling the formation and influence mechanisms of PCDD/F memory effect in wet scrubbers: Fundamental research and field verification - Ying Peng; Yunfeng Ma; Xiaoqing Lin; Jisheng Long; Li Bai; Hailiang Du; Yang Cao; Jiajun Wang; Lu Liu; Xiaodong Li (Science of The Total Environment, 2024)

New Ediacaran tubular fossils from southern Shaanxi, China - Qiao-Kun Dai; Hong Hua; Jin-Zhou Luo; Xiao Min; Xiao-Qiang Pan; Zi-Wei Liu; Song Zhang; Lin Bai (Palaeoworld, 2024)

Occurrence characteristics and ecological impact of agricultural soil microplastics in the Qinghai Tibetan Plateau, China - Xiaoyun Bai; Noman Shoaib; Zhifen Pan; Kaiwen Pan; Xiaoming Sun; Xiaogang Wu; Lin Zhang (Journal of Hazardous Materials, 2024)

Cd indirectly affects the structure and function of plankton ecosystems by affecting trophic interactions at environmental concentrations - Zhendong Jiang; Xuhao Wan; Xue Bai; Zhongzhi Chen; Lin Zhu; Jianfeng Feng (Journal of Hazardous Materials, 2024)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

Unveiling the susceptibility mechanism of Microcystis to consecutive sub-lethal oxidative stress—Enhancing oxidation technology for cyanobacterial bloom control - Fang Bai; Jie Li; Tianli Li; Jun Sha; Jin Liu; Lin Li; Guofei Dai; Yunlu Jia; Lirong Song (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Polycyclic aromatic hydrocarbons emissions from biomass-fueled boilers in China - Chunlin Zhang; Meixue Yang; Jiangyong Li; Hao Wang; Lin Song; Liran Shen; Li Bai; Yujun Lin; Jun Liu; Boguang Wang (Journal of Hazardous Materials, 2024)

Optimizing nitrogen management for pollution control in Lake Baiyangdian following water replenishment - Peixian Hao; Jing Yang; Xia Liu; Maryna Strokal; Dianneke van Wijk; Zhaohai Bai; Lin Ma (Journal of Environmental Management, 2024)

Magnetic sludge-derived biochar for Cu (II) removal: RSM-based preparation and BP artificial neural network adsorption modeling - Yunfan Bai; Danyang Lei; Lin Li; Chuhua Qi; Yongxing Lv; Qilin Guo; Zhixian He; Shuangli Chen; Sijing Zhang (Journal of Environmental Chemical Engineering, 2024)

Optical characteristic of dissolved organic matter polar fractions by spectrum technologies and the relationship with indirect photodegradation of ofloxacin - Shukai Liu; Zhengguo Cui; Ying Bai; Dongsheng Ding; Qingjing Hu; Yuqiu Wei; Lin Zhu; Keming Qu; Rongguo Su (Journal of Environmental Chemical Engineering, 2024)

Differential mineral diagenetic evolution of lacustrine shale: Implications for CO2 storage - Liu Wang; Bo Liu; Longhui Bai; Lin Ma; Zhichao Yu; Qiuli Huo; Kevin G. Taylor (International Journal of Coal Geology, 2024)

Characterization of newly isolated Bacillus cereus D3 Co-producing α-amylase and protease and its application in food raw materials - Shuang Wang; Hua Bai; Zongmin Wang; Lin Peng; Ling Li; Hongbo Yan; Lanlan Zhu; Yanbo Wang; Jinyan Shao; Jizhou Liu (Food Bioscience, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Deep dehumidification characteristics of a silica gel coated cross-flow heat exchanger with a circulating blowing loop - Lin Liu; Hongyu Huang; Jun Li; Yu Bai; Zhaohong He; Lisheng Deng; Tieyu Gao; Mitsuhiro Kubota; Noriyuki Kobayashi (Energy and Buildings, 2024)

Compromise boosted high capacitive energy storage in lead-free (Bi0.5Na0.5)TiO3 −based relaxor ferroelectrics by phase structure modulation and defect engineering - Jiachen Xi; Long Lin; Wangfeng Bai; Shiting Wu; Peng Zheng; Peng Li; Jiwei Zhai (Chemical Engineering Journal, 2024)

Improving global weather and ocean wave forecast with large artificial intelligence models - Fenghua Ling; Lin Ouyang; Boufeniza Redouane Larbi; Jing-Jia Luo; Tao Han; Xiaohui Zhong; Lei Bai (Science China Earth Sciences, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Impacts of February climate conditions in the Gobi Desert on March dust activities in the northern East Asia - Lin Liu; Dongping Bai; Zhili Wang; Deying Wang; Huizheng Che; Yadong Lei; Ke Gui; Junting Zhong; Xiaoye Zhang (Science of The Total Environment, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

A real time data-driven dynamic glasius bionic neural network path planning algorithm for polar under-ice feature scanning by “Xinghai 1000” AUV - Lin Zhou; Zhongchao Deng; Guiqiang Bai; Nan Zhou; Hongde Qin; Zhongben Zhu; Yifan Xue; Xiaokai Mu; Xiaojian Cao (Ocean Engineering, 2024)

Investigation of factors affecting oil-water separation efficiency in micro-bubble micro-cyclonic flow air flotation - Wei Wang; Xiang Zhao; Xu Bai; Xue-liang Ma; Wei Lin; Jiu-yang Yu (Journal of Water Process Engineering, 2024)

Biochar affects soil properties over 1 m depth in an alkaline soil of north China Plain - Xiongxiong Bai; Jiao Tang; Qingwei Lin (Journal of Environmental Management, 2024)

Dissection of molecular mechanisms of liver injury induced by microcystin-leucine arginine via single-cell RNA-sequencing - Yunmeng Bai; Yali Song; Miaoran Li; Jinhuan Ou; Hong Hu; Nan Xu; Min Cao; Siyu Wang; Lin Chen; Guangqing Cheng; Zhijie Li; Gang Liu; et al. (Journal of Environmental Sciences, 2024)

One-stone-for-two-birds strategy to achieve effective electrochemical nitrate reduction towards ammonia synthesis with Ru doped cobalt tungstate - Xue Bai; Keyu Zhou; Lan Lin; Huiying Li; Qianggen Li; Guangyin Fan (Fuel, 2024)

Passive protection of chicken egg yolk immunoglobulin (IgY) against Streptococcus agalactiae infection in Nile tilapia (Oreochromis niloticus) - Linpeng Zhang; Yucong Hong; Kaihui Sun; Shuyan Zhao; Yanhan Bai; Shiyi Yang; Junjie Tao; Fei Shi; Fanbin Zhan; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Transgenerational and parental impacts of acrylamide exposure on Caenorhabditis elegans: Physiological, behavioral, and genetic mechanisms - Yajuan Chen; Zihan Liu; Weijia Yuan; Shan Lu; Weidong Bai; Qinlu Lin; Jianfei Mu; Jianqiang Wang; Haifang Wang; Ying Liang (Environmental Pollution, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Spray-on electronic tattoos with MXene and liquid metal nanocomposites - Lin Wang; Yong Lin; Cheng Yang; Qian Wang; Ting Fang; Chong Bai; Jianhui Wang; Desheng Kong (Chemical Engineering Journal, 2024)

Modifying functional groups of straw-based hydrogel provide soil N2O mitigation potential by complete denitrification - Weishuai Wang; Xuan Wang; Shuping Qin; Jiao Yuan; Jiafa Luo; Zhaohai Bai; Lin Ma (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Mechanism of unactivated peroxymonosulfate-induced degradation of amino-G acid: Kinetics and transformation pathway - Xue Bai; Kuangfei Lin; Qi Wang (Chemical Engineering Journal, 2024)

Correction to: Identification and map‑based cloning of an EMS‑induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Can similarity of autistic traits promote neural synchronization? - Shuyuan Feng; Lin Ding; Mingliang Wang; Jianing Zhang; Yuqing Yuan; Peng Zhang; Xuejun Bai (Experimental Brain Research, 2024)

Dynamic changes of soil metabolite profiles during Moso bamboo (Phyllostachys edulis (Carrière) J. Houz.) expansion into adjacent planted forests in a typical karst river basin, South China - Lin Ai; Yuxin Dai; Feng Chen; Jiaojiao Zhang; Jiangming Ma; Kundong Bai; Zhangqi Yang; Hao Yang (Applied Soil Ecology, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Optimizing straw and nitrogen fertilizer resources for low-carbon sustainable agriculture - Bai-Jian Lin; Jia Cheng; Hong-Xuan Duan; Wen-Xuan Liu; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

Hotspot–subduction zone interactions and their resource effects at ∼120 Ma on the central Tibetan Plateau - Jia-Wei Bai; Jian-Jun Fan; Ye Zhan; Bo-Chuan Zhang; Si-Lin Sun; Yu-Jie Hao (Lithos, 2024)

Novel Cu(I)/Cu(II) oxide nanowires electrode with efficient cyclic catalytic performance for electroreduction of nitrate wastewater to ammonia - Ye Du; Wenjie Liu; Changhui Zhou; Chaoyue Xie; Zhinan Dai; Jie Wang; Jia Lin; Jinhua Li; Hong Zhu; Jing Bai; Baoxue Zhou (Journal of Environmental Chemical Engineering, 2024)

Magnetic bio-based Fe3O4@urushiol-Fe polymeric nanoparticles for efficient photothermal sterilization - Weibin Bai; Xu Zhang; Xinghang Chen; Pengcheng Li; Jinxin Huang; Jiani Chen; Shijing Zheng; Xiaoyan Li; Yucai Lin; Rongkun Jian (Journal of Environmental Chemical Engineering, 2024)

A novel “on-off-on” electrochemiluminescence aptasensor based on resonance energy transfer as signal amplification strategy for ultrasensitive detection of sulfadiazine in different samples - Youqi Long; Junjie Liu; Yijie Wu; Lin Fu; Lijuan Bai (Food Chemistry, 2024)

Ordered 2D/3D CoNi-LDH/FeSe electrode for efficient and durable seawater oxidation - Yue Shi; Jiejie Bai; Aixin Ma; Zhitao Zou; Yanru Liu; Haifeng Lin; Dehong Chen; Ruiyong Zhang; Jianping Lai; Lei Wang (Chemical Engineering Journal, 2024)

A dual-action Rhein-peptide hydrogel synergistically inhibits inflammation and matrix degradation for therapeutic mitigation of abdominal aortic aneurysm - Mingliang Wang; Yaling Li; Yizhou Bai; Zien Lin; Shenghui Bi; Yunxiang Long; Yanbin Cai; Xiaowu Wang (Chemical Engineering Journal, 2024)

Flexible, wearable triboelectric rubber with tunable surface charge density enabled by regulation of surface functional group density and permittivity - Junjie Lu; Zehua He; Zihao Lin; Xianwei Deng; Bai Huang; Baofeng Lin; Lihua Fu; Chuanhui Xu (Chemical Engineering Journal, 2024)

A clinical-radiomics nomogram based on spectral CT multi-parameter images for preoperative prediction of lymph node metastasis in colorectal cancer - Qian Li; Rui Hong; Ping Zhang; Liting Hou; Hailun Bao; Lin Bai; Jian Zhao (Clinical & Experimental Metastasis, 2024)

Global research trends in Rhizodeposition-mediated soil carbon cycle: A bibliometric analysis - Dongming Chen; Fei Yan; Xuemei Fang; Jiqiong Zhou; Xingpeng Hu; Xiaoming Ma; Xin Zheng; Rui Yin; Feida Sun; Yanfu Bai; Zhouwen Ma; Yakov Kuzyakov; et al. (Applied Soil Ecology, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Transcriptome analysis reveals the rapid defense responses in a disease-resistant brown seaweed against a bacterial pathogen - Yingrui Zhuang; Tao Liu; Qin Lin; Yan Bai; Mingyu Ma; Mengxin Wang; Qianyu Liu; Suhelen Egan; Gaoge Wang (Aquaculture, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Sensitive and rapid detection of three foodborne pathogens in meat by recombinase polymerase amplification with lateral flow dipstick (RPA-LFD) - Wenxia Bai; Jie Chen; Dong Chen; Yike Zhu; Kairui Hu; Xiaoyu Lin; Junlin Chen; Dafeng Song (International Journal of Food Microbiology, 2024)

Research on high-carbon ether-based oxygen additives: Catalytic transformation of 2-methylfuran and furfural to ethers via CuMgAlOx catalysts - Xiangrui Lin; Xiaowei Bai; Wenqi Zhao; Zhenghua Dai; YunPeng Zhao; Jian Li (Fuel, 2024)

SHM data compression and reconstruction based on IGWO-OMP algorithm - Longguan Zhang; Junfeng Jia; Yulei Bai; Xiuli Du; Ping Lin; He Guo (Engineering Structures, 2024)

Insight into response mechanism of aerobic granular sludge to combined nanoparticle stress: Nitrogen removal, microbial community and heavy metal resistance genes - Yu-Qi Li; Bai-Hang Zhao; Yu-Qing Zhang; Hai-Shan Yang; Bing-Lin Zhang (Chemical Engineering Journal, 2024)

Bavachinin, a main compound of Psoraleae Fructus, facilitates GSDMD-mediated pyroptosis and causes hepatotoxicity in mice - Wei Shi; Yuan Gao; Huijie Yang; Hui Li; Tingting Liu; Jia Zhao; Ziying Wei; Li lin; Yujiao Huang; Yuming Guo; Anlong Xu; Zhaofang Bai; et al. (Chemico-Biological Interactions, 2024)

Identification of stripe rust resistance gene YrBDT in Chinese landrace wheat Baidatou using BSE-seq and BSR-seq - Jingchun Wu; Yukun Cheng; Weihao Hao; Bin Bai; Luping Fu; Yan Ren; Yuanfeng Hao; Fengju Wang; Ruiming Lin; Hongqi Si; Chuanxi Ma; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

Role of O-GlcNAcylation in Central Nervous System Development and Injuries: A Systematic Review - Li Zhang; Wanshan Bai; Yaonan Peng; Yixing Lin; Mi Tian (Molecular Neurobiology, 2024)

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

Uncertainty of canopy interception modeling in high-altitude Picea crassifolia forests of Semi-arid regions - Junjun Yang; Zhibin He; Pengfei Lin; Jun Du; Dong Shi; Meng Bai (Agricultural and Forest Meteorology, 2024)

Harmful Cyanobacterial Bloom Control with Hydrogen Peroxide: Mechanism, Affecting Factors, Development, and Prospects - Yue Chen; Fakhar Zaman; Yunlu Jia; Yingzi Huang; Tianli Li; Fang Bai; Lin Li; Lirong Song; Jie Li (Current Pollution Reports, 2024)

Bacterial evolution in Biofiltration of drinking water treatment plant: Different response of phage and plasmid to varied water sources - Peijun Zhang; Yuhan Wang; Huan Lin; Jinsong Liang; Juntao Wang; Yaohui Bai; Jiuhui Qu; Aijie Wang (Water Research, 2024)

Comparative study on the damping-gradient spectral elements for the elastic wave absorbing - Taoping Bai; Songhan Zhang; Lin Liang (Soil Dynamics and Earthquake Engineering, 2024)

Water scarcity footprint and water saving potential for large-scale green hydrogen generation: Evidence from coal-to-hydrogen substitution in China - Lifeng Du; Yanmei Yang; Xue Bai; Shuo Xu; Ling Lin; Min Liu (Science of The Total Environment, 2024)

Ursolic acid suppresses fatty liver-associated hepatocellular carcinoma by regulating lipid metabolism - Mingyan Dong; Qi Cui; Yunong Li; Yujing Li; Qiuyu Chang; Ruixue Bai; Minjiie Wei; Lin zhao; Qili Chen (Food Bioscience, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Tailoring metal-support interactions via spatial confinement of Ni/CeO2 interfaces on h-BN for efficient CO2 methanation - Shuangxi Lin; Longchen Gong; Ning Zhao; Huibo Zhao; Feigang Zhao; Yang Bai; Zhenhua Li; Wen Liu (Chemical Engineering Journal, 2024)

Online monitoring lignocellulosic particles by focus beam reflectance measurement for efficient bioprocessing - Ji-Wen Yao; Xiao-Yan Huang; Yen-Han Lin; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2024)

Evaluating CMIP6 models in simulating the North Pacific decadal variability in sea surface salinity - Jian Chen; Hailong Liu; Pengfei Lin; Wenrong Bai; Chengzu Bai; Lu Wang (Science China Earth Sciences, 2024)

Inhibition of microelement accumulation and disorder of saccharide and amino acid metabolism explain rice grain empty under dimethylarsinic acid stress - Qinghui Liu; Zhijun Zhang; Cuihua Bai; Xueying Yin; Wanting Lin; Lixian Yao (Plant Cell Reports, 2024)

Stefin B alleviates the gouty arthritis in mice by inducing the M2 polarization of macrophages - Shishui Lin; Xu Hu; Yang Li; Jiyue Huang; Rui Zhang; Xinxin Bai; Shaohuang Weng; Min Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The present study aims to explore the therapeutic effect of Stefin B on gouty arthritis (GA) and the polarization of macrophages in mice. Stefin B-overexpressed or knockdown M0 macrophages were constructed. The GA model was established in mice by injecting 25 mg/mL MSU, followed by a single injecting of Stefin B-overexpressing adenovirus vector (GA model + Stefin B OE) or an empty vector (GA model + Stefin B OE NC). Stefin B was found lowly expressed in M1 macrophages. CD206 was markedly upregulated and IL-10 release was signally increased in Stefin B-overexpressed macrophages. In gouty arthritis mice, marked redness and swelling were observed in the ankle joint. Dramatical infiltration of inflammatory cells was observed in the GA model and GA model + Stefin B OE NC groups, which was suppressed in the Stefin B OE group. Increased proportion of F4/80 + CD86 + cells observed in GA mice was markedly repressed by Stefin B overexpression, accompanied by the declined level of Caspase-1 and IL-17. Collectively, Stefin B alleviated the GA in mice by inducing the M2 polarization of macrophages.

Deubiquitinating enzyme OTUD4 stabilizes RBM47 to induce ATF3 transcription: a novel mechanism underlying the restrained malignant properties of ccRCC cells - Ziyao Li; Ye Tian; Huafeng Zong; Xuelei Wang; Dongyang Li; Adili Keranmu; Shiyong Xin; Bowen Ye; Rong Bai; Weihua Chen; Guosheng Yang; Lin Ye; et al. (Apoptosis, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Disinfectant-induced ammonia oxidation disruption in microbial N-cycling process in aquatic ecosystem after the COVID-19 outbreak - Lutong Yang; Ping Han; Qiaojuan Wang; Hui Lin; Donglin Wang; Jie Mao; Weixiao Qi; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Effect of vegetable oils on the thermal gel properties of PSE-like chicken breast meat protein isolate-based emulsion gels - Ke Li; Lin-Meng Wang; Bing-Bing Cui; Bo Chen; Dian-Bo Zhao; Yan-Hong Bai (Food Chemistry, 2024)

Effects of feeding chicken egg yolk antibodies on intestinal cell apoptosis, oxidative stress and microbial flora of tilapia (Oreochromis niloticus) infected with Streptococcus agalactiae - Linpeng Zhang; Yanhan Bai; Junjie Tao; Shiyi Yang; Chengming Tu; Lihan Liu; Xiaoman Huang; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Impacts of mixed ferrous sulfate-biochar additives on humification and bacterial community during electric field-assisted aerobic composting - Kunhong Jiang; Dongmei Jiang; Shuo Li; Zhenzhen Guo; Liangbin Zhao; Jie Wang; Xiaoxia Hao; Lin Bai; Shixiu Qiu; Bo Kang (Bioresource Technology, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Meta-analysis addressing the potential of antibiotic resistance gene elimination through aerobic composting - Hongge Wang; Xuan Wang; Lu Zhang; Xinyuan Zhang; Yubo Cao; Ran Xiao; Zhaohai Bai; Lin Ma (Waste Management, 2024)

Has benchmarking improved the performance of the Australian electricity distribution utilities? A meta-frontier model - Lin-Lan Bu; Maria Kopsakangas-Savolainen; Bai-Chen Xie; Hong-Zhou Li; Yi-Meng Liu; Shao-Peng Yin (Utilities Policy, 2024)

Optimizing the rate of straw returning to balance trade-offs between carbon emission budget and rice yield in China - Ruo-Chen Li; Yu-Gang Tian; Fan Wang; Yuan-Feng Sun; Bai-Jian Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang; Zhi-Yu Xu (Sustainable Production and Consumption, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Late Jurassic–Early Cretaceous Rebangco ophiolite, Tibet: Constraints on the Meso-Tethys Ocean tectonic evolution - Jia-Wei Bai; Jian-Jun Fan; Yu-Jie Hao; Bo-Chuan Zhang; Si-Lin Sun (Journal of Asian Earth Sciences, 2024)

Exploration of the immune response of grass carp (Ctenopharyngodon idellus) erythrocytes during bacterial infection - Shiyi Yang; Yanhan Bai; Junjie Tao; Chengming Tu; Bing Chen; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

FerrylHb induces inflammation and cell death in grass carp (Ctenopharyngodon idella) hepatocytes - Junjie Tao; Lihan Liu; Xiaoman Huang; Chenming Tu; Linpeng Zhang; Shiyi Yang; Yanhan Bai; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Co-exposure to fluoride and sulfur dioxide induces abnormal enamel mineralization in rats via the FGF9-mediated MAPK signaling pathway - Ying Lv; Jin Yao; Yang Wang; Guohui Bai; Changhu Lin; Chenglong Tu (Environmental Research, 2024)

Stabilizing high-Ni cathodes with gradient surface Ti-enrichment - Wenchang Zhu; Xiaotian Zhu; Jizhen Qi; Junyi Yao; Yanbin Shen; Guanjian Cheng; Xue Huang; Shiqi Yang; Hao Zhang; Chao-Lung Chiang; Yan-Gu Lin; Jianming Bai; et al. (Chemical Engineering Journal, 2024)

Modified lignin can achieve mitigation of ammonia and greenhouse gas emissions simultaneously in composting - Weishuai Wang; Xuan Wang; Xinyuan Zhang; Zhaohai Bai; Lin Ma (Bioresource Technology, 2024)

Identification and map-based cloning of an EMS-induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Cadmium Treatment Affected the Growth and Physiology of Larix Olgensis Seedlings, the Chemical Properties of Haplic Cambisols and Toxicity Threshold Determination - Haixia Wang; Kunshu Yao; Jiaxin Ru; Jiagui Guo; Ding Liu; Yunlong Liu; LingYun Bai; Jixiang Lin; Chengbo Gu; Jinfeng Song (Journal of Soil Science and Plant Nutrition, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Responses of different agricultural structures to nitrogen loss and agricultural green development in Northwest China - Jiaxin Liu; Xiangwen Fan; Xiuyuan Li; Yupin Zheng; Yan Li; Caixian Cui; Zhaohai Bai; Lin Ma; Bingnian Zhai; Ziyan Li (Agriculture, Ecosystems & Environment, 2024)

Alkaloids isolated from the endophytic fungus Fusarium concentricum - Xi-Lin Zhang; Bing-Guo Lu; Jian Bai; Ning Li (Natural Product Research, 2024)

Waste treats waste: Facile fabrication of porous adsorbents from recycled PET and sodium alginate for efficient dye removal - Jing Yu; Lan Bai; Zijun Feng; Lin Chen; Shimei Xu; Yuzhong Wang (Chemosphere, 2024)

A retrospective analysis of heavy metals and multi elements in the Yangtze River Basin: Distribution characteristics, migration tendencies and ecological risk assessment - Quanzhen Liu; Xiong Xu; Lihua Lin; Lu Bai; Mengru Yang; Weiqing Wang; Xinghua Wu; Donghong Wang (Water Research, 2024)

Particulate matter deposition and its impact on tuberculosis severity: A cross-sectional study in Taipei - Firdian Makrufardi; Hsiao-Chi Chuang; Chi-Won Suk; Yuan-Chien Lin; Desy Rusmawatiningtyas; Indah Kartika Murni; Eggi Arguni; Kian Fan Chung; Kuan-Jen Bai (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Investigation of bioactive compounds and their correlation with the antioxidant capacity in different functional vinegars - Hua Bai; Shuang Wang; Zong-Min Wang; Lan-Lan Zhu; Hong-Bo Yan; Yan-Bo Wang; Xin-Yu Wang; Lin Peng; Ji-Zhou Liu (Food Research International, 2024)

Dual modification engineering enabled efficient perovskite solar cells with high open-voltage of 1.233 V - Zhongqi Liu; Long Shao; Fancong Zeng; Shuhang Bian; Bin Liu; Yuqi Wang; Yanjie Wu; Yongzhi Shao; Huan Zhang; Yuhong Zhang; Zhicong Shi; Xue Bai; et al. (Chemical Engineering Journal, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

Glucose-Responsive hydrogel optimizing Fenton reaction to eradicate multidrug-resistant bacteria for infected diabetic wound healing - Xingchen Li; Zifan Meng; Lin Guan; Annan Liu; Lei Li; Maja D. Nešić; Bai Yang; Wenrui Qu; Quan Lin (Chemical Engineering Journal, 2024)

Blockade of aryl hydrocarbon receptor restricts omeprazole-induced chronic kidney disease - Nan Sun; Yimeng Zhang; Lin Ding; Xin An; Fang Bai; Yanjiang Yang; Kuipeng Yu; Jiahui Fan; Lei Liu; Huimin Yang; Xiangdong Yang (Journal of Molecular Medicine, 2024)

Identification of rock mass discontinuity from 3D point clouds using improved fuzzy C-means and convolutional neural network - Guangyin Lu; Bei Cao; Xudong Zhu; Zishan Lin; Dongxin Bai; Chuanyi Tao; Yani Li (Bulletin of Engineering Geology and the Environment, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Immune response mechanisms underlying bacterial infection in Aquarana catesbeiana erythrocytes - Yanhan Bai; Lingqin Lu; Junjie Tao; Chengming Tu; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Aquaculture, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Spatially selective defect management of CsPbI3 films for high-performance carbon-based inorganic perovskite solar cells - Hailiang Wang; Qixian Zhang; Zedong Lin; Huicong Liu; Xiaozhen Wei; Yongfa Song; Chunyu Lv; Weiping Li; Liqun Zhu; Kexiang Wang; Zhenhua Cui; Lan Wang; et al. (Science Bulletin, 2024)

Optimizing phosphorus fertilizer use to enhance water quality, food security and social equality - Zhaohai Bai; Ling Liu; Carolien Kroeze; Maryna Strokal; Xinping Chen; Zengwei Yuan; Lin Ma (Resources, Conservation and Recycling, 2024)

A new silicified microfossil assemblage from the Ediacaran Dengying Formation in South Shaanxi, China - Qiaokun Dai; Hong Hua; Jinzhou Luo; Xiao Min; Ziwei Liu; Song Zhang; Meng Gong; Lin Bai (Precambrian Research, 2024)

Photochemical behaviors of sludge extracellular polymeric substances from bio-treated effluents towards antibiotic degradation: Distinguish the main photosensitive active component and its environmental implication - Xuexian Zhong; Jian Sun; Yong Yuan; Yaping Zhang; Xiaoyan Bai; Qintie Lin; Kang Dai; Zhenbo Xu (Journal of Hazardous Materials, 2024)

Development of an electrochemical separation-Rhodopseudomonas palustris electrolysis cell-coupled system for resourceful treatment of mature leachate landfill - Xiaoyan Bai; Yulang Huang; Jian Sun; Chunhua Feng; Yong Yuan; Qintie Lin; Kang Dai; Pingping Zhang (Journal of Environmental Management, 2024)

Emergence of tet(X4)-positive Enterobacterales in retail eggs and the widespread of IncFIA(HI1)-HI1A-HI1B(R27) plasmids carrying tet(X4) - Chao Yue; Yuman Bai; Tong Li; Haotian Deng; Litao Lu; Wannan Lin; Xiaoxiao Cui; Luchao Lv; Guolong Gao; Jian-Hua Liu; Yi-Yun Liu (International Journal of Food Microbiology, 2024)

A novel alginate-embedded magnetic biochar-anoxygenic photosynthetic bacteria composite microspheres for multipollutant removal: Mechanisms of photo-bioelectrochemical enhancement and excellent reusability performance - Ronghui He; Jian Sun; Xiaoyan Bai; Qintie Lin; Yong Yuan; Yaping Zhang; Kang Dai; Zhenbo Xu (Environmental Research, 2024)

Ascertaining sensitive exposure biomarkers of various metal(loid)s to embryo implantation - Mengyuan Ren; Tianxiang Wu; Shuo Yang; Ning Gao; Changxin Lan; Han Zhang; Weinan Lin; Shu Su; Lailai Yan; Lili Zhuang; Qun Lu; Jia Xu; et al. (Environmental Pollution, 2024)

Using the nexus approach to realise sustainable food systems - Jianjie Zhang; Lin Ma; Zhaohai Bai; Wenqi Ma (Current Opinion in Environmental Sustainability, 2024)

High-Performance low-k Poly(dicyclopentadiene)-POSS nanocomposites achieved by frontal polymerization - Dai-Lin Zhou; Jian Wang; Hongwei Bai; Di Han; Qiang Fu (Chemical Engineering Journal, 2024)

Efficient Separation of Uranium in Solution by ZnFe2O4 Doped with ZrO2: Adsorption Behaviors and Mechanism Study - Lin Peng; Houzhen Bai; Lishan Rong; Jinxiang Liu; Guohua Wang; Jinsong Wang; Han Xian (Water, Air, & Soil Pollution, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Bisphenol A Regulates the TNFR1 Pathway and Excessive ROS Mediated by miR-26a-5p/ADAM17 Axis to Aggravate Selenium Deficiency-Induced Necroptosis in Broiler Veins - Xue Fan; Yixuan Wang; Jintao Zhang; Hongjin Lin; Zhikun Bai; Shu Li (Biological Trace Element Research, 2024)

An in silico scheme for optimizing the enzymatic acquisition of natural biologically active peptides based on machine learning and virtual digestion - Like Lin; Cong Li; Tianlong Zhang; Chaoshuang Xia; Qiuhong Bai; Lihua Jin; Yehua Shen (Analytica Chimica Acta, 2024)

In-situ synthesis of ZIF-8 on magnetic pineapple leaf biochar as an efficient and reusable adsorbent for methylene blue removal from wastewater - Xiaoxiao Ma; Yutong Li; Yile Du; Shuangli Chen; Yunfan Bai; Lin Li; Chuhua Qi; Pingping Wu; Sijing Zhang (Environmental Science and Pollution Research, 2024)

FireViTNet: A hybrid model integrating ViT and CNNs for forest fire segmentation - Guodong Wang; Di Bai; Haifeng Lin; Hongping Zhou; Jingjing Qian (Computers and Electronics in Agriculture, 2024)

New discovery of extremely high adsorption of environmental DNA on cuttlefish bone pyrolysis derivative via large pore structure and carbon film - Lin Shi; Di Zhang; Mingyi Yang; Fangfang Li; Jinfeng Zhao; Zhaohui He; Yangwei Bai (Waste Management, 2024)

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Expressing a human RNA demethylase as an assister improves gene-editing efficiency in plants - Mengyan Bai; Wenxin Lin; Chunyan Peng; Peizhe Song; Huaqin Kuang; Jieni Lin; Jieping Zhang; Jiyao Wang; Bo Chen; Huarong Li; Fanjiang Kong; Guifang Jia; et al. (Molecular Plant, 2024)

Digitalizing river aquatic ecosystems - Yaohui Bai; Hui Lin; Chenchen Wang; Qiaojuan Wang; Jiuhui Qu (Journal of Environmental Sciences, 2024)

Precipitation and plant functional composition mediate desert canopy nutrient responses to water and nitrogen addition - Weiwei She; Yong Zhou; Wentao Luo; Yuxuan Bai; Wei Feng; Zongrui Lai; Yangui Qiao; Liang Liu; Wenjin Zhang; Lin Miao; Chun Miao; Shugao Qin; et al. (Plant and Soil, 2024)

Moderate input of nanoscale zero-valent iron accelerated soil polychlorinated biphenyls dissipation with limited inhibition on arbuscular mycorrhizal fungal diversity - Shuo Wen; Dongnian Sun; Hua Qin; Jingwei Wang; Xiangui Lin; Jianfeng Bai; Junli Hu (Journal of Soils and Sediments, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

The Earth Summit Mission-2022: Successful ozone soundings contribute to source identification in the north Mt. Qomolangma region - Jinqiang Zhang; Chunxiang Ye; Yuejian Xuan; Zhixuan Bai; Weili Lin; Dan Li; Lingkun Ran; Baofeng Jiao; Yaoming Ma; Weiqiang Ma; Nan Yao; Yunshu Zeng; et al. (Journal of Environmental Sciences, 2024)

Influence of inertinite on coal physicochemical thermal transformation properties and liquefaction behaviors - Wenchao Qian; Chunyang Yan; Xiaoyin Mu; Jiahao Chen; Lulu Cui; Hualin Lin; Sheng Han; Zongqing Bai (Fuel, 2024)

Nitrite self-degradation process in radish paocai under the synergistic regulation of prokaryotic microorganisms - Xinyu Hu; Wei Wei; Jiayan Zhang; Songtao Fan; Yufeng He; Juan Bai; Ying Zhu; Yansheng Zhao; Lin Zhu; Xiang Xiao (Food Bioscience, 2024)

The inactivation of Shigella flexneri by synergistic effect of ultrasound combined with basil essential oil nanoemulsion and application in cabbage cleaning - Lei Duan; Tongyu Jiang; Yuanjian Zhou; Xin Bai; Yutang Wang; Xin Lü; Xiaodong Xia; Lin Lin; Chao Shi (Food Control, 2024)

The infection of Aeromonas hydrophila activated Multiple programmed cell death pathways in red blood cells of Clarias fuscus - Junjie Tao; Chengming Tu; Zizheng Xu; Yanhan Bai; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Engineered nanomaterials display a variable interaction with anoxygenic photoelectrogenic biofilm for pharmaceutical pollutants degradation - Ronghui He; Xubin Zhang; Jian Sun; Xiaoyan Bai; Qintie Lin; Yong Yuan; Yaping Zhang; Kang Dai; Zhenbo Xu (Chemical Engineering Journal, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Novel perspective on the regulation of food allergy by probiotic: The potential of its structural components - Huming Shao; Fangfang Min; Meijia Huang; Zhongliang Wang; Tianliang Bai; Min Lin; Xin Li; Hongbing Chen (Critical Reviews in Food Science and Nutrition, 2024)

Identifying ARG-carrying bacteriophages in a lake replenished by reclaimed water using deep learning techniques - Donglin Wang; Jiayu Shang; Hui Lin; Jinsong Liang; Chenchen Wang; Yanni Sun; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

The application of static digestive models simulating the digestion system of infants and young children for the development of accessory food: Current status and future perspective - Jing Lin; Caiyu Liu; Ru Bai; Jinzhu Pang; Junan Li; Chi Zhang; Xinqi Liu; He Li; Sumei Hu (Trends in Food Science & Technology, 2024)

Status of phthalate esters pollution in facility agriculture across China: Spatial distribution, risk assessment, and remediation measures - Xiaoyun Bai; Kaiwen Pan; Noman Shoaib; Xiaoming Sun; Xiaogang Wu; Lin Zhang (Science of The Total Environment, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Impacts of subsidy for export of pig to domestic market on the spatial distribution of pig production and related nitrogen losses in China - Yue Zhao; Zhaohai Bai; Ling Liu; Xiangwen Fan; Lin Ma (Science of The Total Environment, 2024)

Otolith microchemistry reveals diverse habitat uses and migratory patterns of two Coilia species (Engraulidae) in the Min River Estuary, southern China - Qing Xu; Qing-qiang Ren; Tao Jiang; Bai-an Lin; Xiao-bin Jiang; Jian Yang; Min Liu (Marine Environmental Research, 2024)

Complementary waste heat utilization from data center to ecological farm: A technical, economic and environmental perspective - Xiaoyuan Chen; Jun Bai; Lin Fu; Yi Lei; Donghui Zhang; Zhiying Zhang; Qiaoyu Luo; Shirong Gong; Boyang Shen (Journal of Cleaner Production, 2024)

Preparation of refined phosphoric acid with recycling of raffinate acid by the extraction of metal impurities - Xiaokang Gong; Chao Hu; Yanru Jin; Haifeng Liu; Jiahui Bai; Lixue Niu; Lin Yang (Journal of Cleaner Production, 2024)

Arbuscular mycorrhizae mitigate negative impacts of soil biodiversity loss on grassland productivity - Jiqiong Zhou; Yingying Su; Xiangjun Li; Yakov Kuzyakov; Pengsen Wang; Jinchao Gong; Xuxu Li; Lin Liu; Xinquan Zhang; Congyu Ma; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2024)

A novel multiplex PCR based method for the detection of Listeria monocytogenes clonal complex 8 - Jianheng Cheng; Shi Wu; Qinghua Ye; Qihui Gu; Ying Zhang; Qinglei Ye; Ruoqin Lin; Xinwen Liang; Zihao Liu; Jianling Bai; Jumei Zhang; Moutong Chen; et al. (International Journal of Food Microbiology, 2024)

A study on identifying synergistic prevention and control regions for PM2.5 and O3 and exploring their spatiotemporal dynamic in China - Haojie Wu; Bin Guo; Tengyue Guo; Lin Pei; Peiqing Jing; Yan Wang; Xuying Ma; Haorui Bai; Zheng Wang; Tingting Xie; Miaoyi Chen (Environmental Pollution, 2024)

Highly ion-conducting, robust and environmentally stable poly(vinyl alcohol) eutectic gels designed by natural polyelectrolytes for flexible wearable sensors and supercapacitors - Bai Huang; Wanwan Liu; Yufan Lan; Yuhui Huang; Lihua Fu; Baofeng Lin; Chuanhui Xu (Chemical Engineering Journal, 2024)

A ENR-based conductive film integrating electricity-triggered self-healing, damage detection and high sensitivity for flexible sensors - Lingli Kong; Yunpeng Yang; Zihao Lin; Bai Huang; Lusheng Liao; Yueqiong Wang; Chuanhui Xu (Chemical Engineering Journal, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Sequential starch modification by branching enzyme and 4-α-glucanotransferase improves retention of curcumin in starch-alginate beads - Yu Wang; Chengfang Pang; Hossein Mohammad-Beigi; Xiaoxiao Li; Yazhen Wu; Marie Karen Tracy Hong Lin; Yuxiang Bai; Marie Sofie Møller; Birte Svensson (Carbohydrate Polymers, 2024)

Downregulation of the expression of subgenomic chromosome A7 genes promotes plant height in resynthesized allopolyploid Brassica napus - Kanglu Zhao; Jing Dong; Junxiong Xu; Yanbo Bai; Yuhe Yin; Chunshen Long; Lei Wu; Tuanrong Lin; Longqiu Fan; Yufeng Wang; Patrick P. Edger; Zhiyong Xiong (Theoretical and Applied Genetics, 2024)

An insight into the health beneficial of probiotics dairy products: a critical review - JinTao He; Wen Li; Jing Deng; QinLu Lin; Jie Bai; Lin Zhang; Yong Fang (Critical Reviews in Food Science and Nutrition, 2023)

An Adversarial Single-Domain Generalization Network for Fault Diagnosis of Wind Turbine Gearboxes - Xinran Wang; Chenyong Wang; Hanlin Liu; Cunyou Zhang; Zhenqiang Fu; Lin Ding; Chenzhao Bai; Hongpeng Zhang; Yi Wei (Journal of Marine Science and Engineering, 2023)
In deep learning-based fault diagnosis of the wind turbine gearbox, a commonly faced challenge is the domain shift caused by differing operational conditions. Traditional domain adaptation methods aim to learn transferable features from the source domain and apply them to the target data. However, such methods still require access to target domain data during the training process, which limits their applicability in real-time fault diagnosis. To address this issue, we introduce an adversarial single-domain generalization network (ASDGN). It relies solely on data from a single length of data acquisition in wind turbine fault diagnosis. This novel approach introduces a more flexible and efficient solution to the field of real-time fault diagnosis for wind turbines.

Estimating leaf age of maize seedlings using UAV-based RGB and multispectral images - Yi Bai; Liangsheng Shi; Yuanyuan Zha; Shuaibing Liu; Chenwei Nie; Honggen Xu; Hongye Yang; Mingchao Shao; Xun Yu; Minghan Cheng; Yadong Liu; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Straw incorporation induces rice straighthead disease in As-contaminated paddy soil - Qinghui Liu; Cuihua Bai; Zhijun Zhang; Xueying Yin; Wanting Lin; Yinghui Huang; Lixian Yao (Science of The Total Environment, 2023)

Urban nitrogen budgets: Evaluating and comparing the path of nitrogen through cities for improved management - Katrin Kaltenegger; Zhaohai Bai; Ulrike Dragosits; Xiangwen Fan; Andrzej Greinert; Samuel Guéret; Monika Suchowska-Kisielewicz; Wilfried Winiwarter; Lin Zhang; Feng Zhou (Science of The Total Environment, 2023)

Magnitude and direction of green-up date in response to drought depend on background climate over Mongolian grassland - Wenrui Bai; Huanjiong Wang; Shaozhi Lin (Science of The Total Environment, 2023)

Structurally diverse terpenoids from Elephantopus scaber L. and their acetylcholinesterase inhibitory activities - Jia-Yi Li; Shu-Hui Dong; Xin Zhang; Zi-Jian Liu; Jin-Le Hao; Bin Lin; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Selective and efficient production of 1,5-pentanediol from tetrahydrofurfuryl alcohol using Ni-La(OH)3 catalysts - Wenqi Zhao; Xiaowei Bai; Xiangrui Lin; Yalkunjan Tur sun; Mei Zhong; Zhenghua Dai; Jian Li (Fuel, 2023)

The improvement of sodium dodecyl sulfate on the electrospinning of gelatin O/W emulsions for production of core-shell nanofibers - Jinming Dai; Mei Bai; Changzhu Li; Haiying Cui; Lin Lin (Food Hydrocolloids, 2023)

The inhibition effect and mechanism of litsea cubeba essential oil on the hemolytic activity of listeriolysin O - Mei Bai; Jinming Dai; Wei Hu; Changzhu Li; Haiying Cui; Lin Lin (Food Bioscience, 2023)

A general characterization of integrating and querying heterogeneous fuzzy spatiotemporal XML data - Lin Zhu; Jiahui Wang; Luyi Bai (Earth Science Informatics, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Flood risk assessment of check dams in the Wangmaogou watershed on the Loess Plateau of China - Ze-chao Gao; Peng Shi; Zhan-bin Li; Peng Li; Lu-lu Bai; Yi Jia; Lin Cui (Journal of Mountain Science, 2023)

Pembrolizumab for the treatment of progressive multifocal leukoencephalopathy in China - Siyuan Fan; Mange Liu; Lin Bai; Sixian Chen; Bo Hou; Nan Lin; Jing Yuan; Chenhui Mao; Jingwen Niu; Haitao Ren; Yanhuan Zhao; Zaiqiang Zhang; et al. (Journal of NeuroVirology, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Spatial-temporal clogging development in leachate collection systems of landfills: Insight into chemical and biological clogging characteristics - Qian Wang; Qianming Miao; Ke Huang; Yeqi Lin; Tong Wang; Xinyue Bai; Qiyong Xu (Waste Management, 2023)

Effect of national COVID-19 control measures on water quality in China using an improved dual difference-in-differences method - Jian Zhao; Qingqing Liu; Jing Bai; Haixia Liu; Lin Ding (Science of The Total Environment, 2023)

Circumstellar material ejected violently by a massive star immediately before its death - Jujia Zhang; Han Lin; Xiaofeng Wang; Zeyi Zhao; Liping Li; Jialian Liu; Shengyu Yan; Danfeng Xiang; Huijuan Wang; Jinming Bai (Science Bulletin, 2023)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Sources of nitrogen in reservoirs of the Haihe basin (China) 2012–2017 - Jing Yang; Xia Liu; Maryna Strokal; Carolien Kroeze; Peixian Hao; Zhaohai Bai; Lin Ma (Journal of Environmental Management, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The roles of lipoxygenases and autoxidation during mackerel (Scomberomorus niphonius) dry-cured processing - Qiaoyu Liu; Menglin Lei; Jianjun Lin; Wenhong Zhao; Xiaofang Zeng; Weidong Bai (Food Research International, 2023)

Environmental-friendly biomass-based Janus ink/urushiol modified cotton fabric for efficient solar-driven interfacial evaporation - Weibin Bai; Xu Zhang; Ying Chen; Zhiping Lian; Shijing Zheng; Xinghang Chen; Yucai Lin; Rongkun Jian (Chemical Engineering Journal, 2023)

Study on the removal of iron (II) and manganese (II) in acidic mine drainage by red mud: Performance and mechanism - Ang Liu; Yingchen Bai; Chao Wang; Xianglong Lin; Fei Guo (Environmental Science and Pollution Research, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

A novel variable power microwave (VPM) drying technology for lowering energy consumption and improving the in vitro protein digestibility of black solider fly larvae - Xiaofei Wu; Wenyu Zhao; Xuan Wang; Zhaohai Bai; Lin Ma (Innovative Food Science & Emerging Technologies, 2023)

Comparative studies of fermented coffee fruits post-treatments on chemical and sensory properties of roasted beans in Yunnan, China - Yanbing Wang; Xiaoyuan Wang; Guilin Hu; Zhirun Zhang; Abdulbaset Al-Romaima; Xuehui Bai; Jinhong Li; Lin Zhou; Zhongrong Li; Minghua Qiu (Food Chemistry, 2023)

Performance enhancement of proton exchange membrane fuel cells with bio-inspired gear-shaped flow channels - Yuzhi Ke; Baotong Zhang; Wei Yuan; Yafeng Bai; Yonghao Zhao; Zi'ang Liu; Zhenhe Lin; Xinze Li; Yangang Wang; Yong Tang (Chemical Engineering Journal, 2023)

Photothermal-assisted for ultrafast response acetone sensing with ZIF-90/GO coated microfiber long period gratings - Yan Huang; Wenfu Lin; Ziruo Zhang; Zhenru Li; Tiansheng Huang; Jie Li; Li-Peng Sun; Bai-Ou Guan (Chemical Engineering Journal, 2023)

Upland river planform morphodynamics and associated riverbank erosion: Insights from channel migration of the upper Yarlung Tsangpo river - Zhipeng Lin; Zhongpeng Han; Waqas Ul Hussan; Yalige Bai; Chengshan Wang (CATENA, 2023)

SAPHO syndrome after COVID-19 vaccination complicated with thyroid function abnormalities: a case report and literature review - Jia-Ying Lin; Bing-Xue Bai (Immunologic Research, 2023)

Plant selection and ecological microhabitat drive the shrub-associated microbiome selection in revegetated shrub ecosystems - Zongrui Lai; Yanfei Sun; Yang Yu; Zhen Liu; Yuxuan Bai; Yangui Qiao; Lin Miao; Weiwei She; Shugao Qin; Wei Feng (Applied Soil Ecology, 2023)

An innovative biomass-driven energy systems for green energy and freshwater production with less CO2 emission: Environmental and technical approaches - Yun Bai; Haitao Lin; Azher M. Abed; Mohamed Fayed; Ibrahim Mahariq; Bashir Salah; Waqas Saleem; Ahmed Deifalla (Chemosphere, 2023)

Polyphenolic glycosides with unusual four-membered ring possessing anti-Parkinson's disease potential from black wolfberry - Yi-Kao Hu; Xiao-Lin Bai; Guang-Yu Shi; Yong-Mei Zhang; Xun Liao (Phytochemistry, 2023)

Potential inhibitors of microglial activation from the roots of Wikstroemia lichiangensis W. W. Sm - Zisong Bai; Yingjie Wang; Qingqi Meng; Libin Xu; Gang Chen; Di Zhou; Bin Lin; Yue Hou; Ning Li (Phytochemistry, 2023)

Antibacterial and antibiofilm performance of low-frequency ultrasound against Escherichia coli O157:H7 and its application in fresh produce - Mei Bai; Jinming Dai; Changzhu Li; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2023)

Curcumin delivery using tetrahedral framework nucleic acids enhances bone regeneration in osteoporotic rats - Long Bai; Maogeng Feng; Qiumei Li; Yuxuan Zhao; Geru Zhang; Zhengwen Cai; Jingang Xiao; Yunfeng Lin (Chemical Engineering Journal, 2023)

Nutrient and manure management to improve water quality in urbanizing Baiyangdian - Jing Yang; Maryna Strokal; Carolien Kroeze; Zhaohai Bai; Lin Ma (Nutrient Cycling in Agroecosystems, 2023)

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

Transcriptomic analysis the mechanisms of anti-osteoporosis of desert-living Cistanche herb in ovariectomized rats of postmenopausal osteoporosis - Shuo Tian; Lin Guo; Yagang Song; Jinxin Miao; Mengfan Peng; Xiaoyan Fang; Ming Bai; Mingsan Miao (Functional & Integrative Genomics, 2023)

Quantifying effect of maize tassels on LAI estimation based on multispectral imagery and machine learning methods - Mingchao Shao; Chenwei Nie; Aijun Zhang; Liangsheng Shi; Yuanyuan Zha; Honggen Xu; Hongye Yang; Xun Yu; Yi Bai; Shuaibing Liu; Minghan Cheng; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

The regulation mechanism of hematopoiesis during ischemic and hemolytic anemia in grass carp(Ctenopharyngodon idella) - Lixiang Wei; Yanhan Bai; Rishen Liang; Junyan Lin; Minxuan Yang; Ying Tang; Hong Chen; Minshan Yao; Yao Huang; Li Lin; Zhendong Qin (Aquaculture, 2023)

Dual-targeting lanthanide-ICG-MOF nanoplatform for cancer Theranostics: NIR II luminescence imaging guided sentinel lymph nodes surgical navigation - Bi Lin; Ruiyi Dai; Zhenghao Liu; Wenjing Li; Jingwen Bai; Guojun Zhang; Ruichan Lv (Journal of Photochemistry and Photobiology B: Biology, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Study on extract-pyrolysis cascading utilization characteristics of typical biomass using imidazolium-based ionic liquids - Tiantian Jiao; Shaojie Lin; Guangming Bai; Chuhan Ren; Yaqing Zhang; Xiangping Li; Huawei Zhang; Peng Liang (Fuel, 2023)

Strategic tillage is a promising alternative to conventional and no-tillage: Evidence from a 12-year field trial in a double-cropped rice system - Xing Wang; Cong He; Bai-Jian Lin; Xin Zhao; Ran Zhang; Ling-Tao Zhong; Xiao-Ping Xiao; Hai-Lin Zhang (European Journal of Agronomy, 2023)

Population structure and reproductive dynamics of the ridged swimming crab Charybdis natator in the southern Taiwan Strait of China: significant changes within 25 years - Bai-an Lin; Yan Jiang; Min Liu (Frontiers in Marine Science, 2023)
The ridged swimming crab Charybdis natator (Portunidae) is a commercially important crustacean species in China. The purpose of this study is to compare its population structure and reproductive pattern within the same fishing area (the southern Taiwan Strait) from two datasets over 25 years; one from 1994−1996 (the early years of the C. natator fishery) and the other from 2019. The overall sex ratio (male:female) changed from a male bias (1:0.76, p < 0.01) in 1994−1996 to a female bias (1:1.38, p < 0.01) in 2019. Male body sizes (carapace width, CW) were significantly larger than those of females in both datasets ( p < 0.05). The average CW and body weight (BW) of males and females in 2019 were significantly smaller ( p < 0.01) and lighter ( p < 0.01) than those in 1994−1996. The maximum body size and the proportion of large-sized individuals (CW > 10 cm) decreased dramatically over 25 years. One spawning peak season was identified from each dataset, i.e., March−August 1994−1996 and February−April 2019, revealing a 1-month shift. The minimum body sizes for female maturation (carrying eggs) were 6.9 cm CW in 1994−1996 and 6.1 cm CW in 2019, an 11.6% reduction over 25 years. For the first time, the CW at 50% female maturation, the relationship between female absolute fecundity and CW, and egg diameters were obtained from the 2019 dataset, which can be applied in the future comparisons. Recent studies have revealed a consistent spawning peak in February–April for several commercially important crabs in the southern Taiwan Strait. These findings should be considered in crab fishery management. Furthermore, both fishery- and environment-associated factors influencing crustacean population structure and reproductive dynamics merit further investigation.

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Benzo(a)pyrene regulates chaperone-mediated autophagy via heat shock protein 90 - Min Su; Shuhong Zhou; Jun Li; Nan Lin; Tao Chi; Mengdi Zhang; Xiaoli Lv; Yuxia Hu; Tuya Bai; Fuhou Chang (Toxicology Letters, 2023)

Corrigendum to “Context-dependency of tree species diversity, trait composition and stand structural attributes regulate temperate forest multifunctionality” [Sci. Total Environ., 757 (2021), 143724] - Anvar Sanaei; Arshad Ali; Zuoqiang Yuan; Shufang Liu; Fei Lin; Shuai Fang; Ji Ye; Zhanqing Hao; Michel Loreau; Edith Bai; Xugao Wang (Science of The Total Environment, 2023)

Regulation of inflammatory macrophages by oral mineralized metal-organic framework nanoparticles for the synergistic treatment of ulcerative colitis and liver injury - Chenghu Wu; Ning Lu; Lina Peng; Minghao Lin; Yongheng Bai; Mingqin Lu; Junjie Deng; Jilong Wang (Chemical Engineering Journal, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

Management‐induced changes in soil organic carbon and related crop yield dynamics in China's cropland - Bai‐Jian Lin; Ruo‐Chen Li; Ke‐Chun Liu; Olatunde Pelumi Oladele; Zhi‐Yu Xu; Rattan Lal; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2023)
Enhancing soil organic carbon (SOC) sequestration and food supply are vital for human survival when facing climate change. Site‐specific best management practices (BMPs) are being promoted for adoption globally as solutions. However, how SOC and crop yield are related to each other in responding to BMPs remains unknown. Here, path analysis based on meta‐analysis and machine learning was conducted to identify the effects and potential mechanisms of how the relationship between SOC and crop yield responds to site‐specific BMPs in China. The results showed that BMPs could significantly enhance SOC and maintain or increase crop yield. The maximum benefits in SOC (30.6%) and crop yield (79.8%) occurred in mineral fertilizer combined with organic inputs (MOF). Specifically, the optimal SOC and crop yield would be achieved when the areas were arid, soil pH was ≥7.3, initial SOC content was ≤10 g kg −1 , duration was >10 years, and the nitrogen (N) input level was 100–200 kg ha −1 . Further analysis revealed that the original SOC level and crop yield change showed an inverted V‐shaped structure. The association between the changes in SOC and crop yield might be linked to the positive role of the nutrient‐mediated effect. The results generally suggested that improving the SOC can strongly support better crop performance. Limitations in increasing crop yield still exist due to low original SOC level, and in regions where the excessive N inputs, inappropriate tillage or organic input is inadequate and could be diminished by optimizing BMPs in harmony with site‐specific conditions.

Effect of lignocellulose/montmorillonite immobilized Bacillus sp. on monosodium glutamate wastewater - Bai-Yun Zhao; Xiao-Kai Liu; Xi-Lin Li; Li-Juan Zhou; Li Wang (Environmental Science and Pollution Research, 2023)

A comprehensive investigation of a water and energy-based waste integrated system: Techno-eco-environmental-sustainability aspects - Yun Bai; Haitao Lin; Azher M. Abed; Ahmed Deifalla; Theyab R Alsenani; Samia Elattar (Chemosphere, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Improving sludge settling performance of secondary settling tank and simultaneously adsorbing nitrate and phosphate with surfactant modified zeolite (SMZ) ballasted flocculation - Hai Lin; Xijie Huang; Jiang Chang; Bing Li; Yongsheng Bai; Bojun Su; Luyuan Shi; Yingbo Dong (Journal of Environmental Chemical Engineering, 2023)

Nonradical oxidative degradation of amino-G acid by hydrogen peroxide induced by copper cerium plate catalyst: Electron transfer mechanisms - Xue Bai; Kai Yuan; Yunqing Lu; Yao Yang; Qi Wang; Kuangfei Lin (Journal of Environmental Chemical Engineering, 2023)

Lanthanide bimetallic MOF-based fluorescent sensor for sensitive and visual detection of sulfamerazine and malachite - Xiaoyue Yue; Long Fu; Yan Li; Sheng Xu; Xin Lin; Yanhong Bai (Food Chemistry, 2023)

Antibacterial properties of citral against Staphylococcus aureus: From membrane damage to metabolic inhibition - Jinming Dai; Mei Bai; Changzhu Li; Wai San Cheang; Haiying Cui; Lin Lin (Food Bioscience, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

A life course approach to asthma and wheezing among young children caused by ozone: A prospective birth cohort in northern China - Shuoxin Bai; Liangliang Cui; Shuang Du; Xiaodong Zhao; Shaoqian Lin; Xiwei Yang; Jiatao Zhang; Yuxiu Liang; Zhiping Wang (Environmental Research, 2023)

Integrated physiological and metabolomic analysis reveals new insights into toxicity pathways of paraquat to Microcystis aeruginosa - Fang Bai; Guangbin Gao; Tianli Li; Jin Liu; Lin Li; Yunlu Jia; Lirong Song (Aquatic Toxicology, 2023)

Dimethyl Itaconate Reduces Cognitive Impairment and Neuroinflammation in APPswe/PS1ΔE9 Transgenic Mouse Model of Alzheimer’s Disease - Jing Xiong; Dong-Lin Lu; Bai-Qiang Chen; Tong-Yun Liu; Zi-Xuan Wang (NeuroMolecular Medicine, 2023)

Knowledge Map and Global Trends in Root Exudates Research from 2012 to 2021: a Bibliometric Analysis - Xin Zheng; Dongming Chen; Jiqiong Zhou; Qian Huang; Xingpeng Hu; Zhuxin Deng; Xuemei Fang; Feida Sun; Junming Zhao; Xiao Ma; Congyu Ma; Xinrui Yan; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Challenges and opportunities in animal models of psoriatic arthritis - Lin-Kun Bai; Ya-Zhen Su; Zong-Di Ning; Cheng-Qiang Zhang; Li-Yun Zhang; Gai-Lian Zhang (Inflammation Research, 2023)

Al–Fe pillared bentonite−Fe3O4–CaO2 nanocomposite for efficient adsorption and degradation of trichloroethylene - Meiyun Feng; Zhiqiang Xu; Xue Bai; Kuangfei Lin; Meng Zhang (Sustainable Chemistry and Pharmacy, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Carbon-confined Ni based catalyst by auto-reduction for low-temperature dry reforming of methane - Dongyang Shen; Jie Wang; Yue Bai; Shuai Lyu; Yuhua Zhang; Jinlin Li; Lin Li; Guanghui Wang (Fuel, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Polyamide/polyethylene thin film composite (PA/PE-TFC) NF membranes prepared from reverse-phase interface polymerization (RIP) for improved Mg(II)/Li(I) separation - Qingyi Wang; Yongping Dong; Junmei Ma; Huimin Wang; Xuping Xue; Chaojie Bai; Mingjie Lin; Lingping Luo; Congjie Gao; Lixin Xue (Desalination, 2023)

Surface selenation engineering on metal cocatalysts for highly efficient photoreduction of carbon dioxide to methanol - Wenbin Chen; Shijie Wu; Liyan Xie; Yujie Wu; Yanwen Ye; Huigang Wang; Zhulei Chen; Hongjun Lin; Leihong Zhao; Song Bai (Chemical Engineering Journal, 2023)

Upcycling of nickel iron slags to hierarchical self-assembled flower-like photocatalysts for highly efficient degradation of high-concentration tetracycline - Zhen Wu; Mengye Wang; Yang Bai; Han Song; Jiaxin Lv; Xiaofeng Mo; Xiaoqin Li; Zhang Lin (Chemical Engineering Journal, 2023)

Precipitation scale effect of the TRMM satellite in Tianshan, China - Shan Ning; Hong-wu Zhou; Zheng-yong Zhang; Shi-biao Bai; Lin Liu (Journal of Mountain Science, 2023)

The linkages between stomatal physiological traits and rapid expansion of exotic mangrove species (Laguncularia racemosa) in new territories - Jiankun Bai; Yuchen Meng; Ruikun Gou; Zheng Dai; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2023)
The fast-growing exotic mangrove species ( Laguncularia racemosa ) has been widely introduced in new territories such as China to restore mangrove ecosystems. However, the invasiveness, as well as the mechanisms for the rapid expansion after the introduction are still not well studied. Here, we try to reveal possible micro-mechanisms for the fast expansion of L. racemosa , using the data on leaf stomata straits, gas-exchange parameters, stable isotope ratios, carbon-nitrogen allocation from L. racemosa and the adjacent native mangroves ( Avicennia marina, Aegiceras corniculatum, Bruguiera gymnorhiza, Kandelia obovata ) in Hainan Island, China. We found that the higher density but smaller size stoma of L. racemosa enhanced stomatal conductance and shorten the diffusion path of carbon dioxide, thereby increasing the photosynthetic rate. Moreover, the higher stomatal density of L. racemosa exerts a significant positive effect on transpiration, which thus accelerated the water transport and nutrient uptake to meet the advanced need for nutrients and water for fast-growing. The evidence from leaf δ 13 C and carbon-nitrogen allocation further proved that L. racemosa has a lower intrinsic water use efficiency but a higher rate of photosynthesis than native mangrove species. Our results suggest that stomatal morphological and physiological traits could strongly influence the growth of L. racemosa compared to the adjacent native mangroves, which provides a new perspective for the fast expansion of exotic mangrove species in China. These findings also suggest that L. racemosa has an invasive potential in native mangrove habitats, thereby the mangrove reforestation projects by introducing L. racemosa should be treated with caution.

Preliminary studies of the tardigrada communities from a polymetallic nodule area of the deep South China Sea - Xiaogu Wang; Lifen Bai; Chunsheng Wang; Bo Lu; Yujie Li; Qinyi Lin; Xinyu Huang; Paulo Fontoura (Frontiers in Marine Science, 2023)
Knowledge about marine tardigrades from the South China Sea is very scarce, with only four species from shallow waters recorded to date. The present study investigated the structure and diversity of tardigrade communities from the deep sea (1517-1725 m) at 8 stations in a polymetallic nodule area of the northern South China Sea. A total of 151 arthrotardigrades were collected belonging to 11 genera ( Angursa, Batillipes, Coronarctus, Euclavarctus, Exoclavarctus, Halechiniscus, Moebjergarctus, Raiarctus, Rhomboarctus, Tanarctus and Tholoarctus ), representing 17 species. Two Angursa species ( Angursa sp. 4 and Angursa sp. 3) were the most abundant (25.2% and 14.6%, respectively), followed by Moebjergarctus sp. (13.9%). Specimens were mostly (90.7%) distributed in the upper layer of the sandy-mud sediment (0-1 cm). The SIMPROF test showed that the composition of tardigrade communities at all stations was not significantly different. At different stations, the number of species, Shannon-Wiener diversity index and Pielou’s evenness index ranged from 4 to 10, 1.94 to 2.87, and 0.75 to 1.00, respectively. The average taxonomic distinctness (Δ+) ranged from 72.50 to 90.00, and the variation in taxonomic distinctness (Λ+) ranged from 316.67 to 1181.25. This study provides some basic information about the biodiversity of the marine tardigrade community in the South China Sea.

Dynamic damage characteristics of mudstone around hammer driven pile and evaluation of pile bearing capacity - Jichao Yin; Xiaoyu Bai; Nan Yan; Songkui Sang; Lin Cui; Junwei Liu; Mingyi Zhang (Soil Dynamics and Earthquake Engineering, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

Zirconium tungstate reinforced energetic composites with inhibited thermal expansion and reduced thermal stress - Congmei Lin; Liangfei Bai; Liyuan Wei; Ruqin Liu; Shiliang Huang; Cui Zhang; Xiaoqing Tu; Zhijian Yang; Feiyan Gong; Chengcheng Zeng; Ling Ding; Liping Pan; et al. (Chemical Engineering Journal, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Integrating Ecosystem Health and Services for Assessing Ecological Risk and its Response to Typical Land-Use Patterns in the Eco-fragile Region, North China - Yisen Wang; Zhonghua Yang; Minghui Yu; Ruyu Lin; Lei Zhu; Fengpeng Bai (Environmental Management, 2023)

Abundant culturable diazotrophs within Actinomycetia rather than rare taxa are underlying inoculants for nitrogen promotion in desert soil - Lin Miao; Yangui Qiao; Yuxuan Bai; Wei Feng; Shugao Qin; Yuqing Zhang (Applied Soil Ecology, 2023)

Maternal apparent temperature during pregnancy on the risk of offspring asthma and wheezing: effect, critical window, and modifiers - Jiatao Zhang; Shuoxin Bai; Shaoqian Lin; Liangliang Cui; Xiaodong Zhao; Shuang Du; Zhiping Wang (Environmental Science and Pollution Research, 2023)

Prognostic and functional roles of EIF4G1 in lung squamous cell carcinoma - Baoxin Bai; Lin Dong; Minghao Feng; Zhiwen Zhang; Ying Lu; Zengguang Xu; Yali Liu (Human Cell, 2023)
Eukaryotic translation initiation factor 4 gamma 1 (EIF4G1) is highly expressed in many cancers and affects their occurrence and development. However, the effect of EIF4G1 on the prognosis, biological function and the relevant mechanism in lung squamous cell carcinoma (LSCC) is unclear. Through clinical cases, Cox’s proportional hazard model and Kaplan–Meier plotter survival analysis, we find the expression levels of EIF4G1 are dependent on age and clinical stage, high expression of EIF4G1 could be used to predict the overall survival of LSCC patients. LSCC cell line NCI-H1703, NCI-H226 and SK-MES-1infected with EIF4G1 siRNA are used to detect the function of EIF4G1 with cell proliferation and tumorigenesis in vivo and vitro. The data show that EIF4G1 promotes tumor cell proliferation and the G1/S transition of cell cycle in LSCC, then the biological function of LSCC is effected by the AKT/mTOR pathway. Above all, these results have demonstrated that EIF4G1 promotes LSCC cell proliferation and may represent an indicator of prognosis in LSCC.

A metal-organic framework (MOF) and graphene oxide (GO) based peroxymonosulfate (PMS) activator applied in pollutant removal - Meiyun Qi; Ping Lin; Qiyu Shi; Huiling Bai; Huan Zhang; Weihuang Zhu (Process Safety and Environmental Protection, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Large deformation and failure analysis of the corrugated flexible composite skin for morphing wing - Tian-Wei Liu; Jiang-Bo Bai; Shao-Lin Li; Nicholas Fantuzzi (Engineering Structures, 2023)

Simultaneous dual-defect engineering as a booster for polysulfide adsorption and conversion in Li-S battery - Meixiu Qu; Yu Bai; Weiwei Yang; Lin Peng; Zhenhua Wang; Wang Sun; Kening Sun (Chemical Engineering Journal, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Effects of aerosols on the forecasting of Mei-yu frontal storms over the Yangtze–Huai River valley - Lin Liu; Huiling Yuan; Yi Deng; Jing Ren; Yongqing Bai; Chunguang Cui (Atmospheric Research, 2023)

Fumigation activity of essential oils of Cinnamomum loureirii toward red imported fire ant workers - Huanling Xing; Yingqi Hu; Liupeng Yang; Jianhao Lin; Haiyi Bai; Yanqun Li; Rezwan Tanvir; Ling Li; Mei Bai; Zhixiang Zhang; Hanhong Xu; Hong Wu (Journal of Pest Science, 2023)

The Novel Fluorescent Probe Toward Yttrium(III) and its Bioimaging - Yuxin Qin; Qian Meng; Junxiong Yao; Mengyu Chen; Yajie Dong; Dashuo Chen; Shuping He; Cuibing Bai; Lin Zhang; Biao Wei; Hui Miao; Changqing Qu; et al. (Journal of Fluorescence, 2023)

Keywords Query of uncertain spatiotemporal data based on XML - Changming Xu; Lin Zhu; Luyi Bai; Juan He (Earth Science Informatics, 2023)

Method research and effect analysis of fuel-assembly bowing on neutron-physics simulations of HPR1000 - Chenghui Wan; Lin Guo; Jiahe Bai (Annals of Nuclear Energy, 2023)

Development and application of DETECTR-based rapid detection for pathogenic Bacillus anthracis - Jianhao Xu; Xinru Bai; Xianglilan Zhang; Bing Yuan; Lei lin; Yan Guo; Yujun Cui; Jinxiong Liu; Hongyu Cui; Xiangang Ren; Jinglin Wang; Yuan Yuan (Analytica Chimica Acta, 2023)

Nitrate enhances cadmium accumulation through modulating sulfur metabolism in sweet sorghum - Jiawen Wu; Na Zhao; Pan Zhang; Lin Zhu; Yuan Lu; Xin Lei; Zhenqing Bai (Chemosphere, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Dam construction alters planktonic microbial predator‒prey communities in the urban reaches of the Yangtze River - Qiaojuan Wang; Junwen Chen; Weixiao Qi; Donglin Wang; Hui Lin; Xinghua Wu; Dianchang Wang; Yaohui Bai; Jiuhui Qu (Water Research, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

HSQC-based small molecule accurate recognition technology discovery of diverse cytotoxic sesquiterpenoids from Elephantopus tomentosus L. and structural revision of molephantins A and B - Ming Bai; Wei Xu; Xin Zhang; Qian Li; Ning-Ning Du; De-Feng Liu; Guo-Dong Yao; Bin Lin; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Experimental study on the influence of gas pressure on CH4 adsorption-desorption-seepage and deformation characteristics of coal in the whole process under triaxial stress - Haifei Lin; Pengfei Ji; Xiangguo Kong; Shugang Li; Hang Long; Tong Xiao; Bai Li (Fuel, 2023)

CH4 adsorption and diffusion characteristics in stress-loaded coal based on molecular simulation - Hai-fei Lin; Hang Long; Shu-gang Li; Yang Bai; Tong Xiao; Ao-li Qin (Fuel, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Bacillus subtilis reduces antibiotic resistance genes of animal sludge in vermicomposting by improving heat stress tolerance of Eisenia foetida and bacterial community adjustment - Xiaoxia Hao; Wenjin Zhang; Liangbin Zhao; Linyuan Shen; Li Zhu; Bo Zeng; Dongmei Jiang; Lin Bai (Environmental Research, 2023)

Multi-objective optimization of winter irrigation for cotton fields in salinized freeze-thaw areas - Ling Li; Hongguang Liu; Ping Gong; En Lin; Zhentao Bai; Pengfei Li; Chunxia Wang; Jing Li (European Journal of Agronomy, 2023)

Recent advances in targeted manipulation of the gut microbiome by prebiotics: from taxonomic composition to metabolic function - Songtao Fan; Zhihong Zhang; Yansheng Zhao; Maria Daglia; Jiayan Zhang; Ying Zhu; Juan Bai; Lin Zhu; Xiang Xiao (Current Opinion in Food Science, 2023)

A multifunctional and long-term waterborne anti-corrosion coating with excellent ‘hexagonal warrior’ properties - Luchao Pei; Dan Lin; Sicheng Yuan; Renjie Lu; Ziheng Bai; Yue Sun; Yanji Zhu; Yuanxu Jiang; Jiajun Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Sodium Fluoride and Sulfur Dioxide Derivatives Induce TGF-β1-Mediated NBCe1 Downregulation Causing Acid–Base Disorder of LS8 Cells - Ying Lv; Wentai Wang; Lili Yao; Jiaojiao He; Guohui Bai; Changhu Lin; Chenglong Tu (Biological Trace Element Research, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Comparative transcriptome analysis of early sexual differentiation in the male and female gonads of common carp (Cyprinus carpio) - Mei Wang; Lin Chen; Zhixiong Zhou; Junzhu Xiao; Baohua Chen; Peihong Huang; Chengyu Li; Yaguo Xue; Ruoting Liu; Yulin Bai; Mengzhen Yan; Shuimu Hu; et al. (Aquaculture, 2023)

Gut as the target tissue of mercury and the extraintestinal effects - Xue Tian; Xiaoying Lin; Jiating Zhao; Liwei Cui; Yuxi Gao; Yong-Liang Yu; Bai Li; Yu-Feng Li (Toxicology, 2023)

Study on damage constitutive relationship of mudstone affected by dynamic pile driving - Yamei Zhang; Jichao Yin; Xiaoyu Bai; Lin Cui; Songkui Sang; Junwei Liu; Nan Yan; Mingyi Zhang (Soil Dynamics and Earthquake Engineering, 2023)

Lifetime exposure to benzophenone-3 at an environmentally relevant concentration leads to female–biased social behavior and cognition deficits in zebrafish - Chenglian Bai; Haojia Dong; Junyan Tao; Yuanhong Chen; Hui Xu; Jian Lin; Changjiang Huang; Qiaoxiang Dong (Science of The Total Environment, 2023)

Understanding and revealing the intrinsic impacts of the COVID-19 lockdown on air quality and public health in North China using machine learning - Yunqian Lv; Hezhong Tian; Lining Luo; Shuhan Liu; Xiaoxuan Bai; Hongyan Zhao; Kai Zhang; Shumin Lin; Shuang Zhao; Zhihui Guo; Yifei Xiao; Junqi Yang (Science of The Total Environment, 2023)

Metagenomics analysis of antibiotic resistance genes, the bacterial community and virulence factor genes of fouled filters and effluents from household water purifiers in drinking water - Minglu Zhang; Yue Wang; Miao Bai; Hairong Jiang; Ruoqi Cui; Kaizong Lin; Chaohong Tan; Cuiling Gao; Can Zhang (Science of The Total Environment, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Evolution of spatiotemporal ground deformation over 30 years in Xi’an, China, with multi-sensor SAR interferometry - Guangrong Li; Chaoying Zhao; Baohang Wang; Mimi Peng; Lin Bai (Journal of Hydrology, 2023)

Sustainable preparation of lignocellulosic nanofibrils and cellulose nanopaper from poplar sawdust - Wei Liu; Shuya Zhang; Kun Liu; Hongbin Yang; Qingyi Lin; Ting Xu; Xueping Song; Haishun Du; Long Bai; Shuangquan Yao; Chuanling Si (Journal of Cleaner Production, 2023)

The dynamic changes of flavors and UPLC-Q-Exactive-Orbitrap-MS based lipidomics in mackerel (Scomberomorus niphonius) during dry-cured processing - Qiaoyu Liu; Jianjun Lin; Wenhong Zhao; Menglin Lei; Juan Yang; Weidong Bai (Food Research International, 2023)

Emission characteristics and inventory of volatile organic compounds from the Chinese cement industry based on field measurements - Xiaoxuan Bai; Wei Liu; Bobo Wu; Shuhan Liu; Xiangyang Liu; Yan Hao; Weizhao Liang; Shumin Lin; Lining Luo; Shuang Zhao; Chuanyong Zhu; Jiming Hao; et al. (Environmental Pollution, 2023)

Hollow Co-CeO2@PEG nanospheres: Ultrasound enhanced cascade-nanozyme for synergetic anticancer - Miao Wang; Stephen Choi; Qingchen Bai; Kai Yu; Wei Guo; Feng Zhang; Ran Jia; Fengyu Qu; Huiming Lin (Chemical Engineering Journal, 2023)

Phthalocyanine-mediated interfacial self-assembly of magnetic graphene nanocomposites toward low-frequency electromagnetic wave absorption - Chenchen Liu; Shuning Liu; Xiaofang Feng; Ke Zhu; Guo Lin; Zhongxiang Bai; Lingling Wang; Xiaobo Liu (Chemical Engineering Journal, 2023)

Corrigendum to “Novel diketopyrrolopyrrole NIR-II fluorophores and DDR inhibitors for in vivo Chemo-photodynamic therapy of Osteosarcoma” [Chem. Eng. J. 446 (2022) 136929] - Xiaoding Cheng; Chong Zhang; Kun Shen; Huifan Liu; Caihong Bai; Qihang Ding; Mengting Guan; Junzhu Wu; Zhiquan Tian; Deliang Chen; Lin Cai; Xuechuan Hong; et al. (Chemical Engineering Journal, 2023)

A smart composite coating with photothermal response, anti-UV and anti-corrosion properties - Yue Sun; Sicheng Yuan; Weihao Fan; Dan Lin; Kun Zhang; Ziheng Bai; Yanji Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Correction to: Reforming China’s fertilizer policies: implications for nitrogen pollution reduction and food security - Xiaoxi Wang; Meng Xu; Bin Lin; Benjamin Leon Bodirsky; Jiaqi Xuan; Jan Philipp Dietrich; Miodrag Stevanović; Zhaohai Bai; Lin Ma; Shuqin Jin; Shenggen Fan; Hermann Lotze-Campen; et al. (Sustainability Science, 2023)

Reforming China’s fertilizer policies: implications for nitrogen pollution reduction and food security - Xiaoxi Wang; Meng Xu; Bin Lin; Benjamin Leon Bodirsky; Jiaqi Xuan; Jan Philipp Dietrich; Miodrag Stevanović; Zhaohai Bai; Lin Ma; Shuqin Jin; Shenggen Fan; Hermann Lotze-Campen; et al. (Sustainability Science, 2023)
Reactive nitrogen (N) is a requisite nutrient for agricultural production, but results in greenhouse gas and air and water pollution. The environmental and economic impacts of N fertilizer use in China are particularly relevant, as China consumes the largest amount of N fertilizer in the world to meet its soaring food demand. Here, we use an agro-economic land system model (MAgPIE) in combination with a difference-in-differences econometric model to provide a forward-looking assessment of China’s fertilizer policies in terms of removing fertilizer manufacturing subsidies and implementing measures to improve agricultural nutrient management efficiency. Our model results indicate that enhancing soil N uptake efficiency and manure recycled to soil alongside fertilizer subsidy removal can largely reduce N fertilizer use and N losses and abate N pollution in the short and long term, while food security remains largely unaffected. Enhancing soil N uptake efficiency appears to be decisive to achieving China’s national strategic target of zero growth in N fertilizer use. This study also finds that improving agricultural nutrient management efficiency contributes to higher land productivity and less cropland expansion, with substantial benefits for the environment and food security.

Volumetric Imaging of Neural Activity by Light Field Microscopy - Lu Bai; Zhenkun Zhang; Lichen Ye; Lin Cong; Yuchen Zhao; Tianlei Zhang; Ziqi Shi; Kai Wang (Neuroscience Bulletin, 2022)
Recording the highly diverse and dynamic activities in large populations of neurons in behaving animals is crucial for a better understanding of how the brain works. To meet this challenge, extensive efforts have been devoted to developing functional fluorescent indicators and optical imaging techniques to optically monitor neural activity. Indeed, optical imaging potentially has extremely high throughput due to its non-invasive access to large brain regions and capability to sample neurons at high density, but the readout speed, such as the scanning speed in two-photon scanning microscopy, is often limited by various practical considerations. Among different imaging methods, light field microscopy features a highly parallelized 3D fluorescence imaging scheme and therefore promises a novel and faster strategy for functional imaging of neural activity. Here, we briefly review the working principles of various types of light field microscopes and their recent developments and applications in neuroscience studies. We also discuss strategies and considerations of optimizing light field microscopy for different experimental purposes, with illustrative examples in imaging zebrafish and mouse brains.

Genome-Wide Association and Expression Analysis Revealed the Candidate Variants and Molecular Underpinnings of Cold-Stress Response in Large Yellow Croaker - Ning Suo; Yidi Wu; Zhixiong Zhou; Qian He; Huaqiang Bai; Huanling Lin; Qiaozhen Ke; Peng Xu (Marine Biotechnology, 2022)

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Spatial patterns and driving factors of carbon stocks in mangrove forests on Hainan Island, China - Yuchen Meng; Ruikun Gou; Jiankun Bai; David Moreno‐Mateos; Charles C. Davis; Luoma Wan; Shanshan Song; Hongsheng Zhang; Xiaoshan Zhu; Guanghui Lin (Global Ecology and Biogeography, 2022)
Aim Mangrove forests are important coastal wetlands for the blue carbon budget and play a significant role in mitigating global climate change. However, spatial patterns of carbon stocks in mangrove forests on an island scale have not been quantified owing to methodological limitations and lack of understanding of controlling factors. We took the entire Hainan Island as a case study and aimed to carry out a comprehensive investigation of the spatial patterns and driving factors of carbon stocks in mangrove forests. Location Southern China. Time period 2017–2020. Major taxa studied Mangrove forest. Methods The upscaling method combined with field surveys and Sentinel‐2 imagery analysis were used to compare different models for optimization of mangrove ecosystem carbon stock estimations. We also used structural equation modelling (SEM) to evaluate the factors driving the distributional patterns of mangrove carbon stocks on an island scale. Results The current total mangrove carbon stock of the entire Hainan Island was estimated to be 703,181 Mg C (with a mean density of 192 Mg C/ha), with the above‐ and below‐ground carbon stocks averaging at 44.7 and 147.3 Mg C/ha, respectively. The mangrove carbon storage in the north‐eastern region of the island was the highest and in the west region the lowest. Sediment nitrogen content and plant species diversity had the most positive driving effects on the distribution of total carbon stock for Hainan Island mangroves. Main conclusions The combination of field surveys and Sentinel‐2 imagery analysis can be applied to regional‐scale estimations of carbon stocks for mangrove forests. Spatial pattens of mangrove carbon stocks vary among locations on Hainan Island, and soil nutrient (especially nitrogen) availability is the dominant factor regulating carbon stock variations along the land‐to‐sea gradient. Our findings have significant implications for better understanding the distribution of mangrove carbon stocks and quantification of the global blue carbon budget.

Identification and molecular mapping of YrBm for adult plan resistance to stripe rust in Chinese wheat landrace Baimangmai - Chaoyue Hu; Fengtao Wang; Jing Feng; Cai Sun; Jiyuan Guo; Xiaowei Lang; Jinghuang Hu; Bin Bai; Wentao Zhang; Hongjie Li; Ruiming Lin; Shichang Xu (Theoretical and Applied Genetics, 2022)

The effect and its critical window for ambient temperature and humidity in pregnancy on term low birth weight - Shuang Du; Shuoxin Bai; Xiaodong Zhao; Shaoqian Lin; Yifan Zhai; Zhaojun Wang; Zhiping Wang (Environmental Science and Pollution Research, 2022)

Influence of different inoculation densities of black soldier fly larvae (Hermetia illucens) on heavy metal immobilization in swine manure - Dongmei Jiang; Kunhong Jiang; Rui Li; Liangbin Zhao; Zile Liu; Bangjie Xiong; Du Jin; Xiaoxia Hao; Li Zhu; Bo Kang; Lin Bai (Environmental Science and Pollution Research, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Preliminary study of genome-wide association identified novel susceptibility genes for thyroid-related hormones in Chinese population - Liang Huang; Fenghua Bai; Yutian Zhang; Shanshan Zhang; Tianbo Jin; Xingwei Wei; Xiaoli Zhou; Mei Lin; Yufei Xie; Chanyi He; Qi Lin; Tian Xie; et al. (Genes & Genomics, 2022)

Rhodohalobacter sulfatireducens sp. nov., isolated from a marine solar saltern - Yu-Sheng Wang; Yu-Yan Yue; Yi-Lin Bai; Xu-Yang Zhang; Shuo Wang; Zong-Jun Du (Archives of Microbiology, 2022)

Pon1 Deficiency Promotes Trem2 Pathway–Mediated Microglial Phagocytosis and Inhibits Pro-inflammatory Cytokines Release In Vitro and In Vivo - Li Zhang; Wei Dong; Yuanwu Ma; Lin Bai; Xu Zhang; Caixian Sun; Jingwen Li; Lianfeng Zhang (Molecular Neurobiology, 2022)

A review on the removal of phthalate acid esters in wastewater treatment plants: from the conventional wastewater treatment to combined processes - Lin Bai; Xiaowan Dong; Fangshu Wang; Xiaohan Ding; Zhikai Diao; Dong Chen (Environmental Science and Pollution Research, 2022)

Derivation of water quality criteria for glyphosate and its formulations to protect aquatic life in China - Yili Fan; Kaibo Zhang; Ruiqing Zhang; Guanghui Guo; Huixian Li; Yingchen Bai; Ying Lin; Ting Cai (Environmental Science and Pollution Research, 2022)

Immobilization of lead, copper, cadmium, nickel, and zinc in sediment by red mud: adsorption characteristics, mechanism, and effect of dosage on immobilization efficiency - Xianshang Bai; Jianwei Lin; Zhibin Zhang; Yanhui Zhan (Environmental Science and Pollution Research, 2022)

A dose- and time-dependent effect of oxythiamine on cell growth inhibition in non-small cell lung cancer - Lin Bai; Hui-li Zhu (Cognitive Neurodynamics, 2022)
The high mortality rate of non-small-cell lung cancer (NSCLC) is mostly due to the high risk of recurrence. A comprehensive understanding of proliferation mechanisms of NSCLC would remarkably contribute to blocking up the invasion and metastasis of tumor cells. In our previous study, the remarkable decreased activity of Thiamine-dependent enzymes (TDEs), involving in intermediary metabolism responsible for energy production of tumor, was found under conditions of thiamine deficiency in vivo. To explore the effect of Oxythiamine (OT), a TDEs antimetabolite, on cell growth, we co-cultured A549 cells with OT in vitro at various doses (0.1, 1, 10 and 100 μM) and time periods (6, 12, 24 and 48 h) and subsequent cell proliferation and apoptosis assays were performed respectively. Our findings demonstrated that A549 cells proliferation was significantly downregulated by OT treatment in a progressively dose as well as time dependent manner. Inhibition of TDEs resulted in antagonism of lung cancer growth by inducing cells to cease the cycle as well as apoptotic cell death. We concluded a critical role of OT, a TDEs antagonistic compound, indicating the potential target of its practical use.

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Autoimmune Cerebellar Ataxia: Etiology and Clinical Characteristics of a Case Series from China - Mange Liu; Haitao Ren; Yicheng Zhu; Siyuan Fan; Lin Bai; Jing Wang; Liying Cui; Hongzhi Guan (The Cerebellum, 2022)

Community Structure of Benthic Macrofauna and the Ecological Quality of Mangrove Wetlands in Hainan, China - Ping Li; Jingli Liu; Jiankun Bai; Yifan Tong; Yuchen Meng; Xiaoping Diao; Ke Pan; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2022)
Few studies have systematically assessed the ecological status of mangrove wetlands following the stress of anthropogenic activities in China. This study investigated the spatial and seasonal distribution of benthic macroinvertebrate communities and assessed the ecological quality of mangrove habitats on an island scale in Hainan, China (containing the third largest mangrove area of China and the highest mangrove species richness). For the benthic macrofauna community structure, a total of 102 macrobenthic taxa belonging to 50 families were identified, with Crustaceans, Molluscs, Polychaetes, and Oligochaeta having relative abundances of 52.3%, 36.1%, 10.8%, and 0.8%, respectively. Decapoda and Gastropoda dominated the benthic community abundance. Non-metric multidimensional scaling and an analysis of similarities revealed significantly different macroinvertebrate assemblages among the regions during the two seasons. The South mangroves had the lowest macrofauna species numbers, biodiversity, richness, and abundance. The macrofaunal species richness, Shannon index, Margalef index, abundance, and biomass markedly affected by region and season. As indicated by the biotic indices AMBI (AZTI’s Marine Biotic Index) and M-AMBI, more than half of the mangrove habitats on Hainan Island were slightly to heavily disturbed and had poor to moderate ecological quality. Our results recommend long-term monitoring for evaluating the quality status of mangrove wetlands and avoiding extensive land-use conversion of mangroves. Holistic approaches considering ecological characteristics and combining information on both floral and faunal functionality would contribute to the effective management and conservation of mangroves in disturbed areas.

Two new 7,20-epoxy- ent -kaurane diterpenoids from the aerial parts of Isodon serra - Juan-Juan Hu; Bai-Lin Li; Jin-Dan Xie; Hui-Jun Liang; Qian-Ran Li; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2022)

Lipoxin A4 regulates M1/M2 macrophage polarization via FPR2–IRF pathway - Jixiang Yuan; Feihong Lin; Lichen Chen; Weikang Chen; Xiaodong Pan; Yongheng Bai; Yong Cai; Hong Lu (Inflammopharmacology, 2022)

Characterization of the trophic transfer and fate of methylmercury in the food web of Zhalong Wetland, Northeastern China - Jinming Luo; Wenchong Zhang; Lin Bai; Hongying Li; Zhongyan Gao (Environmental Science and Pollution Research, 2022)

Effects of conservation measures on crop diversity and their implications for climate-resilient livelihoods: the case of Rupa Lake Watershed in Nepal - Yun-li Bai; Chao Fu; Balaram Thapa; Ram Balladur Rana; Lin-xiu Zhang (Journal of Mountain Science, 2022)
Agrobiodiversity conservation is vital for achieving sustainability, but empirical studies on the effects of different practices or measures on crop diversity are rare. This study aims to estimate the effects of raising conservation awareness (RCA), building diversity blocks (BDB), and their combination on crop diversity among 240 randomly selected households surrounding the Rupa Lake Watershed in Nepal. Based on descriptive analysis and multiple regression models, the results indicate that the two single measures had no significant effect on the numbers of crop species and varieties grown by households in 2018. However, the combination of RCA and BDB had a significantly positive effect on the number of crop varieties, especially for grain and vegetable crops. Considering that these crops are essential in the daily lives of local people, the results indicate that a strategy that combines both awareness raising and on-farm conservation measures can generate higher crop diversity and better serve the climate-resilient livelihoods of people in mountainous areas.

Contraction and warming of Antarctic Bottom Water in the Amundsen Sea - Yu Bai; Liang Zhao; Jingen Xiao; Shiying Lin (Acta Oceanologica Sinica, 2022)

Can transportation infrastructure reduce haze pollution in China? - Chenggang Li; Tao Lin; Zhifei Zhang; Dan Xu; Lei Huang; Wanping Bai (Environmental Science and Pollution Research, 2022)

Correction to: Comparative chloroplast genomes of Prunus subgenus Cerasus (Rosaceae): insights into sequence variations and phylogenetic relationships - Jiawen Yan; Jianhui Li; Lin Yu; Wenfu Bai; Dongling Nie; Ying Xiong; Sizheng Wu (Tree Genetics & Genomes, 2022)

Video target detection of East Asian migratory locust based on the MOG2-YOLOv4 network - Zhao Bai; Zhan Tang; Lei Diao; Shuhan Lu; Xuchao Guo; Han Zhou; Chengqi Liu; Lin li (International Journal of Tropical Insect Science, 2022)

Identifying the priority areas for enhancing the ecosystem services in hilly and mountainous areas of southern China - Jia-ling Tian; Yu Peng; Yi-hang Huang; Ting Bai; Lian-lin Liu; Xiao-ao He; Shi-qian Luo (Journal of Mountain Science, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Responses of soil pH to no‐till and the factors affecting it: A global meta‐analysis - Xin Zhao; Cong He; Wen‐Sheng Liu; Wen‐Xuan Liu; Qiu‐Yue Liu; Wei Bai; Li‐Jun Li; Rattan Lal; Hai‐Lin Zhang (Global Change Biology, 2022)
No‐till (NT) is a sustainable option because of its benefits in controlling erosion, saving labor, and mitigating climate change. However, a comprehensive assessment of soil pH response to NT is still lacking. Thus, a global meta‐analysis was conducted to determine the effects of NT on soil pH and to identify the influential factors and possible consequences based on the analysis of 114 publications. When comparing tillage practices, the results indicated an overall significant decrease by 1.33 ± 0.28% in soil pH under NT than that under conventional tillage ( p −1 (−1.83%), or crop residue retention (−1.52%). Changes in organic matter decomposition under undisturbed soil and with crop residue retention might lead to a higher concentration of H + and lower of basic cations (i.e., calcium, magnesium, and potassium), which decrease the soil pH, and consequently, impact nutrient dynamics (i.e., soil phosphorus) in the surface layer under NT. Furthermore, soil acidification may be aggravated by NT within site‐specific conditions and improper fertilizer and crop residue management and consequently leading to adverse effects on soil nutrient availability. Thus, there is a need to identify strategies to ameliorate soil acidification under NT to minimize the adverse consequences.

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Comparative chloroplast genomes of Prunus subgenus Cerasus (Rosaceae): insights into sequence variations and phylogenetic relationships - Jiawen Yan; Jianhui Li; Lin Yu; Wenfu Bai; Dongling Nie; Ying Xiong; Sizheng Wu (Tree Genetics & Genomes, 2021)

Characterization on the P-associated and agronomic traits as well as associated molecular processes in wheat under Pi deprivation condition - Ying-Jia Zhao; Xin-Yang Bai; Rui-Ze Lin; Fang-fang Li; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Efficiency and mechanism of a vermicompost additive in enhancing composting of swine manure - Xiaoxia Hao; Xinyuan Ma; Bo Zeng; Li Zhu; Linyuan Shen; Mingxian Yang; Hongwen Hu; Dongmei Jiang; Lin Bai (Environmental Science and Pollution Research, 2021)

Conservation planning on China's borders with Myanmar, Laos, and Vietnam - Lin Wang; Bin Yang; Yang Bai; Xiaoqiang Lu; Richard T. Corlett; Yunhong Tan; Xiao‐Yong Chen; Jianguo Zhu; Yan Liu; Rui‐Chang Quan (Conservation Biology, 2021)
Transboundary conservation is playing an increasingly important role in maintaining ecosystem integrity and halting biodiversity loss caused by anthropogenic activities. However, lack of information on species distributions in transboundary regions and understanding of the threats in these areas impairs conservation. We developed a spatial conservation plan for the transboundary areas between Yunnan province, southwestern China, and neighboring Myanmar, Laos, and Vietnam in the Indo‐Burma biodiversity hotspot. To identify priority areas for conservation and restoration, we determined species distribution patterns and recent land‐use changes and examined the spatiotemporal dynamics of the connected natural forest, which supports most species. We assessed connectivity with equivalent connected area (ECA), which is the amount of reachable habitat for a species. An ECA incorporates the presence of habitat in a patch and the amount of habitat in other patches within dispersal distance. We analyzed 197,845 locality records from specimen collections and monographs for 21,004 plant and vertebrate species. The region of Yunnan immediately adjacent to the international borders had the highest species richness, with 61% of recorded species and 56% of threatened vertebrates, which suggests high conservation value. Satellite imagery showed the area of natural forest in the border zone declined by 5.2% (13,255 km 2 ) from 1995 to 2018 and monoculture plantations increased 92.4%, shrubland 10.1%, and other cropland 6.2%. The resulting decline in connected natural forest reduced the amount of habitat, especially for forest specialists with limited dispersal abilities. The most severe decline in connectivity was along the Sino‐Vietnamese border. Many priority areas straddle international boundaries, indicating demand and potential for establishing transboundary protected areas. Our results illustrate the importance of bi‐ and multilateral cooperation to protect biodiversity in this region and provide guidance for future conservation planning and practice.

Temporal stability analysis of soil moisture along a coniferous forest hillslope with subtropical monsoon climate in southwest China - Yu-shi Bai; Mu-xing Liu; Jun Yi; Hai-lin Zhang (Journal of Mountain Science, 2021)

Population, Reproductive and Fishery Dynamics of Spotted Box Crab (Calappa philargius), a New Claw-Only Fishery Species, in the Southern Taiwan Strait, China - Bai-an Lin; Yan Jiang; Robert Boenish; Qing Xu; Min Liu (Frontiers in Marine Science, 2021)
The spotted box crab Calappa philargius (Calappidae) is an increasingly consumed species in China, mainly sourced from a claw-only fishery. Being a not well-characterized species in the literature, this study is warranted to inform sustainable management approaches. Here we report on the first in-depth overview on biology and fishery dynamics of C. philargius in the southern Taiwan Strait of China. Whole body crabs ( N = 1,009) were collected monthly from January to December 2019 from trawlers, operating in the southern Taiwan Strait; sample collection was absent from May to July because of the national fishing moratorium regulation. Sex ratio, growth pattern, size at maturity and fecundity were estimated. The overall male: female ratio was 1: 1.47, significantly differing from the 1: 1 ( p < 0.01); monthly sex ratio variations were also significant ( p < 0.01), suggesting possible seasonal sexual segregation. We found the carapace widths (CW) of males were significantly larger than those of females ( p < 0.01). Based on the occurrence and percentages of berried females, we identified twin spawning events in January–April and August–October with the overall peak occurring in February. Size at 50% female maturity was 11.47 cm CW. Female absolute fecundity was significantly related to CW via a power function relationship ( N = 14, p < 0.01). The estimated average claw yield was 36.28 ± 3.07% of the whole body weight ( N = 95), irrespective of sex and size ( p > 0.5). Capture and trade data of C. philargius using trawl and trap fishing gears were documented to characterize claw-only fishery dynamics for future research and sustainable use.

Mapping coastal wetlands in the Yellow River Delta, China during 2008–2019: impacts of valid observations, harmonic regression, and critical months - Zhanpeng Wang; Yinghai Ke; Mengmeng Chen; Demin Zhou; Lin Zhu; Junhong Bai (International Journal of Remote Sensing, 2021)

Distribution and land use characteristics of alluvial fans in the Lhasa River Basin, Tibet - Tongde Chen; Juying Jiao; Yixian Chen; Hong Lin; Haolin Wang; Leichao Bai (Journal of Geographical Sciences, 2021)

A new monoterpene-lactone with neuroprotective activity from corn silk - Wei-Yu Zhou; Tian-Ming Lv; Zi-Lin Hou; Ming Bai; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Production of purple Ma bamboo (Dendrocalamus latiflorus Munro) with enhanced drought and cold stress tolerance by engineering anthocyanin biosynthesis - Mengqi Xiang; WenSha Ding; Chu Wu; Wenjia Wang; Shanwen Ye; Changyang Cai; Xin Hu; Nannan Wang; Weiyuan Bai; Xiaoshan Tang; Caiping Zhu; Xiaomin Yu; et al. (Planta, 2021)

Characterization of Yields, Osmotic Stress-associated Traits, and Expression Patterns of ABA Receptor Genes in Winter Wheat Under Deficit Irrigation - Xinyang Bai; Liguo Guo; Ruize Lin; Le Han; Kai Xiao (International Journal of Plant Production, 2021)

Effects of Heat Stress on Gut Microbiome in Rats - Qian Qu; Hua Li; Lin Bai; Shiwei Zhang; Jiaqi Sun; Weijie Lv; Chunxin Ye; Cui Liu; Dayou Shi (Indian Journal of Microbiology, 2021)
Gut microbiome, as the largest and most important micro-ecosystem, plays a critical role in health. The purpose of this study was to evaluate whether heat stress modulates the composition and diversity of the gut microbiome in rats. The heat stress model was prepared in rats with the heating temperature maintained at 35–38°C. Cecum contents were collected after heat stress for 3 h and days 1, 3 and 7. Total DNA was extracted for 16 S rRNA sequencing and analysis of intestinal microbiome composition and diversity. The study showed that the composition of the intestinal microbiome of heat stress group was changed. And the heat stress modulated key phylotypes of gut microbiota at the level of phylum and genus. In particular, the genus of Lactobacillus and Bacteroides were significantly reduced, whereas the Oscillospira and Clostridium were increased by heat stress. Meanwhile, the rats under the heat stress encountered the change in carbohydrate metabolism, amino acid metabolism, and membrane transport to defense against stress. Taken together, the composition and structure of gut microbiome were affected by heat stress and some key phylotypes were also significantly altered. We conclude that the heat stress could impact multiple biological functions, via altering the gut microbiome.

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Sea surface salinity-derived indexes for distinguishing two types of El Niño events in the tropical Pacific - Hai Zhi; Pengfei Lin; Zhujun Fang; Hailong Liu; Rong-Hua Zhang; Wenrong Bai (Science China Earth Sciences, 2021)

GABA Signaling Pathway-associated Gene PLCL1 Rare Variants May be Associated with Autism Spectrum Disorders - Fengyun Zheng; Guoyuan Liu; Ting Dang; Qiaowen Chen; Yu An; Meng Wu; Xiangxuan Kong; Zilong Qiu; Bai-Lin Wu (Neuroscience Bulletin, 2021)

Using stratified Bayesian model averaging in probabilistic forecasts of precipitation over the middle and lower Yangtze River region - Haixia Qi; Xiefei Zhi; Tao Peng; YongQing Bai; Chunze Lin; Wen Chen (Meteorology and Atmospheric Physics, 2021)

Experimental Research on Adsorption Kinetic Characteristics of CH4, CO2, and N2 in Coal from Junggar Basin, China, at Different Temperatures - Wanjie Sun; Haifei Lin; Shugang Li; Xiangguo Kong; Hang Long; Min Yan; Yang Bai; Jiamin Tian (Natural Resources Research, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Evolution of delayed water inrush in fault fracture zone considering time effect - Jiwen Bai; Shaolong Duan; Rentai Liu; Lin Xin; Jiawei Tian; Qingsong Zhang; Heng Ma (Arabian Journal of Geosciences, 2021)

New insights into the fine-scale history of western–eastern admixture of the northwestern Chinese population in the Hexi Corridor via genome-wide genetic legacy - Hongbin Yao; Mengge Wang; Xing Zou; Yingxiang Li; Xiaomin Yang; Ailin Li; Hui-Yuan Yeh; Peixin Wang; Zheng Wang; Jingya Bai; Jianxin Guo; Jinwen Chen; et al. (Molecular Genetics and Genomics, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Simvastatin Enhances Muscle Regeneration Through Autophagic Defect-Mediated Inflammation and mTOR Activation in G93ASOD1 Mice - Yafei Wang; Lin Bai; Shuai Li; Ya Wen; Qi Liu; Rui Li; Yaling Liu (Molecular Neurobiology, 2021)

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

Western North Pacific Tropical Cyclone Database Created by the China Meteorological Administration - Xiaoqin Lu; Hui Yu; Ming Ying; Bingke Zhao; Shuai Zhang; Limin Lin; Lina Bai; Rijin Wan (Advances in Atmospheric Sciences, 2021)
This paper describes the access to, and the content, characteristics, and potential applications of the tropical cyclone (TC) database that is maintained and actively developed by the China Meteorological Administration, with the aim of facilitating its use in scientific research and operational services. This database records data relating to all TCs that have passed through the western North Pacific (WNP) and South China Sea (SCS) since 1949. TC data collection has expanded over recent decades via continuous TC monitoring using remote sensing and specialized field detection techniques, allowing collation of a multi-source TC database for the WNP and SCS that covers a long period, with wide coverage and many observational elements. This database now comprises a wide variety of information related to TCs, such as historical or real-time locations (i.e., best track and landfall), intensity, dynamic and thermal structures, wind strengths, precipitation amounts, and frequency. This database will support ongoing research into the processes and patterns associated with TC climatic activity and TC forecasting.

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Correction to: IL-17A Induces MIP-1α Expression in Primary Astrocytes Via Src/MAPK/PI3K/NF-kB Pathways: Implications for Multiple Sclerosis - Hongwei Yi; Ying Bai; Xinjian Zhu; Lin Lin; Lei Zhao; Xiaodong Wu; Shilpa Buch; Longxin Wang; Jie Chao; Honghong Yao (Journal of Neuroimmune Pharmacology, 2021)

MiR-27b-3p inhibits the progression of renal fibrosis via suppressing STAT1 - Lin Bai; Yongtao Lin; Juan Xie; Yiyuan Zhang; Hongwu Wang; Donghui Zheng (Human Cell, 2021)
Renal fibrosis is a pathologic change in chronic kidney disease (CKD). MicroRNAs (miRNAs) have been shown to play an important role in the development of renal fibrosis. However, the biological role of miR-27b-3p in renal fibrosis remains unclear. Thus, this study aimed to investigate the role of miR-27b-3p in the progression of renal fibrosis. In this study, HK-2 cells were stimulated with transforming growth factor (TGF)-β1 for mimicking fibrosis progression in vitro. The unilateral ureteric obstruction (UUO)-induced mice renal fibrosis in vivo was established as well. The results indicated that the overexpression of miR-27b-3p significantly inhibited epithelial-to-mesenchymal transition (EMT) in TGF-β1-stimulated HK-2 cells, as shown by the decreased expressions of α-SMA, collagen III, Fibronectin and Vimentin. In addition, overexpression of miR-27b-3p markedly decreased TGF-β1-induced apoptosis in HK-2 cells, as evidenced by the decreased levels of Fas, active caspase 8 and active caspase 3. Meanwhile, dual-luciferase assay showed that miR-27b-3p downregulated signal transducers and activators of transcription 1 (STAT1) expression through direct binding with the 3′-UTR of STAT1. Furthermore, overexpression of miR-27b-3p attenuated UUO-induced renal fibrosis via downregulation of STAT1, α-SMA and collagen III. In conclusion, miR-27b-3p overexpression could alleviate renal fibrosis via suppressing STAT1 in vivo and in vitro. Therefore, miR-27b-3p might be a promising therapeutic target for the treatment of renal fibrosis.

Genome-Wide Association Study Identifies Genomic Loci of Sex Determination and Gonadosomatic Index Traits in Large Yellow Croaker (Larimichthys crocea) - Huanling Lin; Zhixiong Zhou; Ji Zhao; Tao Zhou; Huaqiang Bai; Qiaozhen Ke; Fei Pu; Weiqiang Zheng; Peng Xu (Marine Biotechnology, 2021)

Gastrointestinal toxicities associated with immune checkpoint inhibitors: a disproportionality analysis leveraging VigiBase, the WHO Adverse Drug Reaction Database - Sifu Huang; Xuefeng Bai; Taiyong Fang; Yanta Guo; Kainan Zheng; Xiahong Lin (Journal of Zhejiang University-SCIENCE B, 2021)

Preliminary study on relationships among nutritional risk, serum prealbumin, and peripheral blood T cell subsets in patients with severe COVID-19 - Yanli Li; Yanbo Sun; Jing He; Peng Zhao; Pengju Luo; Jinsong Bai; Weiming Li; Shumin Li; Yueying Lin; Yunyun Cen (Infectious Diseases, 2021)

Artificial selection in breeding extensively enriched a functional allelic variation in TaPHS1 for pre-harvest sprouting resistance in wheat - Shubing Liu; Danfeng Wang; Meng Lin; Sunish K. Sehgal; Lei Dong; Yuye Wu; Guihua Bai (Theoretical and Applied Genetics, 2021)

Memory impairment of chewing-side preference mice is associated with 5-HT-BDNF signal pathway - Hua Jiang; Hong Yin; Lin Wang; Chunzhen Feng; Yang Bai; Dongzong Huang; Qiao Zhang; Hongchen Liu; Yuan Hu (Molecular and Cellular Biochemistry, 2021)

Interception of sedimentary phosphorus release by iron-modified calcite capping - Xiaoyun Bai; Jianwei Lin; Zhibin Zhang; Boyang Liu; Yanhui Zhan; Dazhu Hu (Journal of Soils and Sediments, 2021)

Biochar improves heavy metal passivation during wet anaerobic digestion of pig manure - Jun Wang; Xiaoxia Hao; Zile Liu; Zili Guo; Li Zhu; Bangjie Xiong; Dongmei Jiang; Linyuan Shen; Mingzhou Li; Bo Kang; Guoqing Tang; Lin Bai (Environmental Science and Pollution Research, 2021)

Wetland Ecosystem Service Dynamics in the Yellow River Estuary under Natural and Anthropogenic Stress in the Past 35 Years - Huijuan Xia; Lusan Liu; Junhong Bai; Weijing Kong; Kuixuan Lin; Fen Guo (Wetlands, 2020)

Assessment of Applications of Design of Experiments in Pharmaceutical Development for Oral Solid Dosage Forms - Ge Bai; Zhijin Chen; Kimberly Raines; Hansong Chen; Kaushalkumar Dave; Ho-Pi Lin; Banu S. Zolnik (Journal of Pharmaceutical Innovation, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Over expression of a Chitinase 2 gene from Chinese Wild Strawberry improves resistance to anthracnose disease in transgenic Arabidopsis thaliana - Zhifeng Wen; Jinhui Bai; Lin Wang; Liping Yao; Bilal Ahmad; Muhammad Hanif; Qingxi Chen (Plant Biotechnology Reports, 2020)

Development of 85 SNP markers for the endangered plant species Prunus mira (Rosaceae) based on restriction site-associated DNA sequencing (RAD-seq) - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Yu-e Bai (Conservation Genetics Resources, 2020)

Diagnostic value of optic disc retinal nerve fiber layer thickness for diabetic peripheral neuropathy - Xiao-hong Wu; Jing-wen Fang; Yin-qiong Huang; Xue-feng Bai; Yong Zhuang; Xiao-yu Chen; Xia-hong Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Chemoheterotrophic diazotrophs contribute to nitrogen incorporation in a semi-arid desert - Lin Miao; Wei Feng; Yuqing Zhang; Yuxuan Bai; Yanfei Sun; Weiwei She; Henan Mao; Zongrui Lai; Shugao Qin (Biology and Fertility of Soils, 2020)

Nitrogen‐induced acidification, not N‐nutrient, dominates suppressive N effects on arbuscular mycorrhizal fungi - Shang Pan; Yang Wang; Yunpeng Qiu; Dima Chen; Lin Zhang; Chenglong Ye; Hui Guo; Weixing Zhu; Aiqun Chen; Guohua Xu; Yi Zhang; Yongfei Bai; et al. (Global Change Biology, 2020)
Arbuscular mycorrhizal fungi (AMF) form symbiosis with most terrestrial plant roots, obtaining photosynthates in return for mineral nutrients. Ecological theories based on the economics of trading partnership predict that nutrient enrichment would suppress AMF. Experimental results from nitrogen (N) and phosphorus (P) additions, however, were highly variable, and the underlying mechanisms remain unclear. Here we show distinct AMF responses to soil N:P stoichiometry manipulations via gradients of long‐term N and P additions in a Mongolian steppe. A complementary experiment with an acid addition gradient was designed to help tease apart the effect of N‐induced acidification from N nutrient. AMF root colonization and extraradical fungal biomass progressively decreased along the P gradient under two distinct host plant species, suggesting a carbon (C)‐P tradeoff. In contrast, low to moderate N inputs increased both AMF parameters, corresponding to the increasing N:P ratio. Yet, high N inputs reduced AMF colonization and biomass, and the magnitudes of N‐led inhibition were similar to those under acid additions that induced comparable changes in soil pH. Structural equation modeling further showed that while soil N:P stoichiometry primarily controlled the effect of P addition on AMF, N‐induced soil acidity overtook the N:P stoichiometry under high N inputs and dominated the effects of reactive N on AMF. In addition, AMF community composition in roots was more dependent on host plants and unresponsive to changes in soil nutrients. We further proposed a comprehensive framework that integrates biological and geochemical effects of reactive N and P inputs on AMF. Together, these results indicate that while the C‐P tradeoff controls P suppression of AMF, N‐induced acidification dominates the N inhibition. Our findings suggest that incorporation of geochemical impacts of N and P inputs would facilitate modeling efforts to project mycorrhizal impact on plant interactions and soil C balance under future nutrient enrichment scenarios.

SEPM: rapid seism emergency information processing based on social media - Xuesong Bai; Xiaoxue Liu; Shuhan Lu; Xiaodong Zhang; Wei Su; Xiaohui Su; Lin Li (Natural Hazards, 2020)

Genome-Wide Association Study of Body Shape-Related Traits in Large Yellow Croaker (Larimichthys crocea) - Shengnan Kong; Zhixiong Zhou; Tao Zhou; Ji Zhao; Lin Chen; Huanling Lin; Fei Pu; Qiaozhen Ke; Huaqiang Bai; Peng Xu (Marine Biotechnology, 2020)

Comparative analysis of physiological traits of three Actinidia valvata Dunn genotypes during waterlogging and post-waterlogging recovery - Zhi Li; Yunpeng Zhong; Danfeng Bai; Miaomiao Lin; Xiujuan Qi; Jinbao Fang (Horticulture, Environment, and Biotechnology, 2020)

The dominant model analysis of Sirt3 genetic variants is associated with susceptibility to tuberculosis in a Chinese Han population - Tao Wu; Lin Jiao; Hao Bai; Xuejiao Hu; Minjin Wang; Zhenzhen Zhao; Hui Xue; Binwu Ying (Molecular Genetics and Genomics, 2020)

Development and characterization of 72 SNP markers in Armeniaca sibirica based on transcriptomics - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Shulan Bai; Yu-e Bai (Conservation Genetics Resources, 2020)

A minor QTL, SG3, encoding an R2R3-MYB protein, negatively controls grain length in rice - Qiuping Li; Li Lu; Haiyang Liu; Xufeng Bai; Xin Zhou; Bi Wu; Mengqi Yuan; Lin Yang; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

Characteristics and health risk assessments of heavy metals in PM2.5 in Taiyuan and Yuci college town, China - Xiaofeng Liu; Zhilei Wang; Huiling Bai; Shuting Zhang; Ling Mu; Lin Peng (Air Quality, Atmosphere & Health, 2020)

Three new pterocarpans from the aerial parts of Abrus Precatorius - Yan Li; Jie-Wei Wu; Hai-Bo Tan; Bai-Lin Li; Sheng-Xiang Qiu (Natural Product Research, 2020)

Gelsemine, a natural alkaloid extracted from Gelsemium elegans Benth. alleviates neuroinflammation and cognitive impairments in Aβ oligomer-treated mice - Liping Chen; Hanbo Pan; Yujing Bai; Huiqin Li; Wen Yang; Zhi-Xiu Lin; Wei Cui; Yan-Fang Xian (Psychopharmacology, 2020)

Drought-tolerant plant growth-promoting rhizobacteria isolated from jujube (Ziziphus jujuba) and their potential to enhance drought tolerance - Min Zhang; Lin Yang; Ruqian Hao; Xiaoxiong Bai; Ying Wang; Xuan Yu (Plant and Soil, 2020)

Numerical Simulation of Wave Interaction with Payloads of Different Postures Using OpenFOAM - Mingwei Yan; Xin Ma; Wei Bai; Zaibin Lin; Yibin Li (Journal of Marine Science and Engineering, 2020)
A three-dimensional numerical wave tank (NWT) is established with Open Source Field Operation and Manipulation (OpenFOAM) software and waves2foam to investigate wave interaction with payloads with different postures in the process of offshore lifting or lowering. Numerical results of regular wave interaction with a vertically suspending cylinder are presented first for validation by comparison with the published data. A series of simulation experiments are carried out, and the forces and the moments exerted by the regular waves on a fixed suspending cylinder payload and a fixed suspending cuboid payload with different postures are presented. It can be concluded from the results that the rotating rectangular payload (cuboid and cylinder) suffers a drastically changed moment when it is initially vertically placed, and the projection area of payload vertical to the force affects the corresponding force. The simulation results also show how the forces and the moments change with different posture angles. With some certain posture, the suspending payload suffers minimum forces and moments. Parametric study for the cuboid payload is done in the case of normal incidence. The influence of the payload’s size and wave parameters on forces and moments are analyzed. All of the numerical simulation results and conclusions provide the fundamentals for further research and safe control of offshore lifting or lowering.

A spatio-temporal prediction of NDVI based on precipitation: an application for grazing management in the arid and semi-arid grasslands - Taosuo Wu; Feng Feng; Qian Lin; Hongmei Bai (International Journal of Remote Sensing, 2020)

Characterization on the water deprivation-associated physiological traits as well as the related differential genes during seed filling stage in wheat (T. aestivum L.) - Yingjia Zhao; Pingping Du; Zijia Chen; Xinyang Bai; Ruize Lin; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Manganese-modified biochar for highly efficient sorption of cadmium - Xiao Tan; Wenxia Wei; Congbin Xu; Yue Meng; Wenrong Bai; Wenjie Yang; Aijun Lin (Environmental Science and Pollution Research, 2020)

Two new steroidal saponins from Maianthemum henryi and their cytotoxic activity against human HepG2 tumor cells - Jie Lin; Guoquan Wang; Lu Bai; Linzhong Yu (Natural Product Research, 2019)

RUNOFF SHRINKAGE IN THE WUYUR RIVER BASIN, NORTH‐EAST CHINA, AND ITS INFLUENCE ON THE SUCCESSION OF SALINE MARSH IN THE LOWER REACHES - Luo Jinming; Yang Fan; Wang Yongjie; Bai Lin; Liu Fugang; Wang Zhiliang (Irrigation and Drainage, 2019)
Drought induced by global climate change and local human disturbance is having a significant impact on the succession of inland saline marshes. This study aims to examine the causes of rapid land degradation in China's Zhalong wetland over the past 65 years (1951–2015) using the Mann–Kendall rank test. Results indicate that local human disturbance (mainly water diversion) is the key detrimental factor in marsh degradation. Water diversion in the upper reaches of the Wuyur river basin has changed the hydrological regime and caused significant water deficit in the Zhalong wetland, thereby leading to rapid shrinkage of the marsh. An increasing runoff trend with an average of 7.44 × 10 8 m 3 was observed in the upper reaches from 1983 to 2015. In contrast, the runoff in the lower reaches had significantly decreased from 8.5 × 10 8 m 3 to 3 × 10 8 m 3 in recent years ( P 2 in 1979 to 260 km 2 in 2010, in which large areas emerged in the core area of the wetland. Land degradation decreased the habitat of the red‐crowned crane ( Grus japonensis ). This condition may be an important contributor to the population decline of rare birds and biodiversity loss. © 2019 John Wiley & Sons, Ltd.

Plants alter their vertical root distribution rather than biomass allocation in response to changing precipitation - Bingwei Zhang; Marc W. Cadotte; Shiping Chen; Xingru Tan; Cuihai You; Tingting Ren; Minling Chen; Shanshan Wang; Weijing Li; Chengjin Chu; Lin Jiang; Yongfei Bai; et al. (Ecology, 2019)
Elucidating the variation of allocation pattern of ecosystem net primary productivity ( NPP ) and its underlying mechanisms is critically important for understanding the changes of aboveground and belowground ecosystem functions. Under optimal partitioning theory, plants should allocate more NPP to the organ that acquires the most limiting resource, and this expectation has been widely used to explain and predict NPP allocation under changing precipitation. However, confirmatory evidence for this theory has mostly come from observed spatial variation in the relationship between precipitation and NPP allocation across ecosystems, rather than directly from the influences of changing precipitation on NPP allocation within systems. We performed a 6‐yr five‐level precipitation manipulation experiment in a semiarid steppe to test whether changes in NPP allocation can be explained by the optimal partitioning theory, and how water requirement of plant community is maintained if NPP allocation is unaltered. The 30 precipitation levels (5 levels × 6 yr) were divided into dry, nominal, and wet precipitation ranges, relative to historical precipitation variation over the past six decades. We found that NPP in both aboveground ( ANPP ) and belowground ( BNPP ) increased nonlinearly as precipitation increased, while the allocation of NPP to BNPP ( f BNPP ) showed a concave quadratic relationship with precipitation. The declined f BNPP as precipitation increased in the dry range supported the optimal partitioning theory. However, in the nominal range, NPP allocation was not influenced by the changed precipitation; instead, BNPP was distributed more in the surface soil horizon (0–10 cm) as precipitation increased, and conversely more in the deeper soil layers (10–30 cm) as precipitation decreased. This response in root foraging appears to be a strategy to satisfy plant water requirements and partially explains the stable NPP allocation patterns. Overall, our results suggest that plants can adjust their vertical BNPP distribution in response to drought stress, and that only under extreme drought does the optimal partitioning theory strictly apply, highlighting the context dependency of the adaption and growth of plants under changing precipitation.

Overexpression of AtAGT1 promoted root growth and development during seedling establishment - Rui Wang; Lin Yang; Xiaofang Han; Yuhong Zhao; Ling Zhao; Beibei Xiang; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell Reports, 2019)

Latest Progress of the Chinese Meteorological Satellite Program and Core Data Processing Technologies - Peng Zhang; Qifeng Lu; Xiuqing Hu; Songyan Gu; Lei Yang; Min Min; Lin Chen; Na Xu; Ling Sun; Wenguang Bai; Gang Ma; Di Xian (Advances in Atmospheric Sciences, 2019)

Regulation of mitochondrial NAD pool via NAD+ transporter 2 is essential for matrix NADH homeostasis and ROS production in Arabidopsis - Lilan Luo; Yajun He; Yannan Zhao; Qian Xu; Jian Wu; Haiyan Ma; Hongyan Guo; Lin Bai; Jianru Zuo; Jian-Min Zhou; Hong Yu; Jiayang Li (Science China Life Sciences, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Development and validation of nomogram estimating post-surgery hospital stay of lung cancer patients: relevance for predictive, preventive, and personalized healthcare strategies - Xiang-Lin Hu; Song-Tao Xu; Xiao-Cen Wang; Jin-Long Luo; Dong-Ni Hou; Xiao-Min Zhang; Chen Bao; Dong Yang; Yuan-Lin Song; Chun-Xue Bai (EPMA Journal, 2019)

Prediction of Self-Propulsion Performance of Ship Model with Double L-Type Podded Propulsors and Conversion Method for Full-Scale Ship - Dagang Zhao; Chunyu Guo; Jianfeng Lin; Zuotian Zhang; Xue Bai (Journal of Marine Science and Engineering, 2019)
In this study, the self-propulsion performance of a ship model with double-L-type podded propulsors was predicted. Additionally, a conversion method for the performance of a full-scale ship was established based on the correction method published by the International Towing Tank Conference (ITTC) for the scaling effect of a single podded propeller and research reports on pod tests conducted by different ship research institutes. The thrust deduction and wake fraction of the ship were also analyzed. Furthermore, the self-propulsion performance of a full-scale ship with double L-type pods was determined, the full- and model-scale ships compared in terms of their flow fields and pressure charts, and the influence of the scaling effect analyzed. In addition, the calculation results were compared with the conversion results of a full-scale ship, and the reliability of the method adopted for the performance estimation of a full-scale ship with double podded propulsors was verified. The findings reported herein can provide statistics and technical support for the design of L-type podded propulsors and their application in full-scale ships, which are of theoretical significance and practical value in the engineering domain.

Winter chemical partitioning of metals bound to atmospheric fine particles in Dongguan, China, and its health risk assessment - Lin Huang; Yun-He Bai; Rui-Yue Ma; Ze-Ming Zhuo; Ling Chen (Environmental Science and Pollution Research, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Constructing a High-Density Genetic Linkage Map for Large Yellow Croaker (Larimichthys crocea) and Mapping Resistance Trait Against Ciliate Parasite Cryptocaryon irritans - Shengnan Kong; Qiaozhen Ke; Lin Chen; Zhixiong Zhou; Fei Pu; Ji Zhao; Huaqiang Bai; Wenzhu Peng; Peng Xu (Marine Biotechnology, 2019)

Genome-wide analysis identified 17 new loci influencing intraocular pressure in Chinese population - Lulin Huang; Yuhong Chen; Ying Lin; Pancy O. S. Tam; Yilian Cheng; Yi Shi; Bo Gong; Fang Lu; Jialiang Yang; Haixin Wang; Yi Yin; Yong Cao; et al. (Science China Life Sciences, 2019)

Polymorphism of duck MHC class molecules - Lin Zhang; Dongmei Lin; Sen Yu; Junping Bai; Wanchun Jiang; Wenzheng Su; Yanyan Huang; Shaohua Yang; Jiaqiang Wu (Immunogenetics, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Study on the bio-function of lipA gene in Aspergillus flavus - Wenzhao Bai; Tiejun Feng; Faxiu Lan; Guanglan Lin; Yu Li; Opemipo Esther Fasoyin; Yaju Liu; Kunzhi Jia (Genes & Genomics, 2019)

A large meta-analysis of the global prevalence rates of S. aureus and MRSA contamination of milk - Qianting Ou; Junli Zhou; Dongxin Lin; Chan Bai; Ting Zhang; Jialing Lin; Haoqu Zheng; Xiaojie Wang; Jiaping Ye; Xiaohua Ye; Zhenjiang Yao (Critical Reviews in Food Science and Nutrition, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

QTL mapping of pre-harvest sprouting resistance in a white wheat cultivar Danby - Mingqin Shao; Guihua Bai; Trevor W. Rife; Jesse Poland; Meng Lin; Shubing Liu; Hui Chen; Tadele Kumssa; Allan Fritz; Harold Trick; Yan Li; Guorong Zhang (Theoretical and Applied Genetics, 2018)

Effects of Litter Inputs on N2O Emissions from a Tropical Rainforest in Southwest China - Jinbo Gao; Wenjun Zhou; Yuntong Liu; Jing Zhu; Liqing Sha; Qinhai Song; Hongli Ji; Youxing Lin; Xuehai Fei; Xiaolong Bai; Xiang Zhang; Yun Deng; et al. (Ecosystems, 2018)

Response of the wheat rhizosphere soil nematode community in wheat/walnut intercropping system in Xinjiang, Northwest China - Peng-hua Bai; Qi-Zhi Liu; Xing-yue Li; Yan-bin Liu; Lin-lin Zhang (Applied Entomology and Zoology, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

The dynamic observation of dissolved organic matter in the Zhujiang (Pearl River) Estuary in China from space - Dong Liu; Yan Bai; Xianqiang He; Delu Pan; Difeng Wang; Ji’an Wei; Lin Zhang (Acta Oceanologica Sinica, 2018)

Evolutionary, interaction and expression analysis of floral meristem identity genes in inflorescence induction of the second crop in two-crop-a-year grape culture system - Rongrong Guo; Bo Wang; Ling Lin; Guo Cheng; Sihong Zhou; Shuyu Xie; Xiaofang Shi; Muming Cao; Ying Zhang; Xianjin Bai (Journal of Genetics, 2018)

Spatiotemporal Dynamics of Coastal Wetlands and Reclamation in the Yangtze Estuary During Past 50 Years (1960s–2015) - Lin Chen; Chunying Ren; Bai Zhang; Lin Li; Zongming Wang; Kaishan Song (Chinese Geographical Science, 2018)

Remote Monitoring of Expansion of Aquaculture Ponds Along Coastal Region of the Yellow River Delta from 1983 to 2015 - Chunying Ren; Zongming Wang; Bai Zhang; Lin Li; Lin Chen; Kaishan Song; Mingming Jia (Chinese Geographical Science, 2018)

A Quninolylthiazole Derivatives as an ICT-Based Fluorescent Probe of Hg(II) and its Application in Ratiometric Imaging in Live HeLa Cells - Jian-Ying Bai; Yu-Zhong Xie; Chang-Jiang Wang; Shu-Qing Fang; Lin-Nan Cao; Ling-Li Wang; Jing-Yi Jin (Journal of Fluorescence, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

Resisting impact mechanical analysis of an anchored roadway supporting structure under P-wave loading and its application in rock burst prevention - Zheng-yi Wang; Lin-ming Dou; Gui-feng Wang; Long-fei Feng; Kai Kang; Jin-zheng Bai; Sheng-chuan Wang (Arabian Journal of Geosciences, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Population health risk via dietary exposure to trace elements (Cu, Zn, Pb, Cd, Hg, and As) in Qiqihar, Northeastern China - Jinming Luo; Jia Meng; Yajie Ye; Yongjie Wang; Lin Bai (Environmental Geochemistry and Health, 2018)

Climatology of cloud-base height from long-term radiosonde measurements in China - Yong Zhang; Lejian Zhang; Jianping Guo; Jinming Feng; Lijuan Cao; Yang Wang; Qing Zhou; Liangxu Li; Bai Li; Hui Xu; Lin Liu; Ning An; et al. (Advances in Atmospheric Sciences, 2018)

A new ent -kaurane diterpene derivative from the stems of Eurya chinensis R.Br - Jia-Ling Song; Yao Yuan; Ling-Hui Nie; Bai-Lin Li; Xu-Bing Qin; Yan Li; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2018)

The persistent prevalence and evolution of cross-family recombinant coronavirus GCCDC1 among a bat population: a two-year follow-up - Joseph O. Obameso; Hong Li; Hao Jia; Min Han; Shiyan Zhu; Canping Huang; Yuhui Zhao; Min Zhao; Yu Bai; Fei Yuan; Honglan Zhao; Xia Peng; et al. (Science China Life Sciences, 2017)

Spatiotemporal expression of proprotein convertase subtilisin/kexin type 5 in the development of anorectal malformations in fetal rats - Xiao Bing Tang; Li Chen; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Journal of Molecular Histology, 2017)

Productive functional evolution of rural settlements: analysis of livelihood strategy and land use transition in eastern China - Bai-lin Zhang; Guang-hui Jiang; Wei-min Cai; Pi-ling Sun; Feng-rong Zhang (Journal of Mountain Science, 2017)

Determining the trophic linkage of the red-crowned crane Grus japonensis in Zhalong wetland in northeastern China - Jinming Luo; Jia Li; Xiaohua Li; Lin Bai; Yongjie Wang; Dongmei Zheng (Biologia, 2017)

Yangonindimers A-C, three new kavalactone dimers from Piper methysticum (kava) - Jia-Ling Song; Bai-Lin Li; Yao Yuan; Ling-Hui Nie; Jia Niu; David Chiu; Zhi-Fang Xu; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2017)

A comparative analysis of two-dimensional multi-valued ray tracing techniques - Bin Li; Chao-ying Bai; Qing-lin Wang; Stewart Greenhalgh (Arabian Journal of Geosciences, 2017)

Quantitative estimation and spatial reconstruction of urban and rural construction land in Jiangsu Province, 1820–1985 - Jinyuan Xie; Xiaobin Jin; Yinan Lin; Yinong Cheng; Xuhong Yang; Qing Bai; Yinkang Zhou (Journal of Geographical Sciences, 2017)

Effects of temperature, salinity, diet and stocking density on development of the veined Rapa whelk, Rapana venosa (Valenciennes, 1846) larvae - Tao Zhang; Hao Song; Yu-Cen Bai; Jing-Chun Sun; Xiao-Fang Zhang; Shao-Jun Ban; Zheng-Lin Yu; Mei-Jie Yang; Hai-Yan Wang (Aquaculture International, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

The monitoring and analysis of the coastal lowland subsidence in the southern Hangzhou Bay with an advanced time-series InSAR method - Peng Han; Xiaoxia Yang; Lin Bai; Qishi Sun (Acta Oceanologica Sinica, 2017)

Modeling farm nutrient flows in the North China Plain to reduce nutrient losses - Zhanqing Zhao; Zhaohai Bai; Sha Wei; Wenqi Ma; Mengru Wang; Carolien Kroeze; Lin Ma (Nutrient Cycling in Agroecosystems, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Seasonal association between ambient ozone and mortality in Zhengzhou, China - Lijie Qin; Jianqin Gu; Shijie Liang; Fang Fang; Weimin Bai; Xu Liu; Tao Zhao; Joseph Walline; Shenglong Zhang; Yingjie Cui; Yaxin Xu; Hualiang Lin (International Journal of Biometeorology, 2017)

An irregular triangle mesh buffer analysis method for boundary representation geological object in three-dimension - Nan Li; Leon Bagas; Mark Lindsay; Daniel Wedge; Lin Bai; Xianglong Song (Earth Science Informatics, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

NMR-based metabolomics reveals brain region-specific metabolic alterations in streptozotocin-induced diabetic rats with cognitive dysfunction - Hong Zheng; Qiuting Lin; Dan Wang; Pengtao Xu; Liangcai Zhao; Wenyi Hu; Guanghui Bai; Zhihan Yan; Hongchang Gao (Metabolic Brain Disease, 2017)

Disrupted brain connectivity networks in acute ischemic stroke patients - Yifei Zhu; Lin Bai; Panpan Liang; Shan Kang; Hengbo Gao; Haiqing Yang (Brain Imaging and Behavior, 2017)

Association analysis between HFM1 variations and idiopathic azoospermia or severe oligozoospermia in Chinese Men - Wenxiang Zhang; Xiaomin Song; Feng Ni; Jinbao Cheng; Bai-Lin Wu; Hong Jiang (Science China Life Sciences, 2017)

Increased inter-hemispheric resting-state functional connectivity in acute lacunar stroke patients with aphasia - Haiqing Yang; Lin Bai; Yi Zhou; Shan Kang; Panpan Liang; Lihua Wang; Yifei Zhu (Experimental Brain Research, 2017)

Rapid determination of gizzerosine in fish meals using microchip capillary electrophoresis with laser-induced fluorescence detection - Meng-Wei Xiao; Xiao-Lin Bai; Pei-Li Xu; Yan Zhao; Li Yang; Yi-Ming Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

Assessment of the MCC method to estimate sea surface currents in highly turbid coastal waters from GOCI - Zifeng Hu; Delu Pan; Xianqiang He; Dehai Song; Ningli Huang; Yan Bai; Yi Xu; Xiaohua Wang; Lin Zhang; Fang Gong (International Journal of Remote Sensing, 2017)

Naringenin ameliorates hypoxia/reoxygenation-induced endoplasmic reticulum stress-mediated apoptosis in H9c2 myocardial cells: involvement in ATF6, IRE1α and PERK signaling activation - Jia-You Tang; Ping Jin; Qing He; Lin-He Lu; Ji-Peng Ma; Wei-Lun Gao; He-Ping Bai; Jian Yang (Molecular and Cellular Biochemistry, 2017)

Equisetum cf. oppositum (Equisetaceae) from the Paleocene-Eocene of Tibet in southwestern China and its paleoenvironmental implications - Guo-Lin Yang; Zi-Xi Wang; Jing-Wei Chen; De-Fei Yan; Bai-Nian Sun (Arabian Journal of Geosciences, 2016)

Local-scale determinants of elemental stoichiometry of soil in an old-growth temperate forest - Yanyan Suo; Zuoqiang Yuan; Fei Lin; Xugao Wang; Ji Ye; Edith Bai; Zhanqing Hao (Plant and Soil, 2016)

Deep-sequencing transcriptome analysis of field-grown Medicago sativa L. crown buds acclimated to freezing stress - Lili Song; Lin Jiang; Yue Chen; Yongjun Shu; Yan Bai; Changhong Guo (Functional & Integrative Genomics, 2016)

Genomewide association analysis for awn length linked to the seed shattering gene qSH1 in rice - RISPER AUMA MAGWA; HU ZHAO; WEN YAO; WEIBO XIE; LIN YANG; YONGZHONG XING; XUFENG BAI (Journal of Genetics, 2016)

Extracellular Cl− regulates human SO4 2−/anion exchanger SLC26A1 by altering pH sensitivity of anion transport - Meng Wu; John F. Heneghan; David H. Vandorpe; Laura I. Escobar; Bai-Lin Wu; Seth L. Alper (Pflügers Archiv - European Journal of Physiology, 2016)

Adaptability comparison of E. fetida in vermicomposting against sludge from livestock wastewater treatment plant based on their several growth stages - Xiaoxia Hao; Hongwen Hu; Xuewei Li; Dongmei Jiang; Li Zhu; Lin Bai (Environmental Science and Pollution Research, 2016)

Comparison of ultrastructural and physiological changes of potato (Solanum tuberosum L.) plantlets subjected to salt and modeling drought stresses - Jiang-Ping Bai; Hui-Juan Gao; Hong-Yu Yang; Yan Lou; Jun-Lian Zhang; Di Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Occurrence, spatial distribution, sources, and risks of polychlorinated biphenyls and heavy metals in surface sediments from a large eutrophic Chinese lake (Lake Chaohu) - Wei He; Ze-Lin Bai; Wen-Xiu Liu; Xiang-Zhen Kong; Bin Yang; Chen Yang; Sven Erik Jørgensen; Fu-Liu Xu (Environmental Science and Pollution Research, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Changes in phosphorus use and losses in the food chain of China during 1950–2010 and forecasts for 2030 - Zhaohai Bai; Lin Ma; Wenqi Ma; Wei Qin; Gerard L. Velthof; Oene Oenema; Fusuo Zhang (Nutrient Cycling in Agroecosystems, 2016)

Vermicomposting of sludge from animal wastewater treatment plant mixed with cow dung or swine manure using Eisenia fetida - Dan Xie; Weibing Wu; Xiaoxia Hao; Dongmei Jiang; Xuewei Li; Lin Bai (Environmental Science and Pollution Research, 2016)

Arbuscular Mycorrhizal Fungus Alleviates Chilling Stress by Boosting Redox Poise and Antioxidant Potential of Tomato Seedlings - Airong Liu; Shuangchen Chen; Mengmeng Wang; Dilin Liu; Rui Chang; Zhonghong Wang; Xiaomin Lin; Bing Bai; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2016)

Identification and molecular mapping of Rps11, a novel gene conferring resistance to Phytophthora sojae in soybean - Jieqing Ping; Joshua C. Fitzgerald; Chunbao Zhang; Feng Lin; Yonghe Bai; Dechun Wang; Rajat Aggarwal; Maqsood Rehman; Oswald Crasta; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Observation of the supercritical Pearl River plume front under the downwelling-favorable winds - Peng Bai; YanZhen Gu; Lin Luo; WanLei Zhang; KaiGuo Fan (Science China Earth Sciences, 2015)

Genetic architecture, epigenetic influence and environment exposure in the pathogenesis of Autism - Li Yu; YiMing Wu; Bai-Lin Wu (Science China Life Sciences, 2015)

Parenting stress and affective symptoms in parents of autistic children - Yun Gong; YaSong Du; HuiLin Li; XiYan Zhang; Yu An; Bai-Lin Wu (Science China Life Sciences, 2015)

Mobilization of Diverse Transposable Elements in Rice Induced by Alien Pollination Without Entailing Genetic Introgression - Ying Wu; Tingting Jiang; Yue Sun; Zeyang Wang; Guizhen Guo; Shuai Sun; Jie Wang; Ning Li; Zhenhui Wang; Di Zhang; Yan Bai; Yang Gao; et al. (Plant Molecular Biology Reporter, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

Health risk assessment of toxic VOCs species for the coal fire well drillers - Yulong Yan; Lin Peng; Na Cheng; Huiling Bai; Ling Mu (Environmental Science and Pollution Research, 2015)

Characteristics of hopanoid hydrocarbons in ambient PM10 and motor vehicle emissions and coal ash in Taiyuan, China - Feng Han; Junji Cao; Lin Peng; Huiling Bai; Dongmei Hu; Ling Mu; Xiaofeng Liu (Environmental Geochemistry and Health, 2015)

DNA Interaction, Photocleavage and Topoisomerase I Inhibition by Ru(II) Complex with a New Ligand Possessing Phenazine Unit - Xue-Wen Liu; You-Ming Shen; Jun-Shi Shu; Yang Xiao; Song-Bai Zhang; Ji-Lin Lu (Journal of Fluorescence, 2015)

Crack propagation patterns and energy evolution rules of coal within slotting disturbed zone under various lateral pressure coefficients - Lin Bai-quan; Liu Ting; Zou Quan-le; Zhu Chuan-jie; Yan Fa-zhi; Zhang Zhen (Arabian Journal of Geosciences, 2015)

Improving arsenic mobility concentration from As-polluted soils by the functional strains - JianFeng Bai; XianGui Lin; Jue Dai; JianFeng Hua; Hua Qin; JunLi Hu; YiMing Wang; ChengLong Zhang; JingWei Wang; WenYi Yuan (Science China Earth Sciences, 2015)

Contamination of sulfonamide antibiotics and sulfamethazine-resistant bacteria in the downstream and estuarine areas of Jiulong River in Southeast China - Danyun Ou; Bin Chen; Renao Bai; Puqing Song; Heshan Lin (Environmental Science and Pollution Research, 2015)

Genotyping-by-sequencing (GBS) identified SNP tightly linked to QTL for pre-harvest sprouting resistance - Meng Lin; Shibin Cai; Shan Wang; Shubing Liu; Guorong Zhang; Guihua Bai (Theoretical and Applied Genetics, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Effect of igneous intrusions and normal faults on coalbed methane storage and migration in coal seams near the outcrop - Chuan-jie Zhu; Bai-quan Lin (Natural Hazards, 2015)

No tillage enhances arbuscular mycorrhizal fungal population, glomalin-related soil protein content, and organic carbon accumulation in soil macroaggregates - Jue Dai; Junli Hu; Anning Zhu; Jianfeng Bai; Junhua Wang; Xiangui Lin (Journal of Soils and Sediments, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Marinobacter shengliensis sp. nov., a moderately halophilic bacterium isolated from oil-contaminated saline soil - Yi-Jing Luo; Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Ya-Nan Wang; Heng-Lin Cui; Hua Cai; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

A record-breaking low ice cover over the Great Lakes during winter 2011/2012: combined effects of a strong positive NAO and La Niña - Xuezhi Bai; Jia Wang; Jay Austin; David J. Schwab; Raymond Assel; Anne Clites; John F. Bratton; Marie Colton; John Lenters; Brent Lofgren; Trudy Wohlleben; Sean Helfrich; et al. (Climate Dynamics, 2015)

Single nucleotide polymorphisms in PDCD6 gene are associated with the development of cervical squamous cell carcinoma - Bin Zhou; Peng Bai; Hui Xue; Zhu Zhang; Shaoqing Shi; Kui Zhang; Yanyun Wang; Kana Wang; Yi Quan; Yaping Song; Lin Zhang (Familial Cancer, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Effects of Traditional Chinese Medicine Fu Zheng Decoction on the Immunological Function and Clinical Prognosis of the Elderly Patients with Pneumonia - Hongqiang Li; Shumin Xu; Tingting Cheng; Lunxian Tang; Jianwen Bai; Minjia Lin (Cell Biochemistry and Biophysics, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

IL-17A Induces MIP-1α Expression in Primary Astrocytes via Src/MAPK/PI3K/NF-kB Pathways: Implications for Multiple Sclerosis - Hongwei Yi; Ying Bai; Xinjian Zhu; Lin lin; Lei Zhao; Xiaodong Wu; Shilpa Buch; Longxin Wang; Jie Chao; Honghong Yao (Journal of Neuroimmune Pharmacology, 2014)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Predisposition to Behçet’s disease and VKH syndrome by genetic variants of miR-182 - Hongsong Yu; Yunjia Liu; Lin Bai; Aize Kijlstra; Peizeng Yang (Journal of Molecular Medicine, 2014)

The contribution of understory light availability and biotic neighborhood to seedling survival in secondary versus old-growth temperate forest - Fei Lin; Liza S. Comita; Xugao Wang; Xuejiao Bai; Zuoqiang Yuan; Dingliang Xing; Zhanqing Hao (Plant Ecology, 2014)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)

Overexpression of Glycine soja WRKY20 enhances both drought and salt tolerance in transgenic alfalfa (Medicago sativa L.) - Lili Tang; Hua Cai; Hong Zhai; Xiao Luo; Zhenyu Wang; Lin Cui; Xi Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Temporal and spatial expression of caudal-type homeobox gene-2 during hindgut development in rat embryos with ethylenethiourea-induced anorectal malformations - Xiao Bing Tang; Tao Zhang; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Cell and Tissue Research, 2014)

Gas outburst affected by original rock stress direction - Wei Yang; Bai-quan Lin; Jiang-tao Xu (Natural Hazards, 2014)

Occurrence and particle-size distributions of polycyclic aromatic hydrocarbons in the ambient air of coking plant - Xiaofeng Liu; Lin Peng; Huiling Bai; Ling Mu; Chongfang Song (Environmental Geochemistry and Health, 2014)

Akt and Erk1/2 activate the ornithine decarboxylase/polyamine system in cardioprotective ischemic preconditioning in rats: the role of mitochondrial permeability transition pores - Hao Zhang; Guo Xue; Weihua Zhang; Lina Wang; Hong Li; Li Zhang; Fanghao Lu; Shuzhi Bai; Yan Lin; Yu Lou; Changqing Xu; Yajun Zhao (Molecular and Cellular Biochemistry, 2014)

The Optimal Velocity Criterion in the Diagnosis of Unilateral Middle Cerebral Artery Stenosis by Transcranial Doppler - Jiafeng Chen; Lin Wang; Jing Bai; Zhijun Lun; Jinqiao Zhang; Yingqi Xing (Cell Biochemistry and Biophysics, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Molecular characterisation and expression profiling of the ENO1 gene in the ovarian follicle of the Sichuan white goose - Bo Kang; Dong Mei Jiang; Lin Bai; Hui He; Rong Ma (Molecular Biology Reports, 2014)

Inactivation kinetics of formaldehyde on N-acetyl-β-d-glucosaminidase from Nile tilapia (Oreochromis niloticus) - Wei-Ni Zhang; Ding-Ping Bai; Xin-Yu Lin; Qing-Xi Chen; Xiao-Hong Huang; Yi-Fan Huang (Fish Physiology and Biochemistry, 2014)

Aqueous stabilization of carbon nanotubes: effects of surface oxidization and solution chemistry - Yingchen Bai; Fengchang Wu; Daohui Lin; Baoshan Xing (Environmental Science and Pollution Research, 2014)

Rhodamine B induces long nucleoplasmic bridges and other nuclear anomalies in Allium cepa root tip cells - Dehong Tan; Bing Bai; Donghua Jiang; Lin Shi; Shunchang Cheng; Dongbing Tao; Shujuan Ji (Environmental Science and Pollution Research, 2014)

Two new dammarane-type glycosides from Phlomis umbrosa - Ming-Ming Ding; Fu-Lin Yan; Jing Tan; Yi-Xiao Bai; Xiang Wang; Yan-Xia Yang (Natural Product Research, 2014)

Quantitative and qualitative characteristics of dissolved organic matter from eight dominant aquatic macrophytes in Lake Dianchi, China - Xiaoxia Qu; Li Xie; Ying Lin; Yingchen Bai; Yuanrong Zhu; Fazhi Xie; John P. Giesy; Fengchang Wu (Environmental Science and Pollution Research, 2013)

Isolation and identification of a new ent -kaurane diterpenoid from the leaves of Isodon japonica - Wei Liu; Bing-Lin Fan; Hong-Yun Guo; Yong-Liang Yuan; Hui-Juan Liang; Su-Ping Bai (Natural Product Research, 2013)

Halomonas socia sp. nov., isolated from high salt culture of Dunaliella salina - Jiao Cao; Huai-Yuan Ma; Hai-Yu Li; Kui-Rong Wang; Kun Ruan; Lin-Han Bai (Extremophiles, 2013)

Overexpression of the Arabidopsis photorespiratory pathway gene, serine: glyoxylate aminotransferase (AtAGT1), leads to salt stress tolerance in transgenic duckweed (Lemna minor) - Lin Yang; Huajun Han; Miaomiao Liu; Zhaojiang Zuo; Kaiqiang Zhou; Jianchao Lü; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Effects of rainfall amount and frequency on vegetation growth in a Tibetan alpine meadow - Baocheng Zhang; Junji Cao; Yanfen Bai; Xuhui Zhou; Zhigang Ning; Songjie Yang; Lin Hu (Climatic Change, 2013)

Genetic diversity of Bartonella quintana in macaques suggests zoonotic origin of trench fever - Hao Li; Jie‐Ying Bai; Li‐Yuan Wang; Lin Zeng; Yan‐Sheng Shi; Zheng‐Liang Qiu; Hua‐Hu Ye; Xiao‐Fei Zhang; Qing‐Bin Lu; Michael Kosoy; Wei Liu; Wu‐Chun Cao (Molecular Ecology, 2013)
Bartonella quintana is a bacterium that causes a broad spectrum of diseases in humans including trench fever. Humans were previously considered to be the primary, if not the only, reservoir hosts for B. quintana . To identify the animal reservoir and extend our understanding of the ecological and evolutionary history of B. quintana , we examined blood samples from macaques and performed multilocus sequence typing ( MLST ) analysis. We demonstrated the prevalence of B. quintana infection was common in macaques from main primate centres in mainland C hina. Overall, 18.0% (59/328) of rhesus macaques and 12.7% (39/308) of cynomolgus macaques were found to be infected with B. quintana by blood culture and/or polymerase chain reaction. The infection was more frequently identified in juvenile and young monkeys compared with adult animals. In contrast with the relatively low level of sequence divergence of B. quintana reported in humans, our investigation revealed much higher genetic diversity in nonhuman primates. We identified 44 new nucleotide variable sites and 14 novel sequence types (STs) among the B. quintana isolates by MLST analysis. Some STs were found only in cynomolgus macaques, while some others were detected only in rhesus macaques, suggesting evidence of host‐cospeciation, which were further confirmed by phylogenetic analysis and Splits decomposition analysis. Our findings suggest that trench fever may primarily be a zoonotic disease with macaques as the natural hosts.

Chemical Composition and Sensory Evaluation of Fermented Tea with Medicinal Mushrooms - Wei-Fang Bai; Xin-Yue Guo; Li-Qing Ma; Li-Qiong Guo; Jun-Fang Lin (Indian Journal of Microbiology, 2013)

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

The satellite reversion of dissolved organic carbon (DOC) based on the analysis of the mixing behavior of DOC and colored dissolved organic matter: the East China Sea as an example - Qiong Liu; Delu Pan; Yan Bai; Kai Wu; Chen-Tung Arthur Chen; Jun Sun; Lin Zhang (Acta Oceanologica Sinica, 2013)

Expression of MMP-9 in hepatic sinusoidal obstruction syndrome induced by Gynura segetum - Xia-zhen Yu; Tao Ji; Xue-li Bai; Liang Liang; Lin-yan Wang; Wei Chen; Ting-bo Liang (Journal of Zhejiang University-SCIENCE B, 2013)

Alteration of discoidin domain receptor-2 expression: possible role in peroxynitrite-induced apoptosis in human cerebral vascular smooth muscle cells - Lin Li; Zhiyong Yue; Xiaojuan Wan; Guodong Zhang; Shasha Song; Xiaohui Bai; Yulian Jiao; Yuanrong Ju; Jianfeng Li (Molecular & Cellular Toxicology, 2012)

Effects of local biotic neighbors and habitat heterogeneity on tree and shrub seedling survival in an old-growth temperate forest - Xuejiao Bai; Simon A. Queenborough; Xugao Wang; Jian Zhang; Buhang Li; Zuoqiang Yuan; Dingliang Xing; Fei Lin; Ji Ye; Zhanqing Hao (Oecologia, 2012)

Molecular diversity, genomic constitution, and QTL mapping of fiber quality by mapped SSRs in introgression lines derived from Gossypium hirsutum × G. darwinii Watt - Bin Wang; Yichun Nie; Zhongxu Lin; Xianlong Zhang; Junjie Liu; Jing Bai (Theoretical and Applied Genetics, 2012)

SNP identification and allelic-specific PCR markers development for TaGW2, a gene linked to wheat kernel weight - Zibo Yang; Zhiyuan Bai; Xiaolin Li; Pei Wang; Qingxia Wu; Lin Yang; Liqun Li; Xuejun Li (Theoretical and Applied Genetics, 2012)

Efficacy of a Therapeutic Vaccine Using Mutated β-amyloid Sensitized Dendritic Cells in Alzheimer’s Mice - Zhongqiu Luo; Jialin Li; Neel R. Nabar; Xiaoyang Lin; Ge Bai; Jianfeng Cai; Shu-Feng Zhou; Chuanhai Cao; Jinhuan Wang (Journal of Neuroimmune Pharmacology, 2012)

Urban Phosphorus Metabolism through Food Consumption - Gui‐Lin Li; Xuemei Bai; Shen Yu; Hua Zhang; Yong‐Guan Zhu (Journal of Industrial Ecology, 2012)
Summary Urbanization has significant impacts on local, regional, and global biogeochemical cycles, including through nutrient enrichment by food consumption, and especially in rapidly urbanizing countries. This article presents a time‐series estimation of phosphorus (P) metabolism through food consumption in Chinese cities and examines its relationship to income level during the period 1985–2006. Our results show that approximately 39% of the total dietary P inflow is exported through direct sewage discharge without treatment, 35% is exported via the output of solid human excreta, 7% is exported through sewage sludge landfill, and 19% is left within urban areas. The total inflow of dietary P to urban systems increases with per capita disposable income level. Furthermore, the ratio of dietary P remaining in urban systems to total dietary P inflow, the dietary P remaining in urban systems per capita, and the dietary P remaining per unit urban built‐up area respond in an inverted U shape to increases in per capita disposable income; the per capita outflow of dietary P shows a U‐shaped response. These relationships may indicate that the impact of urban dietary P on urban environmental systems follows the traditional environmental Kuznets curve, while the environmental impact of urban dietary P on surrounding nonurban ecosystems initially decreases but then increases with the rising income of urban residents.

Cryotherapy is Associated with Improved Clinical Outcomes of Sorafenib Therapy for Advanced Hepatocellular Carcinoma - Yongping Yang; Yinying Lu; Chunping Wang; Wenlin Bai; Jianhui Qu; Yan Chen; Xiujuan Chang; Linjing An; Lin Zhou; Zhen Zeng; Min Lou; Jiyun Lv (Cell Biochemistry and Biophysics, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

NAD(P)H oxidase inhibiting with apocynin improved vascular reactivity in tail-suspended hindlimb unweighting rat - Ran Zhang; Hai-hong Ran; Jin Ma; Yun-gang Bai; Le-jian Lin (Journal of Physiology and Biochemistry, 2012)

Retrieval of total suspended matter (TSM) and chlorophyll-a (Chl-a) concentration from remote-sensing data for drinking water resources - Kaishan Song; Lin Li; Zongming Wang; Dianwei Liu; Bai Zhang; Jingping Xu; Jia Du; Linhai Li; Shuai Li; Yuandong Wang (Environmental Monitoring and Assessment, 2012)

The proportions and variations of the light absorption coefficients of major ocean color components in the East China Sea - Hui Lei; Delu Pan; Yan Bai; Bangyi Tao; Jun Sun; Lin Zhang; Xuan Zhang (Acta Oceanologica Sinica, 2012)

Genetic diversity of ‘Cadidatus Liberibacter solanacearum’ strains in the United States and Mexico revealed by simple sequence repeat markers - Hong Lin; Md Sajedul Islam; Yang Bai; Amin Wen; Suque Lan; Neil C. Gudmestad; Edwin L. Civerolo (European Journal of Plant Pathology, 2012)

Soluble expression and purification of Brucella cell surface protein (BCSP31) of Brucella melitensis and preparation of anti-BCSP31 monoclonal antibodies - Lei Zhang; Xing An Wu; Fang Lin Zhang; Cui Hong An; Yang Xin Sun; Wen Tao Bai; Zhi Kai Xu (Molecular Biology Reports, 2012)

Chronic zebrafish low dose decabrominated diphenyl ether (BDE-209) exposure affected parental gonad development and locomotion in F1 offspring - Jianhui He; Dongren Yang; Chunyan Wang; Wei Liu; Junhua Liao; Tao Xu; Chenglian Bai; Jiangfei Chen; Kuanfei Lin; Changjiang Huang; Qiaoxiang Dong (Ecotoxicology, 2011)

New epothilone congeners from Sorangium cellulosum strain So0157-2 - Ji-Dong Wang; Nan Jiang; Hui Zhang; Lin-Ping Ying; Chuan-Xi Wang; Wen-Sheng Xiang; Bo Wu; Hai-Bin Wang; Hua Bai (Natural Product Research, 2011)

Genetic diversity and positive selection analysis of classical swine fever virus isolates in south China - Haiyan Shen; Jingjing Pei; Jialin Bai; Mingqiu Zhao; Chunmei Ju; Lin Yi; Yanmei Kang; Xuetao Zhang; Lijun Chen; Yinguang Li; Jiaying Wang; Jinding Chen (Virus Genes, 2011)

Immobilization of silver in polypropylene membrane for anti-biofouling performance - Xiaoying Zhu; Lin Tang; Kin-Ho Wee; Yong-Hong Zhao; Renbi Bai (Biofouling, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Grassland responses to grazing: effects of grazing intensity and management system in an Inner Mongolian steppe ecosystem - Philipp Schönbach; Hongwei Wan; Martin Gierus; Yongfei Bai; Katrin Müller; Lijun Lin; Andreas Susenbeth; Friedhelm Taube (Plant and Soil, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

Production of ectoine through a combined process that uses both growing and resting cells of Halomonas salina DSM 5928T - Ya-jun Lang; Lin Bai; Ya-nan Ren; Ling-hua Zhang; Shinichi Nagata (Extremophiles, 2011)

Paraquat pre-treatment increases activities of antioxidant enzymes and reduces lipid peroxidation in salt-stressed cucumber leaves - Shao-Hang Lin; Zhong-Jing Liu; Pei-Lei Xu; Ye-Ying Fang; Ji-Gang Bai (Acta Physiologiae Plantarum, 2011)

Enhanced drought and salinity tolerance in transgenic potato plants with a BADH gene from spinach - Ning Zhang; Huai-Jun Si; Gang Wen; Hong-Hui Du; Bai-Lin Liu; Di Wang (Plant Biotechnology Reports, 2011)

Blocking NF-κB and Akt by Hsp90 inhibition sensitizes Smac mimetic compound 3-induced extrinsic apoptosis pathway and results in synergistic cancer cell death - Lang Bai; Shanling Xu; Wenshu Chen; Zi Li; Xia Wang; Hong Tang; Yong Lin (Apoptosis, 2011)

VKORC1-1639G>A, CYP2C9, EPHX1691A>G genotype, body weight, and age are important predictors for warfarin maintenance doses in patients with mechanical heart valve prostheses in southwest China - Qiang Gu; Yan Kong; Jörn Schneede; Ying-Bin Xiao; Lin Chen; Qian-Jin Zhong; Xue-Feng Wang; Jia Hao; Bai-Cheng Chen; Jing-Jin Chen (European Journal of Clinical Pharmacology, 2010)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

An alkali-tolerant xylanase produced by the newly isolated alkaliphilic Bacillus pumilus from paper mill effluent - Jing Wang; Wei-wei Zhang; Jin-ni Liu; Yao-ling Cao; Xiao-ting Bai; Yue-sheng Gong; Pei-lin Cen; Ming-ming Yang (Molecular Biology Reports, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Phototropic leaf movements and photosynthetic performance in an amphibious fern, Marsilea quadrifolia - Wen-Yuan Kao; Bai-Ling Lin (Journal of Plant Research, 2010)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

A new antitumour ansamitocin from Actinosynnema pretiosum - Guo-Zhu Wei; Lin-Quan Bai; Tao Yang; Juan Ma; Ying Zeng; Yue-Mao Shen; Pei-Ji Zhao (Natural Product Research, 2010)

Life cycle assessment of switchgrass-derived ethanol as transport fuel - Yu Bai; Lin Luo; Ester van der Voet (The International Journal of Life Cycle Assessment, 2010)

Electroporation is a feasible method to introduce circularized or linearized DNA into B. subtilis chromosome - Ming-Ming Yang; Wei-Wei Zhang; Xiao-Ting Bai; Heng-Xin Li; Pei-Lin Cen (Molecular Biology Reports, 2010)

Effects of CYP2C19 and CYP2C9 genotypes on pharmacokinetic variability of valproic acid in Chinese epileptic patients: nonlinear mixed-effect modeling - Dechun Jiang; Xiangrong Bai; Qingxia Zhang; Wei Lu; Yuqin Wang; Lin Li; Markus Müller (European Journal of Clinical Pharmacology, 2009)

Prognostic factors and recurrence of hepatitis B-related hepatocellular carcinoma after argon-helium cryoablation: a prospective study - Chunping Wang; Yinying Lu; Yan Chen; Yongyi Feng; Linjing An; Xinzhen Wang; Shuhui Su; Wenlin Bai; Lin Zhou; Yongping Yang; Dongping Xu (Clinical & Experimental Metastasis, 2009)

Establishment and characterization of a fibroblast cell line from the Mongolian horse - Lin-feng Li; Wei-jun Guan; Yue Hua; Xiu-juan Bai; Yue-hui Ma (In Vitro Cellular & Developmental Biology - Animal, 2009)

A ThCAP gene from Tamarix hispida confers cold tolerance in transgenic Populus (P. davidiana × P. bolleana) - Xiao-Hong Guo; Jing Jiang; Shi-Jie Lin; Bai-Chen Wang; Yu-Cheng Wang; Gui-Feng Liu; Chuan-Ping Yang (Biotechnology Letters, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Cloning and sequence analysis of the gene encoding 19-kD subunit of Complex I from Dunaliella salina - Yi Liu; Dai Rong Qiao; Hong Bo Zheng; Xu Lan Dai; Lin Han Bai; Jing Zeng; Yi Cao (Molecular Biology Reports, 2008)

Cloning and characterization of largemouth bass (Micropterus salmoides) myostatin encoding gene and its promoter - Shengjie Li; Junjie Bai; Lin Wang (Journal of Ocean University of China, 2008)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Fluorine distribution in aquatic environment and its health effect in the Western Region of the Songnen Plain, Northeast China - Bo Zhang; Mei Hong; Bai Zhang; Xue-lin Zhang; Yong-sheng Zhao (Environmental Monitoring and Assessment, 2007)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

Effect of fenofibrate on the level of asymmetric dimethylarginine in individuals with hypertriglyceridemia - Tian-Lun Yang; Mei-Fang Chen; Xin Xia; Bai-Lin Luo; Yuan-Jian Li (European Journal of Clinical Pharmacology, 2006)

Identifying the Scale Thresholds for Field-Data Extrapolation via Spatial Analysis of Landscape Gradients - Chi-Ru Chang; Pei-Fen Lee; Mei-Ling Bai; Tzer-Ton Lin (Ecosystems, 2006)

A locus for familial generalized lentiginosis without systemic involvement maps to chromosome 4q21.1–q22.3 - Qinghe Xing; Xiangdong Chen; Mingtai Wang; Wenjie Bai; Xin Peng; Rui Gao; Shengnan Wu; Xueqing Qian; Wei Qin; Jianjun Gao; Guoyin Feng; Lin He (Human Genetics, 2005)

Fenofibrate decreases asymmetric dimethylarginine level in cultured endothelial cells by inhibiting NF-κB activity - Tian-Lun Yang; Mei-Fang Chen; Bai-Lin Luo; Qi-Ying Xie; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Effect of fenofibrate on LDL-induced endothelial dysfunction in rats - Tian-Lun Yang; Mei-Fang Chen; Bai-Ling Luo; Jing Yu; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)

IGF-I of Orange Spotted Grouper Epinephelus Coioides: cDNA Cloning, Sequencing and Expression in Escherichia Coli - F.T. Shi; W.S. Li; C.H. Bai; H.R. Lin (Fish Physiology and Biochemistry, 2002)

Biodiversity and conservation in the Tibetan Plateau - Zhang Bai-ping; Chen Xiao-dong; Li Bao-lin; Yao Yong-hui (Journal of Geographical Sciences, 2002)

Early genes responsive to abscisic acid during heterophyllous induction in Marsilea quadrifolia - Ting-Chang Hsu; Hung-Chi Liu; Jang-Shiun Wang; Rung-Wu Chen; Ying-Chuan Wang; Bai-Ling Lin (Plant Molecular Biology, 2001)

Unique chromosome identification and sequence-specific structural analysis with short PNA oligomers - Caifu Chen; Bai-lin Wu; Tao Wei; Michael Egholm; William M. Strauss (Mammalian Genome, 2000)

Somatic mosaicism for deletion of the entire NF1 gene identified by FISH - Bai-Lin Wu; Richard G. Boles; Hana Yaari; Stanislawa Weremowicz; Gretchen H. Schneider; B. R. Korf (Human Genetics, 1997)

A study of optimal configuration and control of a multi-chamber balloon for intraaortic balloon pumping - Jing Bai; Hong Lin; Zibin Yang; Xiaoqing Zhou (Annals of Biomedical Engineering, 1994)